Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

Unlocking the phosphorus reservoir in wet waste: Speciation, circular recovery strategies, and inter-phase migration - Xiaojian Dong; Shuang Li; Xiaoxia Chen; Qian Ping; Ming Zheng; Lin Wang; Yongmei Li (Bioresource Technology, 2027)

Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

Beyond direct pathway engineering: reprogramming Fusarium fujikuroi from a GA3 producer into a GA4+7 factory - Hang Xiao; Tao-Xu Lu; Ming-Han Li; Ya-Ling Yi; Hao-Yang Li; Yu-Ke Cen; Zhi-Qiang Liu; Yug-Guo Zheng (Bioresource Technology, 2026)

Epigenetic silencing of DLEC1 correlates with tumor immune microenvironment and predicts immunotherapy prognosis in multiple cancers - Ruijie Ming; Qi Xiong; Shuh-Ying Tan; Lili Li; Shujie Bao; Jianhua Wang; Lijuan Zhao; Xiaoqian He; Zeze Zheng; Yan Wang; Xiaoyu Liu; Jun Tang; et al. (Human Genetics, 2026)
Cancer remains a major health issue globally, with increasing incidence and mortality rates. While immunotherapy has revolutionized cancer treatment, not all patients benefit, urging the identification of predictive biomarkers. This study utilized public datasets and tumor samples to examine the expression and promoter hypermethylation of DLEC1 in normal and tumor tissues, to evaluate its potential as prognostic and immunotherapy marker. In vitro and in vivo experiments on breast cancer (BrCa) cell lines were conducted to explore the functions and mechanisms of DLEC1 . The prognostic significance of DLEC1 downregulation and its impact on immune cell infiltration and immunotherapy efficacy were analyzed using the GEO and TCGA databases. DLEC1 was frequently downregulated and methylated across multiple cancers. In BrCa, expression of DLEC1 inhibited tumor cell proliferation, induced apoptosis, and activated the interferon lambda1 signaling pathway, indicating its important role as a bona fide tumor suppressor and immunoregulator. High DLEC1 expression correlated with better prognosis in several cancer types and with increased immune cell infiltration. Cancer patients with high DLEC1 expression showed improved overall and progression-free survival under immune checkpoint inhibitor therapies, such as anti-CTLA4, anti-PD1 and anti-PDL1. DLEC1 promoter hypermethylation is a promising biomarker for cancer prognosis and potential immunotherapy response prediction. Its expression and promoter hypermethylation status could thus help to guide clinical treatment strategies for cancer patients, particularly of breast cancer.

High carbon burial fluxes in lakes do not equate to stable carbon sinks: Evidence from typical large river-connected lake systems - Zheng Huang; Shilan Wang; Zhongwu Li; Fengwei Ran; Ming Chen; Xiaodong Nie; Xinyu Ling; Chengyu Zhong (Water Research, 2026)

Seismic response of tunnels adjacent to saturated fault zones under SV-wave: Effects of fluid-solid coupling and fault properties - Ming-Yu Chang; Yu-Quan Liu; Yu-Sheng Shen; Wei Zheng; Yang Yu; Ming-Chao Yan; Yong-Yi Li (Tunnelling and Underground Space Technology, 2026)

Petrogenesis of the middle Jurassic Luorong syenite and Xishan A-type granite in the southern Qin-Hang belt, South China: Implications for contrasting mixed sources and divergent differentiation pathways - Zheng-Wei Qin; Xi-Yao Li; Wolfgang Siebel; Jian-Ming Fu; Sanzhong Li; You-Yue Lu; Yu-Xiao Yao; Yu-Shuai Yu; Bo Bao (Journal of Asian Earth Sciences, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Retention characteristic of canopy litter delays carbon release in Cunninghamia lanceolata plantations: Evidence from an aerial decomposition experiment - Xiaojian Wu; Zaifang Yin; Chenxingyi Zheng; Lindong Sun; Ming Li; Pengfei Wu; Kai Wang; Xiangqing Ma (Forest Ecology and Management, 2026)

MOF photo-Fenton catalysis for pharmaceutical removal: Morphology modulation and recyclable immobilization - Zhiyong Chen; Ming Zheng; Bing Gao; Shiyang Li; Liang Tang; Shane A. Snyder; Minghong Wu (Chemical Engineering Journal, 2026)

Deciphering the structural and stoichiometric regulation of anaerobic digestion: A cross-scale perspective from molecular thermodynamics to methanogenic pathways - Qian Ping; Xiaoxia Chen; Yiwei Jin; Yifeng Chen; Ming Zheng; Lin Wang; Yongmei Li (Bioresource Technology, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Plastic fragments impair soil organic carbon persistence through reshaping microbial metabolism and decreasing plant carbon supply in dryland ecosystems - Meng-Ying Li; Wei Wang; Yudi M. Lozano; Jia-Yao Yang; Yue Ma; Xiao-Bin Xiong; Shuang-Jin Huang; Muhammad Ashraf; Jian-Ming Li; Yun-Li Xiao; Zheng-Guo Cheng; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2026)

Viscous fragmentation and topology-induced residual gas trapping during gas–water displacement in fracture networks - Kangsheng Xue; Hai Pu; Yanlong Chen; Ming Li; Yu Wu; Lulu Liu; Qingyu Yi; Zheng Ma (Advances in Water Resources, 2026)

Unraveling the anti-listerial activity of noni fruit essential oil: Omics-based mechanistic insights and application in salmon preservation - Qiongping Hong; Jiamu Kang; Xinyu Li; Shanshan Zheng; Ming Yang; Lin Zhang; Yuyun Lu (International Journal of Food Microbiology, 2026)

Integrating ecological networks and metagenomics to decipher core microbial drivers of organic acid metabolism during heaped fermentation of sauce-flavor Baijiu - Hong-Yan Zhang; Ting-Cai Huang; Li-Juan Chai; Wei Shi; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Research International, 2026)

Decoding the thermocyclic solar-driven fermentation: Multi-omics insights into microbial and metabolic dynamics of traditional Chishui river basin soy sauce - Wei-Qin Deng; Zhen-Ming Lu; Xiong-Bo Li; Zhi-Yi Fan; Ting Li; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Chemistry, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Electromechanically reconfigurable graphene-hydrogel sensor with stress-buffering interface for multi-functional sensing - Yi Wang; Chenling Wu; Yixiao Li; Kun Zheng; Tong Li; Yutao Song; Chan Ye; Zheng Fang; Chenxin Zhu; Ming Zhang; Rong Yang; Lei Liao (Chemical Engineering Journal, 2026)

High-performance biaxially oriented polylactic acid films enabled by long-chain branching: microstructural evolution and property tuning - Yu-Hang Zhang; Xing-Liang Li; Zheng-Ming Li; Ze-Yong Zhao; Xiu-Li Wang; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Harnessing sunlight-driven peracetic acid for rapid pathogen inactivation in surface waters - Yibo Wang; Ming Zheng; Jialin Li; Xinyu Ma; Shenqi Lu; Zhiyong Chen; Yajie Gao; Jiayi Wang; Wenhui Qiu; Rongrong Xuan (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Tracking clinically critical antibiotic-resistant bacteria and resistance genes in biogas slurry-amended soil: occurrence, enrichment and vertical distribution - Jiwei Li; Yi Lu; Xingshuo Wang; Lifeng Ping; Hua Li; Guanyu Zheng; Ming Hung Wong; Shengdao Shan (Bioresource Technology, 2026)

Dietary compound probiotics enhance milk fat production, nutrient digestibility, and modulate hindgut health in lactating dairy cows - Danni Wei; Suran Liu; Meiling Zheng; Ming Deng; Baoli Sun; Yaokun Li; Guangbin Liu; Dewu Liu; Wenfeng Hu; Qingshen Liu; Yongqing Guo (Animal Feed Science and Technology, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Disruption of OsGONST3 reduces grain cadmium accumulation without yield penalty in field-grown rice - Jing Huang; Qiang Zhang; Fang Wei Yu; Ming Qing Liu; Huai Kang Jing; Shen Yun Wang; Hao Yu Wang; Jia Qi Li; Lu Zheng; Hua Shao; Xiao Lin He; Ren Fang Shen; et al. (Journal of Hazardous Materials, 2026)

Cutting performance and fragmentation behavior of rock under confining stress: role of heterogeneity - Zheng Yang; Ming Tao; Tubing Yin; Yanliang Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Dual-catalyst catalytic fast pyrolysis coupled with microwave hydrothermal pretreatment: A novel strategy for enhanced aromatics production from biomass - Ming Huang; Mengfei Yu; Li Zhou; Chang Ma; Wei Cai; Xiaogang Zheng; Lichun Dong; Zhongqing Ma (Fuel, 2026)

Unraveling the fruity aroma in soy sauce aroma Baijiu by pinpointing key aroma compounds and evaluating their sensory impact - Yu-Jie Li; Xiao-Juan Zhang; Lan Wu; Zhen-Ming Lu; Lu-Qin Tian; Yun-Hao Lu; Li-Juan Chai; Hong-Yu Xu; Xiao-Long You; Yuan-Long Chi; Feng Hu; Zheng-Hong Xu (Food Chemistry, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Long-term exposure to air pollution, proteomic aging clocks, and liver-related outcomes in Chinese adults - Yating Huang; Dong Sun; Axing Lv; Jun Lv; Canqing Yu; Dianjianyi Sun; Pei Pei; Ling Yang; Yiping Chen; Huaidong Du; Dan Huang; Xiaoming Yang; et al. (Environmental Research, 2026)

Early pregnancy exposure to organophosphate esters and risk of infant atopic dermatitis: Sex-Specific association analyses in a community-based birth cohort - Limin Dou; Zhiyuan Du; Youping Tian; Huaqing Zhong; Haisheng Huang; Rongqi Xiang; Yingying Ni; Xiaohua Zhang; Weili Yan; Ming Li; Weiwei Zheng; Ying Ye (Environmental Pollution, 2026)

A unified 3D SPH framework for simulating the landslide-damming-breaching-flood cascading hazards - Shuang Li; Ming Peng; Zhenming Shi; Hongchao Zheng; Chengzhi Xia; Maomao Liu; Yan Zhu (Engineering Geology, 2026)

Transformation of waste cotton fibers into pore-adjustable photothermal aerogels for improved salt tolerance and enhanced desalination performance - Xin Zhong; Jiaqi Fu; Yuhang Yu; Shengjie Zheng; Weiming Wang; Jun Xiong; Ming Li (Chemical Engineering Journal, 2026)

Construction and mechanistic insights of salt-responsive nanofiltration membranes with biodegradable polylactic acid support layers for high-salinity textile wastewater treatment - Shenghui Liu; Yuxia Li; Biqin Chen; Xing Zheng; Xiaojun Huang; Dongfei Li; Ming Wang (Chemical Engineering Journal, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Concentration-dependent variation in carbon allocation and microbial assembly in chain elongation microbiota: Comparative effects of acetate, ethanol, and lactate - Ya-Ning Song; Li-Juan Chai; Ling Ao; Jun-Lan Mei; Yu-Long Li; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Bioresource Technology, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

A recombinant baculovirus expressing multi-epitopes elicits protective immunity against ALV-J infection in chickens - Yingyi Chen; Yuqin Zheng; Rongmao Chen; Xueqing Li; Wanlin Jiao; Ming Liao; Min Feng; Manman Dai (Veterinary Microbiology, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

Can perceptual strain index predict physiological strain? A human-participant experiment in low-intensity activity with moisture impermeable protective clothing - Sheng He; Jie Yang; Song Chen; Feifan He; Jialin Wu; Xin Zheng; Ming Fu; Yayun Li; Wenguo Weng (Building and Environment, 2026)

Exploring legal‐ and health‐risk messaging to reduce demand for elephant skin - Beilu Duan; Zac Posada‐Baynham; Joceline Yong; Xiaoxi Zhang; Zhan Chen; Anita K. Y. Wan; Jingjing Zhao; Alexander Clark; Lishu Li; Wuji Zheng; Tien Ming Lee (Conservation Biology, 2026)
Asian elephants ( Elephas maximus ) are poached for an illegal trade in their skins, which are used in traditional medicine in Africa and Asia. We explored whether messages about the legal and health risks of using elephant skin for medicinal purposes (stomach illness) could reduce such consumption. We conducted a randomized controlled trial intervention experiment based on a health belief model. We showed 1673 residents at China's Yunnan–Myanmar border comic strips that portrayed these risks (legal‐risk and health‐risk treatments and control). Respondents were then asked for their perception of benefits and risks of using elephant skin and their consumption intentions for treating stomach illness (i.e., seek elephant skin, seek animal‐based traditional medicine, visit informal market, and visit hospitals). We used structural equation models to examine whether and how different messages affect consumption intentions. Compared with the control group ( n = 580), the comics that showed the legal risks of use of elephant skin ( n = 529) significantly reduced respondents’ intentions to seek elephant skin by 24% compared with the control group, particularly when the message conveyed that its use is not a cure. The health‐risk treatment ( n = 564) increased respondents’ intentions to go to the hospital when suffering from stomach illness and, unexpectedly, increased the intention of urban residents who had never heard of elephant skin as a treatment to look for it by 40% compared with those of urban residents in the control group. Our results revealed that interventions tailored to specific audience segments are necessary to prevent unintended, negative consequences of public messaging conservation interventions.

Multi-scale Microstructure Evolution Characteristics of Gas-Induced Coal Damage: A Study Based on Nuclear Magnetic Resonance Cryoporometry and Site-Specific Scanning Electron Microscopy - Wenqi Zheng; Feng Gao; Hanpeng Wang; Bing Zhang; Yue Niu; Wei Wang; Chunbo Zhou; Zhizhen Zhang; Jiahui Song; Li Ming (Rock Mechanics and Rock Engineering, 2026)

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Genome-wide analysis of the CHIA gene family and functional characterization of ScCHIA1 under cold and osmotic stress in jojoba (Simmondsia chinensis) - Xue Zhu; Ming Zhu; Luping Li; Ronghao Xia; Huini Xu; Fei Gao; Lamei Zheng (Plant Science, 2026)

UV–vis light induced water splitting and photo-Fenton elimination of tetracycline over Cu3P/Bi2WO6 Z-scheme heterojunction - Ming Huang; Yifang Xiao; Jie Li; Xiaogang Zheng (Journal of Water Process Engineering, 2026)

K-feldspar oscillatory zoning constraining efficient crystal fractionation in high-silica magma: A case study of the Dacaowu pluton, eastern China - De-Zhou Chen; Jian Li; Ming-Chun Song; Wen-Yan Cai; Chao Zhang; Zheng-Yang Zhang; Xu-Yan Bian (Journal of Geochemical Exploration, 2026)

Dissecting the division of labor among five jiuqu starters in sesame-flavor baijiu fermentation - Yan-Yan Ma; Wei Zhang; Hui Tian; Tian-Tian Meng; Sheng-Bing Yang; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Wen-Qing Zhang; Chuan-Qiang Gao; Zhen-Ming Lu; Zheng-Hong Xu (Food Bioscience, 2026)

Synergistic impacts of probiotics and prebiotics (synbiotics) in fish farming - Vicent Michael Shija; Ngoc Tuan Tran; Akram Ismael Shehata; Xianyuan Zheng; Ming Zhang; Md Akibul Hasan Bakky; Jia Cai; Shengkang Li (Fish & Shellfish Immunology, 2026)

Cattail leaf-based photothermal aerogel for all-day freshwater production powered by solar energy and Joule heating - Jiaqi Fu; Jing Wu; Ziqi Liu; Shengjie Zheng; Yuming Wu; Jun Xiong; Ming Li (Desalination, 2026)

Variations in microbial community characteristics in runoff driven by maize growth stages under simulated rainfall in the semi-humid southern loess plateau of China - Zihan Yan; Guo Chen; Qingwei Zhang; Lihong Jia; Hao Wang; Chao Chang; Fengbao Zhang; Jian Wang; Ming Li; Ding He; Wei Zheng (CATENA, 2026)

Computational-guided semi-rational design to reprogram phospholipase D into industrially robust enzyme - Xiao-Li Kong; Peng Zhang; Zheng-Qiang Qin; Chang Su; Heng Li; Zhen-Ming Lu; Jin-Song Gong; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2026)

Exploring primate immune responses to SLA-I/II knockdown pig xenografts in humanized mice and rhesus monkeys - Ming-Hui Fang; Hao Feng; Kai Xu; Tang Hai; Song Chen; Ji-Long Ren; Wei-Gang Wang; Yuan-Tao Wang; Jun Zou; Fei Xu; Zi-Yue Wang; Yi-Wei Yao; et al. (Science China Life Sciences, 2026)

Novel cembranoid diterpenoids from the leaves of Nicotiana tabacum with anti-proliferative activity - Xin-Yao Li; Jia-Lin Zhang; Ming-Zhen Liu; Qingxia Zheng; Guo-Xu Ma; Zhong-Hao Sun; Hua Wei (Natural Product Research, 2026)

Glaucoma Drug Target Prioritisation Informs Disease-specific Therapeutic Potentials of Targeting SMAD4 - Chaohui Bao; Tingting Tan; Yisheng Yang; Chenxu Gao; Kaiwen Liu; Chang Lu; Rulin Guo; Zheng Wang; Jiantao Shi; Jinchen Li; Ming Ni; Hai Fang; et al. (Phenomics, 2026)

Probiotic Potential of Indigenous Cetobacterium somerae R9 in Mud Crab (Scylla paramamosain) - Jinkun Li; Ngoc Tuan Tran; Yifan Lei; Taoqiu Deng; Huifen Liang; Zhinuo Du; Xianyuan Zheng; Md. Akibul Hasan Bakky; Ming Zhang; Yongzhen Zhao; Zhixun Guo; Shengkang Li (Probiotics and Antimicrobial Proteins, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Recyclable hygroscopic hydrogels with dynamic networks enable efficient solar-driven atmospheric water harvesting - Fu-Yao Zhong; Chen-Xi Li; Lu-Bin Zhong; Chao-Yang Guo; George Zheng Chen; Bo Weng; Jun He; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2026)

Smelling saltiness: Retronasal aroma compounds contributing to saltiness perception in Nanjing water-boiled salted duck - Jinxue Hou; Yanzhao Zheng; Tianran Huang; Yu Hua; Guanghui Li; Xing Liu; Ming Huang (Food Research International, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Association of plasma n-3 polyunsaturated fatty acid with gut mycobiome and implications for glucose homeostasis - Congmei Xiao; Yue Xi; Xinyu Wang; Chang Gao; Ruiqi Shi; Zelei Miao; Yuhui Liang; Wanglong Gou; Ke Zhang; Chun Wang; Xinxiu Liang; Meng Ye; et al. (Science China Life Sciences, 2026)

Competitive Effects of Gas Pressure and Confining Pressure on Crack Deformation and Failure Characteristics in Gas-Bearing Coal - Wenqi Zheng; Feng Gao; Hanpeng Wang; Chunbo Zhou; Zhizhen Zhang; Li Ming (Rock Mechanics and Rock Engineering, 2026)

A Novel Indigenous Probiotic, Clostridium moniliforme G18, Confers Health Benefits to Mud Crabs (Scylla paramamosain) - Taoqiu Deng; Zhinuo Du; Huifen Liang; Dexin Jiao; Jinkun Li; Yuqing Zheng; Ming Zhang; Bin Zhang; Yongzhen Zhao; Zhixun Guo; Ngoc Tuan Tran; Shengkang Li (Probiotics and Antimicrobial Proteins, 2026)

Cross-domain microbial interactions mediate soil multifunctionality during crop growth stages - Guo Chen; Chao Chang; Zihan Yan; Hao Wang; Qingwei Zhang; Jian Wang; Ming Li; Wei Zheng; Ding He; Biao Zhu (Applied Soil Ecology, 2026)

Behavioral interventions to reduce demand for threatened freshwater turtles as pets - Wuji Zheng; Beilu Duan; Anita Kar Yan Wan; Alexander Clark; Toby Park; Kristina Londakova; Freddy Parker; Xiaoxi Zhang; Lishu Li; Tien Ming Lee (Conservation Biology, 2026)
Growing demand for freshwater turtles as pets has fueled illegal trade and accelerated wild population declines, underscoring the need for theory‐based demand‐reduction interventions. We conducted a three‐part randomized controlled trial with active turtle keepers ( n = 1800) in China to test conservation‐ and legality‐framed messages by comparing purchase intention before and after the intervention between treatment and control groups for two globally threatened species: Indochinese box turtle ( Cuora galbinifrons ) and the big‐headed turtle ( Platysternon megacephalum ). Drawing on an extended theory of planned behavior (TPB), we modeled frame‐specific claim agreement, attitudes, subjective norms, perceived behavioral control, and perceived self‐efficacy with structural equation models. Conservation and legality messages significantly reduced purchase intention relative to a no‐message control (mean declines of 0.37–0.84 points on a 5‐point scale across treatment arms) primarily through indirect psychological pathways. Conservation messages heightened harm‐based evaluations and moral concern, whereas legality messages strengthened illegality appraisals and deterrence‐related cognitions. Across models, claim agreement was a key proximal antecedent, subjective norms consistently predicted lower self‐efficacy, and self‐efficacy emerged as the most proximal positive predictor of intention. Perceived behavioral control showed no direct effect. Species‐specific differences in pathways, suggestive of reactance in the big‐headed turtle conservation model, reflected variation in legal signals and market narratives. Our findings highlight the importance of claim agreement, injunctive norms, and species context in shaping intervention outcomes. Demand‐reduction campaigns may be more effective when tailored to species‐specific legal and market conditions and when normative cues are paired with feasible alternatives and practical guidance that makes compliance achievable.

Two new diterpenoid alkaloids from Aconitum legendrei Hand.-Mazz - Ming-Lu Zheng; Feng-Tai Qiu; Qing Tang; Lin Chen; Qin He; Shuai Huang; Xian-Li Zhou (Natural Product Research, 2026)

Cooling energy demand for maintaining frozen wall thickness in artificial ground freezing - Xu Li; Rui-ming Li; Xiao-kang Li; Shuang Liu; Zheng Yang (Tunnelling and Underground Space Technology, 2026)

Effect of high-pressure homogenization on surfactant-free starch-oil films - Xi-ying Xu; Dong-ming Gao; Xu Yao; Zi-xu Zheng; Zong-qiang Fu; Gang Li; Fei-fei Li (Journal of Food Engineering, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Study on thermophysiological responses for heavy-load activity in hot environment: factors interaction experiments - Sheng He; Liangchang Shen; Song Chen; Feifan He; Jie Yang; Ming Fu; Jialin Wu; Xin Zheng; Yayun Li; Wenguo Weng (Energy and Buildings, 2026)

Intelligent ROS-triggered NO and isotretinoin co-delivery hydrogel dressings for microenvironment modulation and rapid repair of diabetic wounds - Bin Lu; Hanzhang Wang; Junyi Zhou; Jieying Lai; Xue Zheng; Shuang-Zhuang Guo; Li-Ming Zhang (Chemical Engineering Journal, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Berberine Hydrochloride Enhances the Fluconazole Susceptibility of Candida albicans through Multiple Targets - Lu Yu; Weijia Yi; Wenming Zheng; Dongming Zheng; Jiaqi Li; Lihua Luo; Guining Luo; Ming Xia; Li You; Jiangyan Yong (Current Microbiology, 2026)

Detecting extralateral mass variations using inclined satellite pair configurations - Tiantian Qing; Hao Zhou; Ming Li; Le Suo; Zhu Zhu; Mingyang Xia; Yaozong Li; Lijun Zheng; Shuyun Zheng; Siyou Xu; Zhicai Luo (Advances in Space Research, 2026)

Palladium recovery from wastewater using electric field-enhanced ultrafiltration assisted with polyethyleneimine and electro-decomplexation/electrodeposition - Hang Yin; Wenwu Li; Shuhuai Shen; Saina Zheng; Dafang Fu; Jianglei Xiong; Ming Chen (Journal of Cleaner Production, 2026)

Occurrence, landscape impact, and risk assessments of pesticides in a major river basin of a tropical island, South China - Ling Mo; Bin Tang; Li-Ke Chen; Jun Xiang; Ming-Yang Wang; Kai-Yi Wu; Ming-Zhong Ren; Qiao Xing; Li-Cheng Wang; Jing Zheng (Environmental Pollution, 2026)

Mitochondrial stress primed cGAS-STING activation synergized with NF-κB signaling for enhanced antitumor immunotherapy - Chengzhilin Li; Fanyu Yuan; LiHang Lou; Ziang Xu; Nianlei Zhang; Changshun Huang; Xinyu Wang; Wenyu Zhang; Tingjian Zu; Ming Xia; Runxiao Zheng (Chemical Engineering Journal, 2026)

Hobbyist preferences for pet freshwater turtles - Jingjing Zhao; Zhan Chen; Beilu Duan; Wuji Zheng; Anita Kar Yan Wan; Xiaoxi Zhang; Lishu Li; Tien Ming Lee (Conservation Biology, 2026)
The burgeoning pet trade is a primary threat to wild freshwater turtles worldwide. Although the risks from commercial exploitation of turtles have been discussed widely, there is little empirical research on preferences for pet turtles from a hobbyists’ perspective. We conducted an online survey of nearly 2000 turtle hobbyists recruited via discussion forums in China. We collected information on turtle‐keeping experiences, past purchase behaviors, knowledge about the protection status of certain endangered species, and awareness of legality in the trade. We framed discrete choice experiments around different hypothetical scenarios about wild population statuses and captive‐breeding market conditions. We then used a random parameter logit model and a latent class logit model to identify key influencing factors and to explore the level of heterogeneity among turtle hobbyists. Consumers preferred inexpensive turtles, captive‐bred turtles for which traders’ certificates (e.g., business licenses, breeding permits, and proof of legal species origin) were available, online purchase, and delivery by the postal service. They were especially willing to buy turtles for which captive‐breeding techniques were well developed and turtles that had wild populations that were stable or increasing. Preferences were sometimes affected by social factors; for example, some consumers more willingly accepted high‐priced turtles under social influence, rather than when such factors were absent. We identified 3 distinct types of turtle consumers with heterogeneous preferences: 40.3% preferred cheap turtles, 31.1% preferred captive‐bred turtles, and 28.6% preferred both captive‐bred and inexpensive species. Overall, our results can inform interventions and campaigns to conserve freshwater turtles by targeting hobbyists with specific profiles.

Source Control of the Seismic Energy Radiation in Rock Blasting - Yongzhen Li; Wenbo Lu; Yang Wang; Ming Chen; Peng Yan; Ting Meng; Jiawei Zheng (Rock Mechanics and Rock Engineering, 2026)

Application of a Modified In Situ Perfusion Model to Quantify Intestinal Drug Excretion and Transporter-Mediated Interactions after Intravenous Administration - Rongjin Sun; Li Li; Lu Wang; Zuoxu Xie; Dinh Bui; Zicong Zheng; Xiaofeng Zhao; Jia Hao; John Chen; Taijun Yin; Yiding Hu; Yurong Lai; et al. (The AAPS Journal, 2026)

Electrochemical activation of peroxymonosulfate with a boron-doped diamond anode boosts short-chain fatty acid production from waste activated sludge - Kexin Li; Zhendong Lei; Yujia Zhang; Jinling He; Ming Zheng; Ai Zhang; Pin Gao; Xiang Li; Gang Xue (Water Research, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Seasonal variation regulates the efficacy of phytoremediation strategies on the rhizosphere resistome in urban river ecosystems - Yu Xin; Li-Hua Liu; Lin Liu; Shao-Hua Chen; Yu-Ming Zheng; Quan-Bao Zhao (Journal of Hazardous Materials, 2026)

Flavor profiles and microbial mechanisms of suansun: A comparative study of homemade and commercial production - Qiao Qian; Zheng-Pei Chen; Ke Li; Sha-Sha Fang; Zhen-Ming Lu; Hong-Yu Xu; Zheng-Hong Xu (International Journal of Food Microbiology, 2026)

Advancements in metal-organic frameworks for alkaline oxygen evolution reaction: mechanistic insights, catalyst stability and applications - Ruo-Jin Liu; Xue-Ying Yang; Zheng-Yi Wu; Na Xu; Fu-Li Wang; Ren-Qing Lv; Guanqun Han; Bin Dong; Yong-Ming Chai (Fuel, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Engineering a high-performance, sustainable food packaging film: Zinc-doped carbon dots reinforced konjac glucomannan nanocomposite - Lijun Wu; Jiacheng Li; Yin Zhang; Ming Zhang; Xiaoli Han; Tian Liang; Jian Liu; Qingfa Zhang; Lu Wang; Lei Zheng (Food Packaging and Shelf Life, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Enhanced mechanical strength and sustainable biomass-derived bipolar membranes with in-situ embedded LDH nanosheets for efficient water splitting - Ming Li; Jinyun Xu; Haitao Liu; Wancun Huo; Yanyan Ji; Mingming Feng; Shuai Feng; Caixia Liu; Qingqing Zhu; Wenju Zhu; Chunming Zheng; Xiaohong Sun (Chemical Engineering Journal, 2026)

A net-like colloid with peculiar CO2 sorption behavior formed by aggregation of organic ligand molecules in water - Jin Cai; Wan Chen; Hai Li; Xin Zheng; Han Tang; Ming-Ke Yang; Zi-Xuan Huang; Zi-Ying Zhao; Peng Xiao; Yun-Lei Peng; Xian-Ren Zhang; Long-Long Xie; et al. (Chemical Engineering Journal, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Effects of walking activity on micro-environment heat convection and thermal comfort in chemical protective clothing - Sheng He; Jie Yang; Feifan He; Song Chen; Jialin Wu; Liangchang Shen; Xin Zheng; Ming Fu; Yayun Li; Wenguo Weng (Building and Environment, 2026)

Understanding the role of C5a/C5aR1-mediated complement activation pathway in tumor progression and therapy resistance - Lemei Zheng; Jianxia Wei; Mengna Li; Changning Xue; Qingqing Wei; Zubing Wu; Xiaolong Li; Ting Zeng; Huizhen Xin; Wei Xiong; Hongyu Deng; Ming Zhou (Science China Life Sciences, 2026)

Daily-scale spatiotemporal prediction of thin sea ice thickness during the early freezing season based on EOF-Trans - Jikun Liu; Guoping Zhang; Shuai Xing; Ming Gao; Pengcheng Li; Dandi Wang; Bo Zheng (Frontiers in Marine Science, 2026)
The accelerated decline of Arctic sea ice is profoundly reshaping regional climate regimes. Sea ice thickness (SIT), particularly under thin-ice conditions, is an important indicator for assessing early-season Arctic sea ice variability, and accurate prediction of its spatiotemporal evolution during the early freezing period is essential for characterizing short-term sea ice changes. In recent years, deep learning has emerged as a complementary approach to traditional sea ice prediction methods. However, existing deep learning-based studies have not fully exploited the large-scale spatial patterns and temporal contextual dependencies inherent in satellite-derived sea ice thickness. To address this limitation, this study proposes a spatiotemporal prediction framework named EOF-Trans for predicting daily-scale variability of thin sea ice thickness during the early freezing season. The method employs Empirical Orthogonal Functions (EOF) to decompose the sea ice thickness field into temporal mode series, utilizes a Transformer architecture to learn the temporal evolution characteristics, and subsequently reconstructs the predicted outputs back into the spatial thickness field by EOF, thereby enabling spatiotemporal sea ice prediction up to a leadtime of 21 days. Experimental results in the Beaufort Sea indicate that the proposed EOF-Trans framework significantly outperforms numerical models and classical deep learning architectures such as U-Net and ConvLSTM. On the 2022–2023 test set, it achieves a correlation coefficient of 88.04%, representing a 2% improvement over U-Net. Even at a leadtime of 21 days, the correlation remains approximately 84%, with the maximum spatial bias not exceeding 0.5 m. These results indicate that EOF-Trans effectively captures spatiotemporal regularities present in thin sea ice thickness, providing a complementary data-driven perspective for short-term sea ice prediction during the early freezing season.

Quantifying The Evolution of Rock Stiffness During Pre-peak Cyclic Loading: Influence of Porosity and Lithology - Zhao-Qiang Zheng; Li Zhuo; Jian-Liang Pei; Hong-Qiang Xie; Ming-Li Xiao; Huai-Zhong Liu (Rock Mechanics and Rock Engineering, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Hydrochemistry based positive matrix factorization combined with stable isotopes of nitrogen and oxygen based Bayesian mixing model revealed the source and dynamics of the main pollutants in three urban lakes in Nanchang City, China - Fangwen Zheng; Tianning Li; Linsen Tang; Xihong Hu; Jinfu Liu; Ming Li (Journal of Environmental Chemical Engineering, 2026)

Construction of an efficient synergistic catalytic system using DBD plasma and Fe-TiO2-rGO/HCP catalytic coating for ofloxacin removal - Ming Li; Liang Guo; Yimo Zhao; Shanshan Huang; Ruofei Jia; Lijiao Zheng; Yongyang Chen; Shanping Li (Journal of Contaminant Hydrology, 2026)

4E-based performance evaluation of a solar-assisted SOFC–CCHP system integrating zero-energy CO2 enrichment and cascade waste heat recovery - Yunxiu Ren; Ming Yang; Nan Zheng; Qiang Zhang; Zherui Ma; Wenjiang Zou; Shaolong Wang; Xingqi Ding; Qiushi Wang; Yimin Li; Liqiang Duan (Fuel, 2026)

An ultrasensitive electrochemiluminescent aptasensor comprising mesoporous polydopamine covered with CdTe quantum dots for organophosphorus pesticide detection - Ming Li; Junhu Zhao; Youhang Zhang; Fei Cheng; Heng Zheng; Haoqian Gao; Shucheng Tang; Xiaowan Li; Pier-Luc Tremblay; Tian Zhang (Food Chemistry, 2026)

Differential regulation of root iron plaque formation in a mangrove species, Kandelia obovata by biodegradable and conventional nanoplastics: Evidence from interfacial interactions, microbial communities, and redox conditions - Ming Li; Jie Gao; Nora Fung-Yee Tam; Haichao Zhou; Min Pan; Fred Wang-Fat Lee; Steven Jing-Liang Xu; Jian Liu; Kaixuan Deng; Peng Zheng; Cheng Ye; Xinran Ke; et al. (Environmental Pollution, 2026)

Creep of water-bearing soft rock and its influence on long-term rock mass stability - Zhao-Qiang Zheng; Li Zhuo; Jian-Liang Pei; Ming-Li Xiao; Huai-Zhong Liu; Hong-Qiang Xie; Tao Luo (Engineering Geology, 2026)

M2 macrophage-derived apoptotic extracellular vesicles mediate immune reprogramming and inhibit osteoclastogensis via mitophagy to ameliorate periodontitis - Jiahua Li; Tianyao Wang; Xueting Zhao; Yuting Chen; Xu Chen; Kai Zheng; Ming Zhang; Huiqing Gou; Yan Xu (Chemical Engineering Journal, 2026)

The change in structure and improvement of anti-aging effects of polysaccharides in Polygonati Rhizoma after the traditional “Nine Steaming-Nine Sun-Drying” - Yanhui Guan; Ruoyu Li; Zheng Lv; Nianguo Bo; Teng Wang; Yunjiao Guo; Zhengwei Liang; Jinyan Zhang; Qingfei Fan; Lingjing Dang; Ming Zhao; Junwen Chen (Carbohydrate Polymers, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Development and application of antibody-drug conjugates in gynecological cancers - Ruxi Zheng; Jiaojiao Zhang; Jianwei Zhou; Zhigang Zhang; Mengke Niu; Jing Fei; Kongming Wu; Ming Yi; Tianye Li (Science China Life Sciences, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Efficacy and safety of treatments for atopic dermatitis: a model based meta-analysis of randomized controlled trials - Lingxiao Zhang; Yiwen Gong; Xiang Gu; Yifan Liu; Ming Chen; Qianhui Yi; Jianmin Jia; Lujin Li; Ling Xu; Qingshan Zheng (European Journal of Clinical Pharmacology, 2026)

Long‐Term Dispersal Ability and Climate Drive Genetic and Biogeographic Divergence in Two Lizards With Contrasting Distribution Ranges - Shan Su; Wei Qian; Lu‐Wen Zhang; Xiang‐Mo Li; Li Ma; Xiao‐Ming Wang; Zheng‐Huan Wang; Xiang Ji (Journal of Biogeography, 2026)
Aims Long‐term dispersal ability fundamentally shapes genetic structure and biogeographic patterns, yet its role in driving divergence between closely related species with contrasting ranges remains less explored. Here, we assess its influence on genetic differentiation and range dynamics in two Eremias lizards, the widespread E. argus and the narrowly distributed E. brenchleyi . Location Northeast, Central North, and Northwest China. Taxon Mongolia racerunner Eremias argus and Ordos racerunner Eremias brenchleyi (Sauria: Lacertidae). Methods We sequenced two mitochondrial (COI and cyt b ) genes from 240 E. argus and 98 E. brenchleyi adults across their Chinese ranges, performed phylogenetic analyses using Maximum Likelihood and Bayesian Inference, assessed genetic diversity and differentiation via haplotype metrics and pairwise F ST , and projected suitable habitats under past, present and future climates using ensemble species distribution models (SDMs). Results The two species diverged approximately 4.28 million years ago. Eremias brenchleyi exhibited strong isolation‐by‐distance, high genetic differentiation, and limited post‐LGM (Last Glacial Maximum) demographic expansion, indicating topography‐constrained dispersal. In contrast, E. argus showed higher genetic connectivity and rapid expansion from the late LGM to the post‐glacial period. SDMs indicate that E. argus expanded following the LGM, while E. brenchleyi persisted in restricted ranges. By 2070, both species are projected to expand northward under SSP2‐4.5 and SSP5‐8.5, with E. brenchleyi benefiting more from warming in net range gain. Main Conclusions Long‐term dispersal ability, interacting with landscape and climate, drives genetic and biogeographic divergence. Eremias brenchleyi remains vulnerable to isolation and genetic erosion, while E. argus is threatened by climate‐driven range loss. Their contrasting responses underscore the necessity of integrating genetic and environmental data to understand species resilience under climate change.

Adaptive Surface-Borehole Seismic Profile Matching and Tying Using BiGRU: A Case Study of Ultra-Deep Zero-Offset VSP in the Tarim Basin - Teng-yu Wang; Da-jun Li; Zhen Zhang; Duo-ming Zheng; Bing Fang; Pei Liu; Jing-jing Zong (Applied Geophysics, 2026)

Regulation of air-sea CO2 flux and aragonite saturation state in coral reef ecosystems along the eastern coast of Hainan Island, China - Wei Yang; Zijia Zheng; Peiqiang Zhuang; Jianhang Zhang; Wei Deng; Shengyong Li; Yanmei Liu; Ming He; Yingfeng Chen; Bingbing Yu; Xinxin Xu; Xinxing Li; et al. (Marine Pollution Bulletin, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

A persistently active fast radio burst source embedded in an expanding supernova remnant - Chen-Hui Niu; Di Li; Yuan-Pei Yang; Yuhao Zhu; Yongkun Zhang; Jia-Heng Zhang; Zexin Du; Jumei Yao; Xiaoping Zheng; Pei Wang; Yi Feng; Bing Zhang; et al. (Science Bulletin, 2026)

Mechanisms driving anammox bacteria enrichment in constructed wetlands for self-purification of high-nitrogen polluted wastewater: Environmental gradients and microbial interactions - Lin Liu; Jie Li; Yu Xin; Quan-Bao Zhao; Yu-Ming Zheng (Journal of Environmental Sciences, 2026)

Low-cholesterol egg yolk lipids alleviated the development of atherosclerosis in ApoE −/− mice by regulating bile acid metabolism and gut microbiota - Le Cheng; Ming Zhang; Fang Wu; Jianguo Dong; Yifei Wang; Lin Dong; Yumeng Ma; Chenyan Zheng; Zihan Wang; Yixuan Li; Ran Wang; Fazheng Ren; et al. (Food Research International, 2026)

Accurate prediction and screening of Ni-based bimetallic catalysts for hydrogen production from biogas reforming: An interpretable machine learning study - Wen-ming Zhang; Bin Hu; Bo-yuan Zheng; Ji Liu; Qi Niu; Kai Li; Zhi-mo Fang; Bing Zhang; Qiang Lu (Chemical Engineering Journal, 2026)

ROS responsive polydopamine coated black phosphorus nanocarrier for enhanced methylprednisolone delivery in acute lung injury immunotherapy - Zhiwei Gao; Mengxue Mo; Qianyue Liu; Jiaxiao Li; Hongshuai Zheng; Yaohui Huang; Yan Liu; Jing Qian; Xuzhi Liang; Yuting Xiao; Yan Long; Chen Qian; et al. (Chemical Engineering Journal, 2026)

Trimethylamine N-oxide induced cognitive impairment through disruption of blood-brain barrier by inhibiting TGF-β pathway - Yue Liu; Hua-Yue Zhang; Xi-Yan Hong; Yi-Xiao Wu; Ming-Jie Li; Hua-Jun Zheng (Chemico-Biological Interactions, 2026)

Secondary metabolites from the arial parts of Hyssopus cuspidatus Boriss. and their chemotaxonomic significance - Jian-Kang Lu; Gui-Juan Zheng; Jing-Jing Li; Xiao-Xia Jiang; Jin-Xin Zhan; Chang-Hao Yu; Xu Wang; Yi-Xuan Zeng; Tian-Jiao Qi; Hong Liu; Hui-Ming Peng; Jin-Bo Fang (Biochemical Systematics and Ecology, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

Protein Phosphatase 1 Regulatory Subunit 17 (PPP1R17) Regulates Cerebral Ischemia and Ischemia–Reperfusion Brain Injury by Suppressing YAP1-Mediated Mitophagy - Ming Ma; Jiahui Yang; Zheng Li; Xiaohua Shi; Zhongxin Xu (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

1-NP hijacks endocrine-metabolic checkpoints and disrupts testicular steroidogenesis by suppressing the cAMP-PKA-CREB-HMGCR axis - Xin-xin Zhu; Wei-wei Zhang; Ming-yue Hao; Zheng-ya Chen; Bai-fan Wan; Ming-hui Niu; Xiu-liang Li; Jian-hua Wei; Su-ya Liu; Shuang-ling Mi; Hua Wang; De-xiang Xu; et al. (Toxicology Letters, 2025)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

SensoryCharacterization ofChicken soup at different temperatures by using check-all-that-apply (CATA) analysis and temporal dominance of sensations (TDS) - Mingcheng Zhang; Luyi Jin; Peng Yu; Ming Li; Di Yu; Kaixian Zhu; Duoduo Zheng; Wensheng Yao; Dengyong Liu (Food Research International, 2025)

Ethephon combined with synergist promoted grain formation by improving photosynthetic performance and floret development of maize - Zhi Wang; Zheng Liu; Ruixian Liu; Baoyuan Zhou; Xinbing Wang; Zaisong Ding; Renhe Zhang; Congfeng Li; Ming Zhao (Field Crops Research, 2025)

Effects of UHPC age and interfacial treatment on structural behavior of post-cast UHPC joints in prefabricated wall-base slab assemblies - Ding-Li Jin; Yong Yuan; Shou-Ming Zheng; Giovanni Muciaccia; János Lógó; Jiao-Long Zhang (Engineering Structures, 2025)

A label-free magnetic enrichment SERS platform for ultra-sensitive detection and AI intelligent identification of novel coronavirus variants - Yusi Peng; Dan Li; Yanyan Li; Shuai Zhao; Meimei Xu; Weida Zhang; Zheng Teng; Ming Liu; Masaki Tanemura; Yong Yang (Chemical Engineering Journal, 2025)

Synergistic regulation of BFe2O4/Fe2O3 (B = Mn, Co, Ni, Cu) nanoarray materials by crystal plane and interface engineering for highly selective detection of 2-CEES gas - Baosheng Li; Ming Zheng; Qiuyue Zheng; Jiahui Li; Xin Dong; Xianfa Zhang; Lihua Huo; Xin Zhou; Xiaoli Cheng; Yingming Xu (Chemical Engineering Journal, 2025)

A feasible strategy of photothermal nanocellulose/chitosan porous composite with brine tolerance and magnetic controllability for solar-driven polluted seawater purification - Yu Qiu; Chaoyang Zhang; Ming Zhang; Dingqiang Zheng; Dongsheng Song; Shoufu Long; Zhenghui Li; Zhe Zhang; Zhimin Zhao (Carbohydrate Polymers, 2025)

Balancing nitrogen metabolism to efficiently drive anti-tuberculosis ilamycins biosynthesis in Streptomyces atratus - Gaofan Zheng; Weiyan Zhou; Yingyue Gui; Yuxi Jiang; Yunfei Zhu; Junying Ma; Jianhua Ju; Xiujuan Xin; Baoli Li; Ruida Wang; Ming Zhao; Faliang An (Bioresource Technology, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

NK cells: shielding senescence homeostasis in the decidua during early pregnancy - Zi-Meng Zheng; Jia-Wei Shi; Li Wang; Ming-Qing Li (Seminars in Immunopathology, 2025)

Preclinical Safety Assessment of the Oral Administration of Lactobacillus plantarum GUANKE in Animal Models - Yuewen Yang; Yanlin Zhang; Ruixiang Sun; Wenjuan Du; Yangyang Liu; Lijun Zheng; Zhihong Ren; Ming ding Li; Jianguo Xu (Probiotics and Antimicrobial Proteins, 2025)

Syringaldehyde Ameliorates Cognitive Dysfunction in APP/PS1 Mice by Stabilizing the NLRP3 Pathway - Ruidan Chen; Hua Gao; Tianshu Zhu; Ni Zheng; Yan Jin; Ming Li; Zhiming Lu (Molecular Neurobiology, 2025)

Xuanhong Dingchuan Tang suppresses bronchial asthma inflammation via the microRNA-107-3p/PTGS2/MAPK axis - Xi Ming; Yingzhu Lu; Huihui Huang; Jialin Zheng; Tianzi Wang; Zhuoqun Li; Xingzhu Yu; Lei Xiong (Functional & Integrative Genomics, 2025)

Exploration of new azole derivatives containing ethanolamine moiety as anti-UC agents by inhibiting NF-κB/MAPK pathways - Ming-Qian Ju; Zheng-Xiao Huang; Qing-Yan Mo; Shuai Liu; Dong-Xue Wang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

Variation in the response of maize (Zea mays L.) root-shoot growth and grain yield to tillage practices under various soil compactions - Zhuohan Gao; Xinbing Wang; Zhigang Wang; Zaisong Ding; Lu Liang; Wenchao Zhen; Zheng Liu; Congfeng Li; Ming Zhao; Baoyuan Zhou (Field Crops Research, 2025)

Experiment and theoretical analysis on the rotational behavior of mass glulam bolted and glued-in rod joints - Zheng Su; Ming Xu; Zhaoyan Cui; Ruixiong Li; Hongxin Liu (Engineering Structures, 2025)

Sustainable bipolar membranes with three-dimensional flower-like spherical MgAl-layered double hydroxides doped quaternized chitosan for accelerated water dissociation and durability - Ming Li; Jinyun Xu; Hongze Li; Xiaoqing Wang; Shijie Shang; Xiaoyan Wang; Sijia He; Yanyan Ji; Li Yang; Rong Kuang; Chenxin Hu; Wenju Zhu; et al. (Desalination, 2025)

High-performance large-area ITO-free organic photovoltaics under indoor illumination enabled by a dual-interfacial engineering strategy - Jiaxin Gao; Zheng Li; Cuifen Zhang; Fangliang Dong; Zheng Tang; Ming Wang; Dengteng Ge; Zaifei Ma (Chemical Engineering Journal, 2025)

Intermediate-entropy metal hexagonal nanoplates for high-performance and durable formic acid electrooxidation - Shengming Li; Hu Yang; Xin Cheng; Jie Zheng; Yuan Liu; Chengwei Deng; Feng Ji; Sisi Liu; Ming Ge; Xiaolei Yuan (Chemical Engineering Journal, 2025)

Gradient degradation of ionomer along proton transport path in proton exchange membrane fuel cell catalyst layers: Mechanistic insights from 5000 h NEDC testing - Yan Xiao; Weibo Zheng; Tiankuo Chu; Jue Wang; Pingwen Ming; Bing Li (Chemical Engineering Journal, 2025)

Low-surface-energy polyfluorinated acceptors enable cascaded donor/acceptor distribution in ternary organic solar cells - Zhe Hao; Siyuan Li; Zhilong He; Ming Xia; Rongbin Zhang; Xuelin Wang; Zheng Tang; Hongliang Zhong (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

[3 + 2 + 1] iridium(III) complexes for high-efficiency saturated red organic light-emitting diodes - Ping Chen; Qingwu Wu; Gui-Yan Yang; Qifei Xie; Sheng Yu; Ming-Yu Teng; Huabo Han; Guo-Li Huang; You-Xuan Zheng; Guangzhao Lu (Chemical Engineering Journal, 2025)

The study of microscopic damage in moraine soils under freeze-thaw cycles based on discrete element - Li Mingli; Liu Jianuo; Jiang Yuanjun; Chang Ming; Zheng Haijun; Tian Hongling; Huang Shibo (Bulletin of Engineering Geology and the Environment, 2025)

Distribution, partitioning behaviors, and source identification of legacy and emerging per- and polyfluorinated alkyl substances in the Pearl River Estuary, South China - Bin Tang; Can Peng; Dong-Jing Zhou; Kai-Yi Wu; Fei Tian; Hai-Gang Chen; Shi-Yi Zhang; Bo-Wen Li; Guo-Cheng Hu; Ming-Zhong Ren; Jing Zheng (Water Research, 2025)

Efficacy of a non-recombinant NADC34-like PRRSV-2 vaccine candidate against a recombinant NADC34-like PRRSV-2 isolate - Ming Qiu; Shuai Li; Meng Cui; Shuai Yang; Xiaoyang Zhu; Yifan Meng; Yanhan Lin; Hong Lin; Zhe Sun; Yuan Wang; Sen Jiang; Wanglong Zheng; et al. (Veterinary Microbiology, 2025)

Differential evolution algorithm with local and global parameter adaptation - Xiao Lin Jin; Sheng Xin Zhang; Li Ming Zheng; Shao Yong Zheng (Swarm and Evolutionary Computation, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Study on mechanism of in-situ hydrogen generation based on molecular dynamics simulation from pyrolysis of heavy oil - Houfeng He; Yuning Gong; Mingguo Peng; Haoran Zheng; Tian Feng; Ming Zhang; Qiu Li; Pengcheng Liu (Fuel, 2025)

IL-4/13A1 promotes the proliferation of IgT+ B cells while enhancing their apoptosis in tilapia - Yating Zhu; Haokai Chen; Yuying Zheng; Jiansong Zhang; Ming Geng; Zhichao Fang; Kang Li; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2025)

Effect of MnFe2O4 loading on photocatalytic performance of BiVO4 for levofloxacin degradation with or without peroxydisulfate - Meng Tang; Liduan Zhang; Lijia Zheng; Ming Li; Ming Ge (Environmental Research, 2025)

Heat conduction and fracture mechanism of jointed granite: Insight from a fully coupled Thermo-Mechanical DEM model - Jian Ma; Zheng-Wei Li; Hai-Xi Wang; Jia-Qi Song; Ming-Yu Zhang (Computers and Geotechnics, 2025)

Polyacrylic acid promotes anti-passivation and electron-donation of boronized nanoscale zero-valent iron during groundwater remediation - Zelong Zheng; Lihang Ma; Xiaobin Liao; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Chemical Engineering Journal, 2025)

Selectively passivated core-satellite cobalt-iron bimetallic phosphide with optimized ⁎OH adsorption for boosting oxygen evolution reaction - Baoshan Liu; Wangshu Zheng; Zhaoxi Zhang; Jiarui Yang; Yanqi Yuan; Feng Li; Jing Liu; Liping Zhao; Ming Wen; Han Chen; Peng Zhang; Lian Gao (Chemical Engineering Journal, 2025)

Tailoring key intermediates and interfacial water at Ag92Ru8 aerogel toward sustainable ammonia synthesis from nitrate - Junjie Chen; Xiaomei Xing; Sisi Wen; Mengyuan Li; Di Liu; Wenji Jiang; Xinyi Shao; Ruikai Qi; Yumei Yang; Ming Mu; Zheng-jie Chen; Bing Zhao; et al. (Chemical Engineering Journal, 2025)

Defect-rich carbon nanofiber membranes as metal-free catalysts for flow-through peroxymonosulfate activation: toward efficient antibiotic removal and water remediation - Jiaqiang Wang; Linghui Li; Xiaoben Yang; Qianglin Li; Ling Wu; Binghua Zhou; Zhipeng Wang; Zheng-Hong Huang; Ming-Xi Wang (Chemical Engineering Journal, 2025)

Regulation of retrogradation and textural properties of mung bean starch gels during storage: Role of cooling rate - Zheng Zou; Ming Li; Qiaozhi Song; Boli Guo; Guoyan Zhou; Fengwei Xie (Carbohydrate Polymers, 2025)

Research on seismic resilience evaluation method of RC frame structures - Yong-Ming Li; Shan-Suo Zheng; Li-Guo Dong; Song Yang (Bulletin of Earthquake Engineering, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

Weaving through time: Stocks and flows of textile fibers in China (1978–2022) - Zheng Zhou; Yuheng Cao; Zhuolun Du; Meng Jiang; Yucheng Ren; Chunlong Li; Hengzhi Zhu; Dingjiang Chen; Yadong Yu; Ming Xu; Baohua Guo; Yong He; et al. (Resources, Conservation and Recycling, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Soil mesofauna bacterial diversity: Insights from cultured collembolans, enchytraeids, and mites species - Bo-Wen Liu; Jing Wen; Shuai-Fei Ye; Jia-Jia Gu; Ming-Xin Li; Xiao-Bo Xiong; Zong-Zheng Liang; Hong-Tao Wang (Food Webs, 2025)

Investigation on quality discrepancies of Soy Sauce Aroma Baijiu: Flavor chemical characteristics in single-source and cross-source samples - Chen Li; Xiao-Juan Zhang; Shi-Yi Wang; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Bo Yang; Cai-Hong Shen; Zheng-Hong Xu (Food Control, 2025)

The effect of ligand regulation on mechanism of alkaline oxygen evolution reaction under industrial scale - Xin-Ru Li; Xue-Jun Zhai; Hao-Zheng Liu; Xin Wen; Yanbin Qi; Chen Zhang; Guodong Li; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2025)

Wave parameter analysis of landslide-tsunamis - Ming Peng; Qingxin Zhao; Yan Zhu; Shuang Li; Hongchao Zheng; Shaoqiang Meng (Natural Hazards, 2025)

Cucurbitacin B alleviates DSS-induced experimental colitis by targeting ZNF70 to suppress the NLRP3/STAT3 signaling axis - Shen Cao; Yuhan Wang; Yi Tai; Jing Han; Yanjin Zheng; Can Wang; Hong Xiang Zuo; Ming Yue Li; Yue Xing; Xuejun Jin; Juan Ma (Inflammopharmacology, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Development and application of IgT monoclonal antibody in Nile tilapia Oreochromis niloticus - Haokai Chen; Yating Zhu; Kang Li; Yuying Zheng; Ming Geng; Zhichao Fang; Jiansong Zhang; Yi Cao; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2025)

Dual-functional tight ultrafiltration membrane constructed from aminoquinone networks for sufficient dye/salt selectivity and bacterial inactivation - Riri Liu; Hanna Vanermen; Jiale Du; Qin Chen; Zijian Yu; Junwei Li; Pengrui Jin; Junfeng Zheng; Alexander Volodin; Wenyuan Ye; Raf Dewil; Ming Xie; et al. (Desalination, 2025)

The combination of linkage mapping, genome-wide association study, and dynamic transcriptome analysis reveals conserved candidate genes for salt tolerance in maize - Ziyi Xiao; Zhenyuan Pan; Xinxin Liu; Xueqing Zheng; Guantao Wang; Yayu Fu; Mengmeng Li; Bin Hou; Xuhua Li; Ming Zhang; Chunlan Jia; Fazhan Qiu (Theoretical and Applied Genetics, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

A Novel Large-Scale 3D Printing Apparatus for Complex Geological Models and Its Application - Shi-Ming Mei; Zheng-Wei Li; Ben-Guo He; Jia-Qi Song; Ming-Yu Zhang; Wei Zhang (Rock Mechanics and Rock Engineering, 2025)

Soil compaction reduces the yield potential of densely planted maize (Zea mays L.) by disrupting root and shoot growth coordination - Zhuohan Gao; Lu Liang; Xinbing Wang; Wenchao Zhen; Zaisong Ding; Congfeng Li; Zheng Liu; Ming Zhao; Zhigang Wang; Baoyuan Zhou (Plant and Soil, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Uncovering the coupling mechanisms among urban form, surface thermal environments and air pollution - Kaixin Wang; Jun Du; Chunlin Li; Ming Li; Cheng Chen; Zheng Wang; Jike Chen (Sustainable Cities and Society, 2025)

Construction of hierarchical nanostructured surface on an organic hybrid selenidostannate with light trapping effect to achieve sunlight-driven environmental remediation - Ji-Ming Yu; Longfei Zhai; Bing Zheng; Haohao Li; Chunhui Hou; Yimin Han; Juan Ma; Zihui Wang; Wei-Wei Xiong (Journal of Hazardous Materials, 2025)

Correction for calcium interference in the 40Ar/39Ar dating method - Wan-Feng Zhang; Jun-Jie Wang; De-Wen Zheng; Ming Xiao; Jia Zhang; Jun-Jie Li; Yu-Lian Zhang; Ying-De Jiang; Fei Su; Li Li; Yi-Gang Xu (Icarus, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Numerical prediction of premixed syngas/air explosion in a closed duct using a reduced combustion mechanism - Kai Zheng; Zhifeng Zhou; Qianhang Jia; Ming Peng; Song Lin; Yuyang Li (Fuel, 2025)

Establishment of mud crab (Scylla paramamosain) spermatogonial stem cell line: A potential tool for immunological research - Ying Song; Yanchuang Duan; Haiqing Luo; Linying Yun; Ming Zhang; Ngoc Tuan Tran; Huaiping Zheng; Qicun Zhou; Shengkang Li (Fish & Shellfish Immunology, 2025)

Synergistic coupling of bipolar membrane electrodialysis and Fenton process for sustainable management of landfill leachate reverse osmosis concentrate - Hao-Ran Yang; Changjiang Li; Chiqian Zhang; Xiaohong Lan; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng; Zhi-Hua Yuan (Chemical Engineering Journal, 2025)

Biochar alleviates nanoplastics and bisphenol A mediated immunological, neurological and gut microbial toxicity in channel catfish Ictalurus punctatus - Qingzhi Zheng; Yufeng Zheng; Muhammad Junaid; Ming Zeng; Hongping Liao; Ye Li; Yuanqi Zhao; Qian Huang; Jun Wang (Chemosphere, 2025)

Eucalyptus oil: A promising anticoccidial agent with multifaceted protective effects - Jun-jie Huang; Jie-yu Shi; Kai-yuan Li; He Zheng; Wen-hai Zhang; Xiao-bin Yi; Ming-jiang Liu; Ruo-nan Bo; Jin-gui Li (Veterinary Parasitology, 2025)

Chemical composition, antibacterial and antioxidant activities of Sanghuangporus baumii fermented cultures - Xiao-Dan Zheng; Meng-Jia Pu; Zi-Feng Guo; Ying Li; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Finite element modeling of clavicle fracture fixations: a systematic scoping review - Yi Zheng; Jing Li; Andy Yiu-Chau Tam; Timothy Tin-Yan Lee; Yinghu Peng; James Chung-Wai Cheung; Duo Wai-Chi Wong; Ming Ni (Medical & Biological Engineering & Computing, 2025)
Finite element analysis has become indispensable for biomechanical research on clavicle fractures. This review summarized evidence regarding configurations and applications of finite element analysis in clavicle fracture fixation. Seventeen articles involving 22 clavicles were synthesized from CINAHL, Embase, IEEE Xplore, PubMed, Scopus, and Web of Science databases. Most studies investigated midshaft transverse closed fractures by reconstructing intact models from CT scans and simulating fractures through gap creation. Common loading schemes included axial compression, distal torsion, and inferior bending. The primary objective was comparing different implant designs/placements on construct stiffness, von Mises stress, and fracture site micro-motion. Our review suggested a preference for plate fixation, particularly with anterior placement, for midshaft transverse fractures. However, limited fracture types studied constrain comprehensive recommendations. Additionally, the review highlighted discrepancies between finite element and clinical studies, emphasizing the need for improved modeling of physiological conditions. Future research should focus on developing a comprehensive database of finite element models to test various implant options and placements under common loading schemes, bridging the gap between biomechanical simulations and clinical outcomes. Graphical Abstract

YOLO-DAFS: A Composite-Enhanced Underwater Object Detection Algorithm - Shengfu Luo; Chao Dong; Guixin Dong; Rongmin Chen; Bing Zheng; Ming Xiang; Peng Zhang; Zhanwei Li (Journal of Marine Science and Engineering, 2025)
In computer vision applications, the primary task of object detection is to answer the following question: “What object is present and where is it located?”. However, underwater environments introduce challenges, such as poor lighting, high complexity, and diverse marine organism shapes, leading to missed detections or false positives in deep learning-based algorithms. To improve detection accuracy and robustness, this paper proposes an enhanced YOLOv11-based algorithm for underwater object detection that strengthens the ability to capture both local and global details and global contextual information in complex underwater environments. To better capture local and global features while integrating contextual information, the proposed method introduces several enhancements. The backbone incorporates a DualBottleneck module to enhance feature extraction, replacing the standard bottleneck structure in C3k, thus enhancing the feature extraction and the channel aggregation. The detection head adopts DyHead-GDC, integrating ghost depthwise separable convolution with DyHead for greater efficiency. Furthermore, the ADown module replaces conventional feature extraction and downsampling convolutions, reducing parameters and FLOPs by 14%. The C2PSF module, combining focal modulation and C2, strengthens local feature extraction and global context processing. Additionally, a SCSA module is inserted before the detection head to fully utilize multi-semantic information, improving the detection performance in complex underwater scenes. Experimental results confirm the effectiveness of these improvements. The model achieves 84.2% mAP50 on UTDAC2020, 84.4% on DUO and 86.7% on RUOD, surpassing the baseline by 2.5%, 1.6% and 1.2%, respectively. It remains lightweight, with 6.5 M parameters and a computational cost of 7.1 GFLOPs.

Salvianolic acid B protects against UVB-induced HaCaT cell senescence and skin aging through NRF2 activation and ROS scavenging - Jia-Ming Sun; Yu-Xin Liu; Yi-Tung Tsai; Yang-Dan Liu; Chia-Kang Ho; Dong-Sheng Wen; Ting-Yu Tsai; Dan-Ning Zheng; Ya Gao; Yi-Fan Zhang; Li Yu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Engineering a thermophilic Bacillus thermoamylovorans for degradation of polyethylene terephthalate waste - Yi-Mei Cai; Cui-Can Lu; Tian-Tian Wang; Li-Jun Song; Yu-Ming Deng; Han Xu; Sheng Chen; Wei Xia; Jing Wu; Zheng-Fei Yan (Journal of Cleaner Production, 2025)

Rational design of phospholipase D to enhance thermostability and catalytic activity for efficient biocatalytic phosphatidylserine synthesis - Peng Zhang; Xin-An Mao; Xiao-Li Kong; Jin-Song Gong; Zi-Kai Wang; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Chemistry, 2025)

Effects of calcium chloride and licorice flavonoids on Tan sheep myofibrillar protein oxidation and gelation: Synergistic impact of endogenous characteristic active substances - Jiangying Yu; Xinru Xie; Simiona Grasso; Chengpeng Cheng; Ming Zhu; Cheng Li; Xiaochun Zheng; Shaobo Li; Li Chen; Dequan Zhang (Food Chemistry, 2025)

Waste silk-derived photothermal aerogel for efficient interfacial solar desalination - Chao Liang; Yipeng Quan; Wenting Qian; Shuang Guo; Shengjie Zheng; Guangjie Zhang; Mingsong Fan; Jun Xiong; Ming Li (Chemical Engineering Journal, 2025)

Vertically oriented micron-thick perovskite film enables efficient and stable inverted perovskite solar cells - Bing-Hao Lv; Yong-Chun Ye; Jun-Gan Wang; Liu-Jiang Zhang; Yu-Hang Zhang; Ming-Li Zheng; Xian-Min Chen; Hui-Wei Du; Jie Yang; Xin-Yu Zhang; Meng-Lei Xu; Qiu-Feng Ye; et al. (Chemical Engineering Journal, 2025)

Redox state of NAD modulates the activation of Na-bicarbonate cotransporter NBCe1-B via IRBIT and L-IRBIT - Tianxiang Gui; Ying Liu; Mingfeng Fu; Han Wu; Pan Su; Xuhui Feng; Mengmeng Zheng; Zixuan Huang; Xudong Luo; Walter F. Boron; Li-Ming Chen (Science China Life Sciences, 2025)

Mechanism of hypoxia tolerance improvement in hybrid fish Hefang bream - Ming Wen; Chunchun Zhu; Yuhua Tang; Hong Zhang; Zheng Liu; Siyu Wang; Min Tao; Li Hu; Wenting Rao; Shengnan Li; Dingbing Gong; Shi Wang; et al. (Aquaculture, 2025)

Promotion of symbiotic interaction between phagotrophic protists and beneficial bacteria, mediated via a balancing of soil nutrients, reduces the incidence of watermelon Fusarium wilt - Yaoyao TONG; Li WANG; Chuanfa WU; Haoqing ZHANG; Yangwu DENG; Ming CHEN; Xianqing ZHENG; Weiguang LÜ; Jianping CHEN; Tida GE (Pedosphere, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Mapping the Research Landscape: A Comprehensive Bibliometric Review of Global Warming and Human Health - Qingyong Zheng; Jianguo Xu; Ming Liu; Kexin Ji; Yu Zhang; Songlin Wu; Tengfei Li; Kaisen Yuan; Zhichao Ma; Zijian Ma; Jinhui Tian; Jiang Li (International Journal of Climatology, 2025)
Human health is increasingly threatened by global warming, necessitating a thorough understanding of research progress in this critical area to inform future studies. The data were analysed using Microsoft Excel 2021, and visualisations were created with GraphPad, VOSviewer and R‐Studio (Bibliometrix). These tools were used to generate graphs and network visualisations illustrating author and country collaborations, journal article distributions, hotspot clustering and future trend predictions. Our analysis revealed a substantial increase in publications in recent years, with intensified research and collaboration observed across Asia, Europe, North America and Oceania, particularly in the United States. Various high‐impact journals have made meaningful contributions to raising awareness in this field, emphasises the multifaceted impacts of global warming on public health and societal activities, while also exploring adaptive measures being implemented in response to these changes. As the world continues to grapple with the global pandemic, further research is likely to spotlight related issues, with heightened interest anticipated. The evidence of global warming's impact on human health is becoming increasingly evident, underscoring the need for global cooperation to mitigate its effects and promote public health. This study provides a foundation for researchers and policymakers, highlighting the significance of addressing global warming's implications for human well‐being. By fostering international collaboration, we can collectively strive toward sustainable strategies to combat global warming and safeguard public health.

Vector Form Intrinsic Finite Element Method for Dynamic Response Analysis of Deep-Sea Mining Hose - Jingchang Xu; Xiaoyan Li; Hao Zheng; Honghao Yan; Ming Zhang; Bingkun Wang (Journal of Marine Science and Engineering, 2025)
The deep-sea mining hose is a crucial component of the underwater lifting and transport system utilized in deep-sea mining operations. The marine environmental loading and the dynamic coupling between the hose, the subsea mining vehicle, and the relay bin have a complex effect on the mechanical properties of the hose. This study employs the vector form intrinsic finite element method to develop a MATLAB-based three-dimensional dynamic response simulation program for analyzing the hose’s dynamic response characteristics under varying current velocities, buoyancy module quantities, relay bin resonance conditions, and mining vehicle motions with double-hose systems, etc. The findings demonstrate that the vector form intrinsic finite element method effectively simulates the dynamic behavior of the hose structure. It is necessary to analyze the dynamic response of the hose’s multiple factors.

Experimental study on the supernormal mechanical properties and antiknock properties of NPR steel - Yong Li; Wei Ming; Zhigang Tao; Jing Zheng; Manchao He (Tunnelling and Underground Space Technology, 2025)

Aeration strategies for microalgae in wastewater treatment: Enhancing pollutant removal and community dynamics - Pan Li; Yajun Luo; Fei Ming; Jingxian Zheng; Zhicheng Pan; Rui Wang; Yanqing He; Miao Zhou; Xin Xiong; Chi Zhang; Yu Lei; Zhaoqi Wang; et al. (Journal of Environmental Management, 2025)

The tungsten tailings remediation by soilless plant establishment: Varied aggregation structure, heavy metal mobilization, and microbial community structure - Xiaojun Zheng; Ziqin Wang; Qi Li; Liliang Liu; Ming Chen (Ecological Engineering, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Strategic regulation of crystallization kinetics to achieve efficient pure-red quasi-2D perovskite light-emitting diodes - Yunhui Kuang; Yazhuo Xue; Zheng Zhang; Lvpeng Yang; Tong Bie; Rui Li; Wenxi Liang; Naigen Zhou; Ming Shao (Chemical Engineering Journal, 2025)

Research on Support Control of New Materials and Structures for Deep Buried Complex Soft Rock Tunnel with Large Deformation - Yong Li; Jing Zheng; Chuang Xu; Manchao He; Fengnian Wang; Zhigang Tao; Wei Ming (Rock Mechanics and Rock Engineering, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Ca2+-SpVAMP2 pathway promotes exosome secretion to resist the infection of Vibrio parahaemolyticus in mud crab (Scylla paramamosain) - Yifan Lei; Ming Zhang; Kangyue Huang; Qian Sun; Jinkun Li; Huifen Liang; Yuqing Zheng; Ngoc Tuan Tran; Xiuli Chen; Yanqiu Zhang; Yueling Zhang; Shengkang Li (Aquaculture, 2025)

Regulation roles of dre-miR-187 in neurological damage by low concentration toluene in zebrafish - Shu-Hui Men; Jia-Yun Xu; Zhen-Guang Yan; Jin-Zhe Du; Ming-Rui Li; Zi-Ye Wang; Chen Liu; Xin Zheng (Journal of Cleaner Production, 2025)

Dynamic thermal and mass transport in PEM fuel cells at elevated temperatures and pressures: A 3D model study - Qianqian Wang; Jixuan Lu; Weibo Zheng; Bing Li; Jim P. Zheng; Guomin Cui; Liang Hao; Pingwen Ming (Fuel, 2025)

Self-assembled preparation of wheat germ gliadin and (−)-epigallo-catechin 3-gallate nanoparticles: Structural characterization, formation mechanism and bioactivity - Zhi-Tong Zhu; Zhi-Rui Ding; Yu-Qing Liu; Ying Zhang; Jian-Zheng Li; Si-Yi Han; Xian-Ming Liu; Ming Hui; Na Liu; Ai-Mei Liao (Food Bioscience, 2025)

Enhancement of the yield of poly (ethylene terephthalate) hydrolase production using cell membrane protection strategy - Xiao-Qian Chen; De-Ming Rao; Xing-Yu Zhou; Yang Li; Xiao-min Zhao; De-min Kong; Han Xu; Chu-Qi Feng; Lei Wang; Ling-Qia Su; Zheng-Fei Yan; Jing Wu (Bioresource Technology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Projected waste and recycling potential of China’s photovoltaic industry - Bingchun Liu; Ming Li; Jiali Chen; Zheng Sun (Waste Management, 2025)

Enhanced removal of sulfonamide antibiotics in water using high-performance S-nZVI/BC derived from rice straw - Xiao-Ming Zou; Tiao Zhang; Yu-Hua Dong; Cui Hu; Li Yin; Yu-Ling Zheng; Mi Li; Xiao-Yu Xiao; Wei Hui (Journal of Environmental Management, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Development of a platform strain for integration expression of phospholipase D and its application in improving phosphatidylserine content of egg yolk - Peng Zhang; Xiao-Li Kong; Jin-Song Gong; Zhi-Yuan Yao; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Bioscience, 2025)

Exploring the immunomodulatory mechanisms of Osmunda japonica Thunb polysaccharides: Activation of MAPK and NF-κB signaling pathways - Xiaochen Liu; Rui Xu; Yuting Miao; Yining Zang; Yuxin Huang; Yuying Zheng; Fengwei Li; Ming Wei; Rui Xiao; Xiaohong Yu (Food Bioscience, 2025)

A bioprosthetic heart valve modified by HUVEC-exosomes with improved biocompatibility, endothelialization and anticalcification properties - Shufen Li; Jingruo Chen; Xiaoting Chen; Ming Chen; Zheng Chai; Weihua Zhuang; Mao Chen (Chemical Engineering Journal, 2025)

Integrative transcriptomics and metabolomics analysis provide insight into the formation of skin pigmentation diversity in Chinese soft-shelled turtle (Pelodiscus sinensis) - Ming Qi; Wei Liu; Wei Li; Guangmei Chen; Wenrui Shi; Gaohua Yao; Yijiang Bei; Fan Yuan; Qinghui Meng; Fan Zhou; Wenjun Ma; Xueyan Ding; et al. (Aquaculture, 2024)

Enhanced degradation of polyethylene terephthalate (PET) microplastics by an engineered Stenotrophomonas pavanii in the presence of biofilm - Qing-Song Huang; Si-Qi Chen; Xiao-Min Zhao; Li-Jun Song; Yu-Ming Deng; Ke-Wei Xu; Zheng-Fei Yan; Jing Wu (Science of The Total Environment, 2024)

Occurrence, fate, and ecological risk of PAEs, PFASs, antibiotics in industrial, urban and rural WWTPs in Shaanxi Province, China - Jianchao Liu; Chengying Zhang; Yu Zheng; En Hu; Ming Li (Journal of Water Process Engineering, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Mode of action underlying toxicity of Camptothecin to Spodoptera frugiperda (Lepidoptera) larvae - Jun-li Lv; Wen-qing Lai; Lei Pang; Xiao-ying Zhang; Kai-yi Zheng; Qiang Zhang; Zhan-peng Lu; Zhi-sheng Wang; Fasihul Lisan; Xue-yang Wang; Lu-feng Hu; Ming-jie Deng (Journal of Asia-Pacific Entomology, 2024)

Seasonality shapes the microbiota and metabolome of strong-flavor Baijiu during fermentation and affects its flavor characteristics - Li-Juan Chai; Jing-Yi Zhang; Tao Gao; Long-Yun Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Jin-Song Shi; Xiang Chen; Zheng-Hong Xu (Food Bioscience, 2024)

Multiple strategies from apparatus to synthetic process toward high-performance spherical manganese hexacyanoferrate for sodium-ion batteries - Jun Zheng; Gang Wang; Kai Zhang; Jiafan Zheng; Wenwu Fu; Chengyu Zhang; Jiayi Liu; Jieyuan Wang; Junwei Li; Fu Cai; Wenbo Huang; Ming Zhang; et al. (Chemical Engineering Journal, 2024)

Heterojunction interface engineering enabling high transmittance and record efficiency in Sb2S3 semitransparent solar cell - Muhammad Ishaq; Xuerui Li; Safdar Mehmood; Yi-Ming Zhong; Adil Mansoor; Usman Ali Shah; Shuo Chen; Yuexing Chen; Zhuanghao Zheng; Guangxing Liang (Chemical Engineering Journal, 2024)

High-level extracellular expression of phospholipase D by combinatorial fine-tuning strategy in Bacillus subtilis for efficient biosynthesis of phosphatidic acid - Peng Zhang; Xin-An Mao; Jin-Song Gong; Xiao-Li Kong; Chang Su; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2024)

A Protocol for Body MRI/CT and Extraction of Imaging-Derived Phenotypes (IDPs) from the China Phenobank Project - Chengyan Wang; Shuo Wang; Sha Hua; Ruokun Li; Yan Li; Zhang Shi; Kai Feng; Lizhen Lan; Meng Liu; Xutong Kuang; Xueqin Xia; Shihai Zhao; et al. (Phenomics, 2024)

A medicine and food homology formula prevents cognitive deficits by inhibiting neuroinflammation and oxidative stress via activating AEA–Trpv1–Nrf2 pathway - Ming-Jie Li; Jing-Yi Xu; Hua-Yue Zhang; Min Guo; Meng-Ning Lan; Jie Kong; Shi-Wei Liu; Hua-Jun Zheng (Inflammopharmacology, 2024)

Response strategies of leaf vein traits and stomatal traits of Aegiceras corniculatum to shrimp aquaculture wastewater discharge - Ying-Ying Qin; Ge-Ge Zhu; Ming-Zhong Liang; Hai-Lei Zheng; Jun-Wei Li (Aquatic Ecology, 2024)

Numerical simulation of two-dimensional magnetotelluric forward modeling of Heifangtai loess landslide in Gansu, China - Bin Li; Qiang Xu; Sui-wang Ji; Qiang Cheng; Tian-Xiang Liu; Hu Zhao; Ming-gao Tang; Guang Zheng (Applied Geophysics, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Synergistic management of nitrogen contamination in overflow wastewater and algal proliferation in lake receiving wastewater based on electrochemical oxidation process - Ya-Ning Wang; Ding Li; Lin Liu; Jia-Fang Xie; Zhi-Tang Lyu; Quan-Bao Zhao; Yu-Ming Zheng (Process Safety and Environmental Protection, 2024)

Differential spatial responses and assembly mechanisms of soil microbial communities across region-scale Taiga ecosystems - Zheng-Xiao Liu; Yue-Ming Lyu; Yang Liu; Yun-Qi Wang; Ming-Min Xiong; Yuan Tang; Xing-Yue Li; Han Sun; Ji-Liang Xu (Journal of Environmental Management, 2024)

Central Tibetan adakitic rocks archive the critical impact of water on the Nb/Ta variation in deep crustal melts - Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Xi-Jun Liu; Ming-Jian Li; Qiang-Tai Huang; Zheng-Lin Li (Geochimica et Cosmochimica Acta, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Simulation-based study of local hydrogen crossover dynamics and their effects on proton exchange membrane fuel cells - Qianqian Wang; Weibo Zheng; Bing Li; Jim P. Zheng; Guomin Cui; Liang Hao; Pingwen Ming (Chemical Engineering Journal, 2024)

Self-flocculating Spirulina platensis CMB-02 to efficiently treat ammonia nitrogen of rare earth elements wastewater - Dandan Che; Yulin Lai; Ziqi Weng; Ming Li; Guanglu Huang; Mingmin Zheng; Mingzi Wang (Bioresource Technology, 2024)

Placental ischemia-upregulated angiotensin II type 1 receptor in hypothalamic paraventricular nucleus contributes to hypertension in rat - Abdoulaye Issotina Zibrila; Jun Zhou; Xiaomin Wang; Ming Zeng; Md. Ahasan Ali; Xiaoxu Liu; Asma A. Alkuhali; Zhaoshu Zeng; Yuan Meng; Zheng Wang; Xuelan Li; Jinjun Liu (Pflügers Archiv - European Journal of Physiology, 2024)

Anti-adipogenesis and anti-obesity potential of alliin mediated by modulating glycolipid metabolism via activating PPARγ signaling - Ming-Yan Yang; Yu-Jing Liu; Mei-Hua Zheng; Tao Pan; Zhen-Yuan Li; Bai-Fang Gong; Hua-Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Experimental Study on Temperature Variation in Saturated Warm Frozen Soil Under Dynamic Triaxial Conditions - Hongchun Li; Hu Zhang; Suiqiao Yang; Bo Zheng; Zheng Li; Jintao Hu; Ming Lu (Geotechnical and Geological Engineering, 2024)

Attenuation of phenylnaphthenic acids related to oil sands process water using solar activated calcium peroxide: Influence of experimental factors, mechanistic modeling, and toxicity evaluation - Ming Zheng; Isaac Sánchez-Montes; Jia Li; Xiaodi Duan; Bin Xu; Mohamed Gamal El-Din (Water Research, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Abundant small microplastics hidden in water columns of the Yellow Sea and East China Sea: Distribution, transportation and potential risk - Jia Lin; Jia-Yuan Zheng; Zhi-Geng Zhan; Yuan-Ming Zhao; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

The construction of yeast β-glucan coated-edible dock protein nanomicelles for the encapsulation and sustained release of apigenin - Qian Zhou; Xiao-Jie Wang; Yu-Ru Wu; Weinan Zhang; Jing Li; Wei Wang; Ying-Nan Liu; Zhen-Yu Yu; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Journal of Food Engineering, 2024)

Cu inanchored MnO/carbonaceous frameworks trigger peroxymonosulfate activation for enrofloxacin degradation: ROS generation and pollutant attacking processes - Huai-Yuan Niu; Zheng-Tao Dong; Hai Guo; Ya-Ya Yang; Wen-Jie Yang; Ming Yan; Cheng-Gang Niu; Ji-Shan Li (Journal of Environmental Chemical Engineering, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Comparative genomics of Clostridium tyrobutyricum reveals signatures of environment-specific adaptation and metabolic potentials - Guan-Yu Fang; Li-Juan Chai; Zhen-Ming Lu; Xiao-Juan Zhang; Hong-Yu Xu; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

Granzyme B secreted by T cells is involved in anti-bacterial immune response of tilapia - Yi Cao; Jiansong Zhang; Ding Wang; Yuying Zheng; Jie Cheng; Ming Geng; Kang Li; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2024)

A self-floating and windproof Janus biomass composite hydrogel with magnetic controllability and salt rejection for polluted seawater desalination - Dingqiang Zheng; Lei Shi; Ming Zhang; Weixing Huang; Zhenghui Li; Shoufu Long; Dongsheng Song (Chemical Engineering Journal, 2024)

Chloride homeostasis via enhanced salt ion secretion selectivity contributes to salt tolerance of recretohalophytic mangrove Avicennia marina - Qian-Su Ding; Chao-Qun Xu; Dong-Na Ma; Ming-Yue Wei; Chang-Hao Gao; Shan Zhang; Huan Li; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2024)

Use of consumer insights to inform behavior change interventions aimed at illegal pet turtle trade in China - Wuji Zheng; Anita Kar Yan Wan; Zhan Chen; Alexander Clark; Caitlin Court; Yuanlu Gu; Toby Park; Jake Reynolds; Xiaoxi Zhang; Lishu Li; Tien Ming Lee (Conservation Biology, 2024)
Illegal poaching and overexploitation for the international pet trade are among the greatest threats to freshwater turtles in Southeast Asia. Expanding consumer research in China is crucial to filling knowledge gaps about the scale and structure of illegal trade and developing audience‐targeted and relevant interventions that may reduce demand for illegal turtles as pets. We applied mixed methods to provide a detailed understanding of the consumer side of the illegal pet turtle trade in China. We conducted 30 interviews with key stakeholders and online surveys ( n = 2456) of turtle keepers via community forums. From these, we identified 3 core consumer groups based on their prior turtle‐keeping experience, species exposure, and potential for future purchases. We conducted a thematic qualitative analysis of concepts related to the capability, opportunity, motivation, and behavior (COM‐B) model to determine the factors influencing the illegal pet turtle trade and to identify barriers to illegal purchases. Specifically, we identified purchasers’ capabilities, opportunities, and motivations in the context of legality, enforcement risk, captive breeding, and impacts on wild population. We developed consumer journey maps (i.e., visual representations of customer's experiences throughout their buying journey) for core consumer groups. These maps illustrate the sequential behaviors and processes that consumers undertake when purchasing turtles, from initial exposure to sourcing, keeping, and providing a new home. Key factors influencing illegal purchases included convenient purchase channels, misguided cognition and motivations for pet keeping, and weak law enforcement. Effective interventions included messages focusing on shifting cognition and beliefs, increasing legal risk perception, and emphasizing stringent law enforcement, primarily delivered through online channels. Our results underscore the necessity for adaptable, audience‐tailored interventions to reduce consumer demand for illegal wildlife products. The mixed‐methods approach, combining quantitative and qualitative data, provided a comprehensive understanding of the target behavior and can inform the development of effective intervention strategies.

Value-added utilization of hemoglobin and its hydrolysis products from livestock and poultry blood processing by-products: A review - Chengpeng Cheng; Li Chen; Dequan Zhang; Jiangying Yu; Ming Zhu; Cheng Li; Xiaochun Zheng; Christophe Blecker; Shaobo Li (Trends in Food Science & Technology, 2024)

Nitrogen cycling in China marginal seas: Progress and challenges - Siqi Wu; Xiuli Yan; Jin-Ming Tang; Ehui Tan; Li Luo; Senwei Tong; Zhen-Zhen Zheng; Yifeng Huang; Min Nina Xu; Shuh-Ji Kao (Marine Chemistry, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Enhancement of chlorine-resistant bacteria inactivation via coupling Magnéli phase Ti4O7-based electrochemical oxidation and chlorination - Sheng-Nan Li; Shu-Xian Zheng; Zi-Xuan Zheng; Yu Ling; Hai-Ming Wu; Hai Liu (Chemical Engineering Journal, 2024)

Triggering Receptor Expressed on Myeloid Cells 2 Alleviated Sevoflurane-Induced Developmental Neurotoxicity via Microglial Pruning of Dendritic Spines in the CA1 Region of the Hippocampus - Li Deng; Shao-Yong Song; Wei-Ming Zhao; Xiao-Wen Meng; Hong Liu; Qing Zheng; Ke Peng; Fu-Hai Ji (Neuroscience Bulletin, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

In vivo manufacture and manipulation of CAR-T cells for better druggability - Rui Hou; Xiaoxue Zhang; Xu Wang; Xuan Zhao; Sijin Li; Zhangchun Guan; Jiang Cao; Dan Liu; Junnian Zheng; Ming Shi (Cancer and Metastasis Reviews, 2024)

Signal Transduction Associated with Mn-induced Neurological Dysfunction - Xiao-wei Zheng; Yuan-yuan Fang; Jun-jie Lin; Jing-jing Luo; Shao-jun Li; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Investigation of high-risk antibiotic resistance bacteria and their associated antibiotic resistance genes in different agricultural soils with biogas slurry from China - Yi Lu; Junhui Wu; Jiwei Li; Zailin Du; Changai Zhang; Yanjun Chai; Zewen Jin; Zichuan Li; Jun Meng; Haifeng Zhuang; Lifeng Ping; Ming Hung Wong; et al. (Journal of Hazardous Materials, 2024)

Interaction and selective treatment of lead-zinc flotation wastewater for wastewater recycling using ectrocatalytic internal micro-electrolysis - Hongyan Ma; Chen Jiang; Xuan Zhu; Xin Zheng; Wenyi Zhou; Lirong Wang; Ming Zhao; Linhui Feng; Xiaojun Xu; Ciming Kong; Tianguo Li (Journal of Cleaner Production, 2024)

The TAK1/JNK axis participates in adaptive immunity by promoting lymphocyte activation in Nile tilapia - Ding Wang; Yuying Zheng; Jiansong Zhang; Yi Cao; Jie Cheng; Ming Geng; Kang Li; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2024)

Elevational distribution of forests and its spatiotemporal dynamics in subtropical China from 2000 to 2019 - Zhencan Zheng; Liuwen Zhuang; Guofang Miao; Han Liu; Zhiqiang Cheng; Wenyu Li; Rong Shang; Peng Gong; Jing Ming Chen (Science China Earth Sciences, 2024)

Biochar produced from diverse invasive species improves remediation of cadmium-contaminated soils - Xue Wang; Wei-Long Zheng; Hao-Ming Yuan; Mark van Kleunen; Fei-Hai Yu; Mai-He Li (Biological Invasions, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Highly salt-resistant polypyrrole decorated waste mop sponge solar evaporator for efficient desalination - Zhihui Yang; Chenxi Han; Yue Zheng; Yibing Chen; Weiming Wang; Xue Min; Jun Xiong; Ming Li (Desalination, 2024)

Integrated assessment of trace elements in a marine ranching area based on multi-species and multi-level biomarkers: a case study in China’s national-level marine ranching demonstration area - Mingzhu Li; Zhixu Chen; Ming Li; Jiugang Zhang; Bingqing Xu; Yanyan Yang; Xiangfei Li; Linlin Fan; Baojun Liu; Tao Zheng; Yan Fang; Fan Li (Frontiers in Marine Science, 2024)
The goal of this study was to evaluate the trace element pollution in a marine ranching area in China based on molecular responses (expression of metallothionein and antioxidant enzyme genes), and biochemical biomarkers (metallothionein content, antioxidant enzyme activities, and malonaldehyde level) in four indicator species. We collected samples of two fish ( Lateolabrax maculatus and Sebastes schlegelii ), one crustacean ( Charybdis japonica ), and one gastropod ( Rapana venosa ) from the western Furong Island marine ranching area and from an adjacent area in March 2022 and measured the trace element content in these indicator species as well as in the seawater and sediment. We found that the bioaccumulation characteristics of trace elements and the response patterns of biomarkers were species specific. Moreover, not every biomarker was significantly correlated with environmental trace element content. We then established two biomarker combinations indicative of trace element pollution in seawater and sediment, respectively, based on the correlation between biomarkers and trace element contents. The selected biomarkers were integrated using integrated biomarker response version 2 (IBRv2). IBRv2 values in the studied marine ranching area were lower than those in the adjacent area. Additionally, these values were consistent with the bioaccumulation of trace elements in the indicator species, the integrated trace element pollution index for seawater, and the potential risk index for sediment. These results show that this multi-biomarker and multi-species IBRv2 approach provided a comprehensive diagnosis of trace element pollution in the marine ranching area. Therefore, its application may be beneficial for marine environmental monitoring and management in view of the ecotoxicological impact of pollutants on organisms.

Metabolites assay offers potential solution to improve the rooster semen cryopreservation - Xue Du; Yuanning Zhang; Duoxi Li; Jie Han; Yali Liu; Lijuan Bai; Tao Huang; Ming Cui; Panlin Wang; Xianzhong Zheng; Ayong Zhao (Theriogenology, 2024)

Differential evolution with collective ensemble learning - Sheng Xin Zhang; Yu Hong Liu; Li Ming Zheng; Shao Yong Zheng (Swarm and Evolutionary Computation, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Using temporal dominance of sensations (TDS), multiple-sip TDS, chemical composition evaluation, and microstructural analysis to assess the impact of repeated reheating cycles on chicken soup - Mingcheng Zhang; Ming Li; Jiali Li; Huikun Chai; Kaixian Zhu; Qiyuan Ni; Duoduo Zheng; Wensheng Yao; Dengyong Liu (Food Chemistry, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

Chemical constitutents and chemotaxonomic research of the deep-sea-derived fungus Talaromyces minioluteus W19 - Kai Zhang; Yuan Wang; Teng Long; Ya-Ping Xie; Zheng-Biao Zou; Yong Zhang; You Li; Ming-Min Xie; Guang-Ming Liu; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Chemical constituents and chemotaxonomic research of the deep-sea-derived fungus Aspergillus japonicus W6 - Tong Yu; Rong Chao; Zheng-Biao Zou; Jia-Xin Duan; Kai Zhang; You Li; Ming-Min Xie; Yong Zhang; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Ferroptosis: a critical mechanism of N6-methyladenosine modification involved in carcinogenesis and tumor progression - Qingqing Wei; Changning Xue; Mengna Li; Jianxia Wei; Lemei Zheng; Shipeng Chen; Yumei Duan; Hongyu Deng; Faqing Tang; Wei Xiong; Ming Zhou (Science China Life Sciences, 2024)

Streptomyces camelliae sp. nov., isolated from rhizosphere soil of Camellia oleifera Abel - Zheng Yaxi; Deng Aihua; Xu Xiaoxiao; Li Chenxi; Peng Yi; Tang Ting; Liu Jin; Ming Yiru; Mo Ping (Archives of Microbiology, 2024)

Alkaloids from the stems of Fissistigma maclurei Merr. inhibit the proliferation of synoviocytes - Mu-Tao Liang; Xiao-Zheng Zhang; Zi-Hao Chen; Chuan-Shan Fu; Duo-Jiang Li; Guo-Ze Chen; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

Rapidly count crop seedling emergence based on waveform Method(WM) using drone imagery at the early stage - Jie Yuan; Xu Li; Meng Zhou; Hengbiao Zheng; Zhitao Liu; Yang Liu; Ming Wen; Tao Cheng; Weixing Cao; Yan Zhu; Xia Yao (Computers and Electronics in Agriculture, 2024)

IFITM1 and IFITM2 inhibit the replication of senecavirus A by positive feedback with RIG-I signaling pathway - Huizi Li; Ming Chen; Tingting Zheng; Xiaoling Lei; Cunhao Lin; Shuo Li; Jiacong Mo; Zhangyong Ning (Veterinary Microbiology, 2024)

Regional variations in management and outcomes of patients with acute coronary syndrome in China: Evidence from the National Chest Pain Center Program - Shuduo Zhou; Yan Zhang; Xuejie Dong; Junxiong Ma; Na Li; Hong Shi; Sidney C. Smith; Yinzi Jin; Ming Xu; Dingcheng Xiang; Zhi-Jie Zheng; Yong Huo (Science Bulletin, 2024)

The ubiquitin-proteasome system in the plant response to abiotic stress: Potential role in crop resilience improvement - Jian Xu; Hongjie Liu; Chao Zhou; Jinxing Wang; Junqiang Wang; Yehui Han; Nan Zheng; Ming Zhang; Xiaoming Li (Plant Science, 2024)

Microplastics in remote coral reef environments of the Xisha Islands in the South China Sea: Source, accumulation and potential risk - Jia Lin; Yuan-Ming Zhao; Zhi-Geng Zhan; Jia-Yuan Zheng; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Multifunctional Spirulina-hybrid helical microswimmers: Imaging and photothermal efficacy enabled by intracellular gold deposition - Ziqiao Li; Yanan Che; Ming Chen; Jing Hu; Pan He; Xiang Sun; Xiaozhen Wu; Youliang Yao; Huili Zheng; Gang Liu; Xiaohui Yan (Chemical Engineering Journal, 2024)

Mechanical Responses of a Porous Red Sandstone to Quasi-Static Cyclic Loads Under Uniaxial Compression - Zhao-Qiang Zheng; Huai-Zhong Liu; Hong-Qiang Xie; Jiang-Da He; Ming-Li Xiao; Li Zhuo (Rock Mechanics and Rock Engineering, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Mapping multi-omics characteristics related to short-term PM2.5 trajectory and their impact on type 2 diabetes in middle-aged and elderly adults in Southern China - Jia-ting Wang; Wei Hu; Zhangzhi Xue; Xue Cai; Shi-yu Zhang; Fan-qin Li; Li-shan Lin; Hanzu Chen; Zelei Miao; Yue Xi; Tiannan Guo; Ju-Sheng Zheng; et al. (Journal of Hazardous Materials, 2024)

Gamma-ray irradiation as an effective method for mitigating antibiotic resistant bacteria and antibiotic resistance genes in aquatic environments - Ming-Qi Zhang; Xiao-Yong Zhang; Han-Chao Zhang; Hai-Bin Qiu; Zheng-Hao Li; Dong-Hua Xie; Li Yuan; Guo-Ping Sheng (Journal of Hazardous Materials, 2024)

Research on fracture propagation of hydraulic fracturing in a fractured shale reservoir using a novel CDEM-based coupled HM model - Bo Zhang; Tiankui Guo; Ming Chen; Jiwei Wang; Zhanqing Qu; Haiyang Wang; Heng Zheng; Wuguang Li (Computers and Geotechnics, 2024)

Controlled assembly of novel Fe2O3/MgFe2O4 nanotubular array structures for rapid detection of dibutylamine - Baosheng Li; Junchao Yang; Guanyi Zhang; Ming Zheng; Rui Li; Yubao Kan; Jiahui Li; Tingting Wang; Qibin Huang; Xianfa Zhang; Lihua Huo; Shan Gao; et al. (Chemical Engineering Journal, 2024)

Evolution of high-filling loess slope under long-term seasonal fluctuation of groundwater - Han Bao; Li Liu; Hengxing Lan; Jianbing Peng; Changgen Yan; Ming Tang; Guanmiao Guo; Han Zheng (CATENA, 2024)

Cruise observation of ambient volatile organic compounds over Hong Kong coastal water - Hao Sun; Dasa Gu; Xin Feng; Zhe Wang; Xiangyunong Cao; Mingyao Sun; Zhi Ning; Penggang Zheng; Yuchen Mai; Zijie Xu; Wai Ming Chan; Xin Li; et al. (Atmospheric Environment, 2024)

CD46 inhibits the replication of swine influenza viruses by promoting the production of type I IFNs in PK-15 cells - Huizi Li; Zhenzhen Sun; Tingting Zheng; Ming Chen; Xiaoling Lei; Xianglong Yu; Zhangyong Ning (Veterinary Research Communications, 2024)

Progress of 3-ketosteroid Δ1-dehydrogenases for steroid production - Bo Zhang; Deng-Feng Zhou; Meng-Juan Li; Jia-Hui Lan; Hui Li; Ming-Long Shao; Zhi-Qiang Liu; Yu-Guo Zheng (Systems Microbiology and Biomanufacturing, 2024)

EgMADS3 directly regulates EgLPAAT to mediate medium-chain fatty acids (MCFA) anabolism in the mesocarp of oil palm - Yaning Wang; Jinqi Yan; Ming Yang; Jixin Zou; Yusheng Zheng; Dongdong Li (Plant Cell Reports, 2024)

Identification of sex locus and a male-specific marker in blunt-snout bream (Megalobrama amblycephala) using a whole genome resequencing method - Ming Wen; Siyu Wang; Chunchun Zhu; Yuxin Zhang; Zheng Liu; Chang Wu; Shi Wang; Yude Wang; Li Ren; Min Tao; QinBo Qin; Chun Zhang; et al. (Aquaculture, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Spätzle maintains homeostasis of hemolymph microbiota in Scylla paramamosain through Toll2 - Zibo Wei; Ming Zhang; Yan Chen; Hang Hu; Xinshan Zhao; Yuqing Zheng; Ngoc Tuan Tran; Haipeng Feng; Chong Zeng; Shengkang Li (Fish & Shellfish Immunology, 2024)

A novel deep learning framework for landslide susceptibility assessment using improved deep belief networks with the intelligent optimization algorithm - Shaoqiang Meng; Zhenming Shi; Gang Li; Ming Peng; Liu Liu; Hongchao Zheng; Changshi Zhou (Computers and Geotechnics, 2024)

Accumulated Endogenous Abscisic Acid Contributes to the Cold Tolerance of Pre-planted Cultivated Tobacco - Qiansi Chen; Pingping Liu; Zefeng Li; Qingxia Zheng; Huina Zhou; Jinyan Liu; Peijian Cao; Ming Fang (Plant Molecular Biology Reporter, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Long-term effect of microplastics on anammox systems: From macro efficiency to micro metabolic mechanisms and antibiotic resistance genes proliferation - Jinli Zheng; Yaru Yang; Yutong Li; Xin Huang; Wenru Liu; Qi Zhang; Xiao-Ming Ji (Journal of Cleaner Production, 2024)

Dual strategy of ultrasound and doping enhance Mott Schottky heterojunction carrier exchange for efficient oxygen evolution - Yi-Wen Dong; Qian-Xi Lv; Bao-Hua Chen; Zheng-Yang Jin; Jing-Yi Xie; Fu-Li Wang; Chun-Ying Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

Community-level bioaugmentation results in enzymatic activity- and aroma-enhanced Daqu through altering microbial community structure and metabolic function - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

Leaching of heavy metals from tungsten mining tailings: A case study based on static and kinetic leaching tests - Xiaojun Zheng; Shiyue Qiu; Buchan Zhou; Qi Li; Ming Chen (Environmental Pollution, 2024)

Hydrogel coatings on universal medical devices with water-responsive Janus adhesion and acidity-triggered transformation for adaptive antibacterial treatment and fluorescence diagnosis - Yanyun Liu; Ming Li; Ying Zheng; Changhua Liu; Yang Cao; Wei Guo; Ming Liu; Jiaqi Qian; Chenchi Gong; Xueqin Shuang; Gaoxing Pan; Wei Huang; et al. (Chemical Engineering Journal, 2024)

On-microparticle construction of endothelialized liver microtissues for drug testing - Zengnan Wu; Yajing Zheng; Jin-Ming Lin; Yuxuan Li; Yongning Lin; Xiaorui Wang; Ling Lin (Chemical Engineering Journal, 2024)

OsMKK1 is a novel element that positively regulates the Xa21-mediated resistance response to Xanthomonas oryzae pv. oryzae in rice - ZeXi Yang; Zheng Zhu; Yalu Guo; Jinping Lan; Jianshuo Zhang; Shuo Chen; Shijuan Dou; Ming Yang; Liyun Li; Guozhen Liu (Plant Cell Reports, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Large-area nanofiber membrane of NIR photothermal Cs0.32WO3 for flexible and all-weather solar thermoelectric generation - Sheng Zhuo; Wangkai Jiang; Yu Dong Zhao; Jin-Zhuo Liu; Xinyu Zhao; Jianyong Ye; Min Zheng; Zuo-Shan Wang; Xiao-Qing Zhou; Xiao-Qiao Wang; Ying-Li Shi; Weifan Chen; et al. (Chemical Engineering Journal, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Microbial diversity and potential health risks of household municipal solid waste in China: A case study in winter during outbreak of COVID-19 - Yanqing Liu; Shuang Li; Zelin Zheng; Xiangyu Zheng; Muhammad Ajmal; Ming Zhao; Wenjing Lu (Science of The Total Environment, 2023)

Unraveling the potential-dependent structure evolution in CuO for electrocatalytic biomass valorization - Ye Wang; Ming Xu; Xi Wang; Ruixiang Ge; Yu-Quan Zhu; An-Zhen Li; Hua Zhou; Fengen Chen; Lirong Zheng; Haohong Duan (Science Bulletin, 2023)

Efficient hybrid capacitive deionization with MnO2/g-C3N4 heterostructure: Enhancing Mn dz2 electron occupancy by interfacial electron bridge for fast charge transfer - Xueying Gao; Zhenzhen Fu; Yanfei Sun; Dewei Wang; Xiaoxuan Wang; Zishan Hou; Jinrui Wang; Xia Liu; Shiyu Wang; Shuyun Yao; Huiying Zhang; Shuyuan Li; et al. (Desalination, 2023)

Ultra-fast degradation of ciprofloxacin by the peroxymonosulfate activation using a Co/Al-LDH decorated magnetic hydrochar: Structural design, catalytic performance and synergistic effects - Jian Zhang; Jia-Fang Xie; Jia-Cheng E. Yang; Ding Li; Lu-Bin Zhong; Yu-Ming Zheng (Chemical Engineering Journal, 2023)

Recombinant Orf virus induced antibody production against capsid protein of porcine circovirus type 3 in mice - Kuipeng Gao; Huizi Li; Xiaoling Lei; Zhenzhen Sun; Tingting Zheng; Ming Chen; Zhangyong Ning (Veterinary Research Communications, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Numerical analysis of wake field and unsteady forces on submarine propeller with twisted rudders - Jin-ming Ye; Di Zhang; Zi-han Zheng; Wan-li Yang; Lin Ke (Ocean Engineering, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Enhancing data reliability in quantitative characterization of moisture distribution in sludge using DSC: Impact of sample attributes and test parameters - Ya-Li Zhang; Hao Zhang; Wen-Hui Liu; Ping Sun; Shao-Ming Zheng; Yun-Yan Gao; Yuan-Ping Zeng; Hou-Feng Wang; Raymond Jianxiong Zeng (Journal of Environmental Management, 2023)

Identification and characterisation of microplastics released from plastic-coated paper cups using micro-Raman spectroscopy - Tianlong Zhang; Jia-Ling Hu; Yipin Duan; Sheng Chen; Dan Li; Ben Dong; Ming-Zhen Mo; Jing Wang; Jian-Guo Zheng; Huai-Ning Zhong; Qin-Bao Lin (Food Control, 2023)

Zebrafish nos2a benefits bacterial proliferation via suppressing ROS and inducing NO production to impair the expressions of inflammatory cytokines and antibacterial genes - Si Yao Zheng; Xinbin Shao; Zhitao Qi; Maocang Yan; Min Hui Tao; Xiao Man Wu; Lining Zhang; Jianzhong Ma; An Li; Ming Xian Chang (Fish & Shellfish Immunology, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

The erythromycin sorption removal at environmentally relevant concentration based on molecular imprinted polymer: Performance and mechanism - Wen-Ming Xie; Yu Wu; Wan-Yang Yan; You Ma; Han Meng; Guo-Xiang Wang; Li-Min Zhang; Guo-Zheng Jia; Wei-Hua Li; Yan Xiao; Fang Fang (Environmental Pollution, 2023)

Enhanced lithium storage in pomegranate-like carbon via dual confinement of lithiophilic seeds and Li deposition - Tangchao Xie; Weibin Ye; Hong Xiao; Banghai Wang; Zhiling Liu; Pan Xu; Weitao Zheng; Jialang He; Hengji Zhu; Yijuan Li; Ming-Sheng Wang; Shaoming Huang (Chemical Engineering Journal, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Suppressing trap density and energy loss via skeleton asymmetry strategy enables highly efficient all-small-molecule organic solar cells - Xufan Zheng; Xunchang Wang; Fengbo Sun; Ming Wan; Zhiya Li; Cong Xiao; Tingting Cong; Tianyu Hu; Yuchen Liao; Renqiang Yang (Chemical Engineering Journal, 2023)

A Novel Large-Scale Three-Dimensional Physical Model Experimental System for Deep Underground Engineering - Xia-Ting Feng; Zheng-Wei Li; Shi-Ming Mei; Jun Tian; Cheng-Xiang Yang; Zhi-Bin Yao; Ji-Kai Gao (Rock Mechanics and Rock Engineering, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Short-term effect of meteorological factors and extreme weather events on daily outpatient visits for dry eye disease between 2013 and 2020: a time-series study in Urumqi, China - Si-Yu Gui; Fei Wang; Jian-Chao Qiao; Xin-Chen Wang; Zhi-Hao Huang; Fan Yang; Cheng-Yang Hu; Fang-Biao Tao; Li-Ming Tao; Dong-Wei Liu; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Efficacy of a porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) natural recombinant against a heterologous PRRSV-1 isolate both clustered within the subgroup of BJEU06-1-like isolates - Chen Li; Shuai Li; Shubin Li; Ming Qiu; Hong Lin; Zhe Sun; Yuejia Qiu; Wenhao Qi; Binghui Feng; Jixiang Li; Wanglong Zheng; Xiuling Yu; et al. (Veterinary Microbiology, 2023)

Inventory of cadmium-transporter genes in the root of mangrove plant Avicennia marina under cadmium stress - Lu-Dan Zhang; Ling-Yu Song; Ming-Jin Dai; Jin-Yu Liu; Jing Li; Chao-Qun Xu; Ze-Jun Guo; Shi-Wei Song; Jing-Wen Liu; Xue-Yi Zhu; Hai-Lei Zheng (Journal of Hazardous Materials, 2023)

Transcriptome analysis provides insights into the high ability to synthesize fatty acids in “yellow oil” mud crab (Scylla paramamosain) - Ming Zhang; Ngoc Tuan Tran; Peina Ji; Yongsheng Zhang; Daimeng Zhang; Huaiping Zheng; Shengkang Li (Food Research International, 2023)

Self-assembly and interaction mechanisms of edible dock protein and flavonoids regulated by the phenolic hydroxyl position - Qian Zhou; Xiao-Jie Wang; Jing Li; Yu-Ru Wu; Wei Wang; Zhen-Yu Yu; Ya-Qing Xiao; Ying-Nan Liu; Shi-Yi Li; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2023)

Time-programmed activation of CD47 disruption and immunogenic cell death with Cas9 ribonucleoprotein nanocapsule for improved cancer immunotherapy - Yumeng Xing; Jianhui Yang; Chun Wang; Ziyao Kang; Zheng Pan; Jihui Tang; Fenghe Li; Xiao Wang; Xiao-ming Meng; Zhifei Cheng; Yang Liu; Qi Liu (Chemical Engineering Journal, 2023)

Experimental and theoretical insights into metal-free catalytic reduction of nitrophenols over porous nitrogen-doped reduced graphene oxide - Meng-Yao Qi; Yuexing Zhang; Qianni Li; Ling Wu; Binghua Zhou; Zhipeng Wang; Zheng-Hong Huang; Ming-Xi Wang (Chemical Engineering Journal, 2023)

Study on pore-water pressure variation and deformation characteristics of warm frozen soils under confined dynamic loading - Jintao Hu; Hu Zhang; Zheng Li; Suiqiao Yang; Shengrong Zhang; Hongchun Li; Ming Lu (Cold Regions Science and Technology, 2023)

Molecular characterization of stable QTL and putative candidate genes for grain zinc and iron concentrations in two related wheat populations - Mengjing Sun; Qiaoling Luo; Qi Zheng; Jingyang Tong; Yue Wang; Jie Song; Yelun Zhang; Zongjun Pu; Jianmin Zheng; Lianzheng Liu; Anding Zhou; Awais Rasheed; et al. (Theoretical and Applied Genetics, 2023)

Effects of hypoxia on the gill morphological structure, apoptosis and hypoxia-related gene expression in blunt snout bream (Megalobrama amblycephala) - Xin-xin Yu; Yan-rui Zhang; Shan-shan Li; Guo-dong Zheng; Shu-ming Zou (Fish Physiology and Biochemistry, 2023)

Combining hydrochemistry and 13C analysis to reveal the sources and contributions of dissolved inorganic carbon in the groundwater of coal mining areas, in East China - Chunlu Jiang; Ming Li; Chang Li; Wendi Huang; Liugen Zheng (Environmental Geochemistry and Health, 2023)

Damage detection of foundation pile in high-pile wharf based on statistical high-order moment of dynamic response under regular wave excitation - Rui-hu Zhu; Qi-ming Wang; Jin-hai Zheng; Hai-kun Zeng; Jia-bao Zhang; Yan Hu; Cheng-ming Li (Ocean Engineering, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

Assessment of dynamic drought-induced ecosystem risk: Integrating time-varying hazard frequency, exposure and vulnerability - Wei Fang; Qiang Huang; Gordon Huang; Bo Ming; Quan Quan; Pei Li; Yi Guo; Xudong Zheng; Gang Feng; Jian Peng (Journal of Environmental Management, 2023)

Systematic analyzing a five- miRNA panel and its diagnostic value of plasma expression in colorectal cancer - Si-Qi Li; Li-Ye Xie; Zheng-Min Cai; Hao-Tang Wei; Ming-Zhi Xie; Bang-Li Hu; Shu-Fang Ning (Molecular Biology Reports, 2023)

Cordythiazole A, the first member of thiazole alkaloids from Chinese cordyceps, with α-glucosidase inhibitory activity - Xue Han; Li-Hua Liu; Xiao-Ying Fang; Shu-Tai Jiang; Huan Zhao; Zheng-Ming Qian; Zhi-Nan Yin; Li-Gong Lu; Chuan-Xi Wang; Xin-Sheng Yao; Hao Gao (Journal of Natural Medicines, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Changes in physicochemical characteristics and metabolites in the fermentation of goji juice by Lactiplantibacillus plantarum - Han Xie; Pengyan Gao; Zhen-Ming Lu; Fang-Zhou Wang; Li-Juan Chai; Jin-Song Shi; Hui-Ling Zhang; Yan Geng; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2023)

Emerging roles of air pollution and meteorological factors in autoimmune eye diseases - Fan Cao; Zhuo-Ran Liu; Qin-Yu Ni; Chen-Kai Zha; Shu-Jie Zhang; Jia-Min Lu; Yue-Yang Xu; Li-Ming Tao; Zheng-Xuan Jiang; Hai-Feng Pan (Environmental Research, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Critical Metals Ga, Ge and In in the Global Pb-Zn Deposits: Current Understanding, Challenges and Perspectives - Yi Zheng; Peng-Peng Yu; Zhan-Ke Li; Suo-Fei Xiong; Ling-Li Zhou; Jia-Xi Zhou; Chang-Ming Wang; Yu-Miao Meng; Yu Zhang; Ye-Jian Wang; Jing Xu; Yue Wu; et al. (Journal of Earth Science, 2023)

Differential evolution with objective and dimension knowledge utilization - Sheng Xin Zhang; Shao Yong Zheng; Li Ming Zheng (Swarm and Evolutionary Computation, 2023)

Sodium selenite inhibits proliferation of lung cancer cells by inhibiting NF-κB nuclear translocation and down-regulating PDK1 expression which is a key enzyme in energy metabolism expression - Xiao Xu; Yaqin Hou; Shumeng Lin; Kai Wang; Yanbei Ren; Tiansheng Zheng; Xi Zhang; Ming Li; Lihong Fan (Journal of Trace Elements in Medicine and Biology, 2023)

Identification of sweet spots in shale-type and siltstone-type “shale oil systems”: A case study of the Chang 7 Member in Ordos Basin - Songqi Pan; Qiulei Guo; Caineng Zou; Zhenhua Jing; Ming Yuan; Ying He; He Zheng; Ying Mu; Zhi Yang; Shixiang Li; Xinping Zhou; Songtao Wu; et al. (Science China Earth Sciences, 2023)

Inulin acetate as a novel recombinant subunit vaccine carrier for immunization of tilapia against tilapia lake virus - Yu-Ying Zheng; Yang Li; Tian-Zi Sun; Xue-Feng Wei; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Bin Zhu (Aquaculture, 2023)

Aromatic polyketide aspergillones A-D from the endophytic fungus Aspergillus sclerotiorum - Yue Hu; Yi-Lei Zheng; Zhuo-Da Zhou; Min Li; Ming-Ling Wang; Ling-Yi Kong; Ming-Hua Yang (Phytochemistry Letters, 2023)

The contradictory roles of tightly bound and loosely bound extracellular polymeric substances of activated sludge in trimethoprim adsorption process - You Ma; Tian-Yu Li; Han Meng; Guo-Xiang Wang; Li-Min Zhang; Guo-Zheng Jia; Jie Ma; Yan Xiao; Wei-Hua Li; Wen-Ming Xie (Journal of Environmental Management, 2023)

Control release of α-mangostin by a novel dual-polysaccharides delivery system for colitis treatment under simulated gastrointestinal conditions - Jialong Li; Cuicui Zeng; Qiqi Huang; Ming-Ming Zheng; Jing Chen; Da Ma (Food Bioscience, 2023)

What affects the accuracy and applicability of determining wastewater sludge water content via low-field nuclear magnetic resonance? - Ya-Li Zhang; Ping Sun; Bing-Bing Dai; Shao-Ming Zheng; Dan-Di Ran; Tian-Xin Wu; Raymond Jianxiong Zeng; Hou-Feng Wang (Environmental Research, 2023)

A single fluorescent probe reveals changes in endoplasmic reticulum–mitochondria contact in hepatocytes during ferroptosis - Ling-Li Wang; Ya-Ru Zhang; Ming-Hua Zheng; Xuan Wang; Xue Wu; Jing-Yi Jin (Chemical Engineering Journal, 2023)

Impact of side-chain engineering on quantum efficiency and voltage losses in organic solar cells - Jing Wang; Deping Qian; Fangliang Dong; Hongbo Wu; Hailin Pan; Shijie Liang; Hanyu Wu; Xunda Feng; Weiwei Li; Ming Wang; Zheng Tang; Zaifei Ma (Chemical Engineering Journal, 2023)

Drinking water quality and inflammatory bowel disease: a prospective cohort study - Shuduo Zhou; Pengfei Chai; Xuejie Dong; Zhisheng Liang; Zongming Yang; Junxia Li; Guigen Teng; Shengzhi Sun; Ming Xu; Zhi-Jie Zheng; Jianbing Wang; Zhenyu Zhang; et al. (Environmental Science and Pollution Research, 2023)

Ancylobacter mangrovi sp. nov., a novel endophytic bacterium isolated from mangrove plant - Fei-Na Li; Zhou-Qing Zheng; Ming-Sheng Chen; Xiao-Hui Chen; Li Tuo (Systematic and Applied Microbiology, 2023)

PpIBH1-1 limits internode elongation of peach shoot in a dose-dependent manner - Mengmeng Zhang; Beibei Feng; Yun Chen; Mingxi Geng; Ming Li; Xianbo Zheng; Haipeng Zhang; Langlang Zhang; Bin Tan; Xia Ye; Wei Wang; Jidong Li; et al. (Plant Science, 2023)

Physical information-fused deep learning model ensembled with a subregion-specific sampling method for predicting flood dynamics - Changli Li; Zheng Han; Yange Li; Ming Li; Weidong Wang; Jie Dou; Linrong Xu; Guangqi Chen (Journal of Hydrology, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Carbon vacancies in porous g-C3N4 nanosheets induced robust H2O2 production for highly efficient photocatalysis-self-Fenton system for metronidazole degradation - Rujin Li; Ming Zheng; Xin Zhou; Dan Zhang; Yan Shi; Chunxiang Li; Min Yang (Chemical Engineering Journal, 2023)

Revealing the dynamic temperature of the cathode catalyst layer inside proton exchange membrane fuel cell by experimental measurements and numerical analysis - Qianqian Wang; Fumin Tang; Xiang Li; Jim P. Zheng; Liang Hao; Guomin Cui; Pingwen Ming (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Ensemble learning system to identify nutritional risk and malnutrition in cancer patients without weight loss information - Liangyu Yin; Jie Liu; Ming Liu; Jin Zheng; Aiguo Xu; Quanjun Lyu; Yongdong Feng; Zengqing Guo; Hu Ma; Jipeng Li; Zhikang Chen; Hui Wang; et al. (Science China Life Sciences, 2023)

Extracellular Vesicles Derived from Bone Mesenchymal Stem Cells Carrying circ_0000075 Relieves Cerebral Ischemic Injury by Competitively Inhibiting miR-218-5p and Up-regulating E3 Ubiquitin Ligase SMURF2 - Yue Liu; You-Ping Li; Li-Min Xiao; Li-Ke Chen; Su-Yue Zheng; Er-Ming Zeng; Chun-Hua Xu (Molecular Neurobiology, 2023)

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

Bacteria and filamentous fungi running a relay race in Daqu fermentation enable macromolecular degradation and flavor substance formation - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2023)

The priming effects of plant leachates on dissolved organic matter degradation in water depend on leachate type and water stability - Yuan Cui; Jian-Qiao Meng; Yu-Han Chen; Fei-Fan Shao; Xuan-Zheng Chen; Yu Jin; Ming-Xiang Zhang; Guo Yun-Qian; Fang-Li Luo; Fei-Hai Yu (Environmental Research, 2023)

Development, calibration and validation of a phase-averaged model for cross-shore sediment transport and morphodynamics on a barred beach - Peng Zheng; Gugum Gumbira; Ming Li; Joep van der Zanden; Dominic van der A; Jebbe van der Werf; Xueen Chen; Xiaonan Tang (Continental Shelf Research, 2023)

Vsig4+ resident single-Kupffer cells improve hepatic inflammation and fibrosis in NASH - Hui-Yi Li; Seng-Wang Fu; Jun-Cheng Wu; Zheng-Hong Li; Ming-Yi Xu (Inflammation Research, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

YTHDF2 controls hexavalent chromium-induced mitophagy through modulating Hif1α and Bnip3 decay via the m6A/mRNA pathway in spermatogonial stem cells/progenitors - Tianjiao Li; Yi Zheng; Zhili Wu; Ming Guo; Ruifang Liu; Wenxian Zeng; Yinghua Lv (Toxicology Letters, 2023)

Associations between trace level thallium and multiple health effects in rural areas: Chinese Exposure and Response Mapping Program (CERMP) - Yun-Jiang Yu; Zhen-Chi Li; Yang Zhou; Chen-Yin Dong; Hong-Xuan Kuang; Tong Zheng; Ming-Deng Xiang; Xi-Chao Chen; Hong-Yan Li; Xiao-Wen Zeng; Shu-Li Xu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Revisiting the centrality definition and observable centrality dependence of relativistic heavy-ion collisions in PACIAE model - Yu-Liang Yan; Dai-Mei Zhou; An-Ke Lei; Xiao-Mei Li; Xiao-Ming Zhang; Liang Zheng; Gang Chen; Xu Cai; Ben-Hao Sa (Computer Physics Communications, 2023)

An electrostatic force-independent dephosphorylation-driven chemiluminescent biosensor for sensitive and rapid detection of poly(ADP-ribose) polymerase-1 in human breast tissues - Ming-hao Liu; Feng-zheng Li; Wen-jing Liu; Juan Hu; Meng Liu; Chun-Yang Zhang (Chemical Engineering Journal, 2023)

Influence of plants on anammox process in constructed Wetland: Irrelevance, inhibition or enhancement - Jie Li; Lin Liu; Yu-Ming Zheng; Lin Ma; Quan-Bao Zhao; Xuan Wang; Chao-Xiang Liu (Chemical Engineering Journal, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Fractal analysis on CO2 hydrate-bearing sands during formation and dissociation processes with NMR - Yuechao Zhao; Ming Li; Shuang Dong; Jia-nan Zheng; Xu Lei; Cong Chen; Yongchen Song (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Optical bulk-boundary dichotomy in a quantum spin Hall insulator - Junfeng Han; Pengcheng Mao; Hailong Chen; Jia-Xin Yin; Maoyuan Wang; Dongyun Chen; Yongkai Li; Jingchuan Zheng; Xu Zhang; Dashuai Ma; Qiong Ma; Zhi-Ming Yu; et al. (Science Bulletin, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Probing the stability of perovskite solar cell under working condition through an ultra-thin silver electrode: Beyond the halide ion diffusion and metal diffusion - Hao Li; Zheng Yan; Min Li; Xiaoyan Wen; Shuo Deng; Sisi Liu; Wallace C.H. Choy; Lijie Li; Ming-Yu Li; Haifei Lu (Chemical Engineering Journal, 2023)

Analysis of microplastics released from plastic take-out food containers based on thermal properties and morphology study - Jia-Ling Hu; Yipin Duan; Huai-Ning Zhong; Qin-Bao Lin; Tianlong Zhang; Chuang-Chuang Zhao; Sheng Chen; Ben Dong; Dan Li; Jing Wang; Ming-Zhen Mo; Jie Chen; et al. (Food Additives & Contaminants: Part A, 2023)

Technological development pathway for carbon neutrality in China - Siyue Guo; Yu Liu; Weichen Zhao; Jiaquan Li; Guangwen Hu; Hui Kong; Yifan Gu; Bang Xu; Xiaodan Huang; Yan Zheng; Shihan Zhang; Da Zhang; et al. (Science Bulletin, 2023)

Early Paleozoic collision-related structures in the Tarim Craton, NW China: Implications for the Proto-Tethys evolution - Yue-Jun Li; Yong-Jin Gao; Hui Zhou; Guang-Ya Zhang; Lei Wen; Yan Zhao; Cheng Li; Duo-Ming Zheng; Ya-Lei Liu; Hong-Hui Li; Cai-Ming Luo; Tong-Fei Huang; et al. (Journal of Asian Earth Sciences, 2023)

Marked shifts of harmful algal blooms in the Bohai Sea linked with combined impacts of environmental changes - Xiao-Yu Li; Ren-Cheng Yu; Anthony J. Richardson; Chaojiao Sun; Ruth Eriksen; Fan-Zhou Kong; Zheng-Xi Zhou; Hui-Xia Geng; Qing-Chun Zhang; Ming-Jiang Zhou (Harmful Algae, 2023)

Regulating electronic structure by Mn doping for nickel cobalt hydroxide nanosheets/carbon nanotube to promote oxygen evolution reaction and oxidation of urea and hydrazine - Kaili Wu; Chenyang Cao; Keren Li; Chaojie Lyu; Jiarun Cheng; Hongyu Li; Pengfei Hu; Jiwen Wu; Woon-Ming Lau; Xixi Zhu; Ping Qian; Jinlong Zheng (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Seasonal variability of eddy kinetic energy in the East Australian current region - Jia Liu; Shaojun Zheng; Ming Feng; Lingling Xie; Baoxin Feng; Peng Liang; Lei Wang; Lina Yang; Li Yan (Frontiers in Marine Science, 2022)
The East Australian Current (EAC) is an important western boundary current of the South Pacific subtropical Circulation with high mesoscale eddy kinetic energy (EKE). Based on satellite altimeter observations and outputs from the eddy-resolving ocean general circulation model (OGCM) for the Earth Simulator (OFES), the seasonal variability of EKE and its associated dynamic mechanism in the EAC region are studied. High EKE is mainly concentrated in the shear-region between the poleward EAC southern extension and the equatorward EAC recirculation along Australia's east coast, which is confined within the upper ocean (0-300 m). EKE in this area exhibits obvious seasonal variation, strong in austral summer with maximum (465±89 cm² s-²) in February and weak in winter with minimum (334±48 cm² s-²) in August. Energetics analysis from OFES suggests that the seasonal variability of EKE is modulated by the mixed instabilities composed of barotropic and baroclinic instabilities confined within the upper ocean, and barotropic instability (baroclinic instability) is the main energy source of EKE in austral summer (winter). The barotropic process is mainly controlled by the zonal shear of meridional velocities of the EAC southern extension and the EAC recirculation. The poleward EAC southern extension and the equatorward EAC recirculation are synchronously strengthened (weakened) due to the local positive (negative) sea level anomalies (SLA) under geostrophic equilibrium, and the barotropic instability dominated by zonal shear is enhanced (slackened), which results in a high (low) level of EKE in the EAC region.

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Jiella avicenniae sp. nov., a novel endophytic bacterium isolated from bark of Avicennia marina - Yong Zhang; Fang Liu; Fei-Na Li; Ming-Sheng Chen; Xiao Ma; Zhou-Qing Zheng; Li Tuo (Archives of Microbiology, 2022)

The association between ethylene oxide exposure and asthma risk: a population-based study - Ziye Li; Pingfan Shi; Zhibo Chen; Wenjia Zhang; Shumeng Lin; Tiansheng Zheng; Ming Li; Lihong Fan (Environmental Science and Pollution Research, 2022)

Stress analysis of full-length grouted bolt under shear deformation of anchor interface - Zheng-de Zhu; Xiao-yun Shu; Zhe Li; Hong-ming Tian; Yun Tian (Journal of Mountain Science, 2022)

Starvation shrinks the mussel foot secretory glands and impairs the byssal attachment - Yi Zheng; Yue-Ming Yang; Yue-Feng Xu; Yu-Qing Wang; Xue Shi; Gao-Hai Zheng; Yi-Feng Li (Frontiers in Marine Science, 2022)
Mussel is an economically and ecologically important species widely distributed throughout the world. The mussel adheres to the attachment substrate by secreting byssus external to the body. Various environmental and biological factors influence the process of byssus secretion, and the present study investigated the effect of starvation on byssal secretion in the hard-shelled mussel Mytilus coruscus . Histological changes in mussel foot secretory glands and gene expression of mussel foot proteins were also determined. The experimental setup consisted of starvation treatments for 7, 14 and 21 days, and the control groups. The results showed that the number of produced byssus was higher in the starvation group compared to the control (CTR) group, and the starvation group had a significantly higher of byssal shedding number from 6 days of starvation treatment onwards ( p < 0.05). The byssal thread diameter was significantly reduced in all starvation treatment groups ( p < 0.05). However, starvation treatment had no effect on the length of the byssal thread ( p > 0.05). After 21 days of starvation treatment, the byssal thread volume was significantly lower than that of the CTR group ( p < 0.05). A significant decrease in the breaking force of the byssal thread was observed after 14 and 21 days of starvation treatment ( p < 0.05), along with an upward shift in the breakpoints. Starvation treatment significantly reduced the percentage of foot secretory glands area to total tissue ( p < 0.05). The expression of the mussel foot protein genes ( Mcfp-1P and Mcfp-1T ) was significantly up-regulated at 7 days of starvation treatment ( p < 0.05). These findings reveal that starvation weakens byssal thread performance by influencing mussel foot secretory glands, which increases the dislodgment risks of suspended-cultured mussels.

Construction of a target MSNs drugcarrier loaded with siRNAGLI1 and siRNASMO aim at hedgehog signal pathway and the pharmacodynamic study of drug-carriers in the treatment of leukemia stem cells - Yuan Zhang; Rui Cai; HaiJun Li; Yu Duan; Yan Zhang; Wei Jing; ShaoGang Lv; Xi Chu; Zheng Cao; Lei Yang; Liang Ming (Drug Delivery and Translational Research, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

Assessment of brain connectome alterations in male chronic smokers using structural and generalized q-sampling MRI - Jun-Cheng Weng; Yu-Chen Chuang; Li-Bang Zheng; Ming-Shih Lee; Ming-Chou Ho (Brain Imaging and Behavior, 2022)

Improving protected area effectiveness through consideration of different human‐pressure baselines - Chun‐Ting Feng; Ming Cao; Fang‐Zheng Liu; Yue Zhou; Jin‐Hong Du; Li‐Bo Zhang; Wen‐Jie Huang; Jian‐Wu Luo; Jun‐Sheng Li; Wei Wang (Conservation Biology, 2022)
Previous assessments of the effectiveness of protected areas (PAs) focused primarily on changes in human pressure over time and did not consider the different human‐pressure baselines of PAs, thereby potentially over‐ or underestimating PA effectiveness. We developed a framework that considers both human‐pressure baseline and change in human pressure over time and assessed the effectiveness of 338 PAs in China from 2010 to 2020. The initial state of human pressure on PAs was taken as the baseline, and changes in human pressure index (HPI) were further analyzed under different baselines. We used the random forest models to identify the management measures that most improved effectiveness in resisting human pressure for the PAs with different baselines. Finally, the relationships between the changes in the HPI and the changes in natural ecosystems in PAs were analyzed with different baselines. Of PAs with low HPI baselines, medium HPI baselines, and high HPI baselines, 76.92% ( n =150), 11.11% ( n =12), and 22.86% ( n =8) , respectively, showed positive effects in resisting human pressure. Overall, ignoring human‐pressure baselines somewhat underestimated the positive effects of PAs, especially for those with low initial human pressure. For PAs with different initial human pressures, different management measures should be taken to improve effectiveness and reduce threats to natural ecosystems. We believe our framework is useful for assessing the effectiveness of PAs globally, and we recommend it be included in the Convention on Biological Diversity Post‐2020 Strategy.

The fate of flavonoids after oral administration: a comprehensive overview of its bioavailability - Abid Naeem; Yang Ming; Hu Pengyi; Kang Yong Jie; Liu Yali; Zhang Haiyan; Xiao Shuai; Li Wenjing; Wu Ling; Zhang Ming Xia; Liu Shan Shan; Zheng Qin (Critical Reviews in Food Science and Nutrition, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Association between meteorological factors and hospital admissions for uveitis in Hefei, China: a time-series study - Fan Cao; Yi-Sheng He; Kun Xiang; Cheng-Huan Wan; Wei Liu; Yan-Chao Gui; Hai-Feng Pan; Zheng-Xuan Jiang; Li-Ming Tao (Environmental Science and Pollution Research, 2022)

Carbon emission efficiency and spatio-temporal dynamic evolution of the cities in Beijing-Tianjin-Hebei Region, China - Li-Ming Xue; Zhi-Xue Zheng; Shuo Meng; Mingjun Li; Huaqing Li; Ji-Ming Chen (Environment, Development and Sustainability, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Transcriptome revealing the dual regulatory mechanism of ethylene on the rhynchophylline and isorhynchophylline in Uncaria rhynchophylla - Xue Li; Xiao-hong Wang; Wei Qiang; Hao-jie Zheng; Li-yang ShangGuan; Ming-sheng Zhang (Journal of Plant Research, 2022)

Distinct co-occurrence patterns and driving forces of abundant and rare bacterial communities in the multispecies solid-state fermentation process of cereal vinegar - Ming-Ye Peng; Zhen-Ming Lu; Xiao-Juan Zhang; Ting Huang; Yong-Jian Deng; Li-Juan Chai; Jin-Song Shi; Zheng-Hong Xu (Systems Microbiology and Biomanufacturing, 2022)

Transcriptomic analyses reveal the effect of nitric oxide on the lateral root development and growth of mangrove plant Kandelia obovata - Ming-Yue Wei; Huan Li; You-Hui Zhong; Zhi-Jun Shen; Dong-Na Ma; Chang-Hao Gao; Yi-Ling Liu; Wen-Hua Wang; Jing-Ya Zhang; Yan-Ping You; Hai-Lei Zheng (Plant and Soil, 2022)

Comparative transcriptome analysis revealed the molecular mechanism of the effect of light intensity on the accumulation of rhynchophylline and isorhynchophylline in Uncaria rhynchophylla - Xiao-Hong Wang; Xue Li; Wei Qiang; Xiao-Song Yu; Hao-Jie Zheng; Ming-Sheng Zhang (Physiology and Molecular Biology of Plants, 2022)

Integrins in the Regulation of Mesenchymal Stem Cell Differentiation by Mechanical Signals - Lei Wang; Fuwen Zheng; Ruixue Song; Lequan Zhuang; Ming Yang; Jian Suo; Lisha Li (Stem Cell Reviews and Reports, 2022)

Using Mendelian randomization as the cornerstone for causal inference in epidemiology - Jianguo Xu; Muyang Li; Ya Gao; Ming Liu; Shuzhen Shi; Jiyuan Shi; Kelu Yang; Zheng Zhou; Jinhui Tian (Environmental Science and Pollution Research, 2022)

Using computational fluid dynamic simulation with Flow-3D to reveal the origin of the mushroom stone in the Xiqiao Mountain of Guangdong, China - Jian-cheng Li; Wei Wang; Yan-ming Zheng; Xiao-hao Wen; Jing Feng; Li Sheng; Chen Wang; Ming-kun Qiu (Journal of Mountain Science, 2022)

Alteribacter salitolerans sp. nov., isolated from a saline-alkaline soil - Shuang Wang; Lei Sun; Manik Prabhu Narsing Rao; Guo-Hong Liu; Pin-Jiao Jin; Zhou-Yan Dong; Zheng-Han Lian; Xiao-Yu Hao; Ming-Yi Zhang; Wen-Jun Li (Archives of Microbiology, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Effective Thermal Conductivity Estimation of Fractured Rock Masses - Zheng-Wei Li; Yuan Liu; Shi-Ming Mei; Shi-Cheng Xing; Xiao-Kai Wang (Rock Mechanics and Rock Engineering, 2021)

Yak Excreta Application Alter Nitrification by Regulating the Ammonia-Oxidizing Bacterial Communities in Wetland Soils - Li Chen; Rong Bo Zheng; Jun Qin Gao; Ming Hua Song; Xue Lian Guo (Journal of Soil Science and Plant Nutrition, 2021)

Tissue distribution of SARS-CoV-2 in non-human primates after combined intratracheal and intranasal inoculation - Tian-Zhang Song; Jian-Bao Han; Xiang Yang; Ming-Hua Li; Yong-Tang Zheng (Science China Life Sciences, 2021)

Influences and mechanisms of nanoparticles on pentachloronitrobenzene accumulation by earthworms - Ming Li; Guanghui Xu; Na Guo; Na Zheng; Weihua Dong; Xiao Li; Yong Yu (Environmental Science and Pollution Research, 2021)

Cross‐phytogroup assessment of foliar epiphytic mycobiomes - Ting Zhu; Jia Yao; Hao Liu; Chen‐Hao Zhou; Yuan‐Zhan Liu; Zheng‐Wei Wang; Zhe‐Xue Quan; Bo Li; Ji Yang; Wei‐Chang Huang; Ming Nie (Environmental Microbiology, 2021)
Summary The foliar surface forms one of the largest aboveground habitats on Earth and maintains plant‐fungus relationships that greatly affect ecosystem functioning. Despite many studies with particular plant species, the foliar epiphytic mycobiome has not been studied across a large number of plant species from different taxa. Using high‐throughput sequencing, we assessed epiphytic mycobiomes on leaf surfaces of 592 plant species in a botanical garden. Plants of angiosperms, gymnosperms, and pteridophytes were involved. Plant taxonomy, leaf side, growing environment, and evolutionary relationships were considered. We found that pteridophytes showed the higher fungal species diversity, stronger mutualistic fungal interactions, and a greater percentage of putative pathogens than gymnosperms and angiosperms. Plant taxonomic group, leaf side, and growing environment were significantly associated with the foliar epiphytic mycobiome, but the similarity of the mycobiomes among plants was not directly related to the distance of the host evolutionary tree. Our results provide a general understanding of the foliar fungal mycobiomes from pteridophytes to angiosperms. These findings will facilitate our understanding of foliar fungal epiphytes and their roles in plant communities and ecosystems.

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

The downregulation of PpPG21 and PpPG22 influences peach fruit texture and softening - Ming Qian; Ze Xu; Zehua Zhang; Qin Li; Xiangyan Yan; Hangkong Liu; Mingyu Han; Furui Li; Jicheng Zheng; Dong Zhang; Caiping Zhao (Planta, 2021)

Phylogenomic Analyses of a Clade Within the Family Flavobacteriaceae Suggest Taxonomic Reassignments of Species of the Genera Algibacter, Hyunsoonleella, Jejuia, and Flavivirga, and the Proposal of Pseudalgibacter gen. nov. and Pseudalgibacter alginicilyticus comb. nov. - Miao Li; Ling-Zhi Hou; Xing-Hao Xu; Xiao-Xiao Wang; Ming-Can Zheng; Yan-Jiao Zhang; Ang Liu (Current Microbiology, 2021)

A luminescent Zn(II)-Containing Complex: Selective Sensing of Cr(VI) Anion and Application Values on Tuberculosis Care Through Increasing the Antibacterial Response of Macrophages - Jin-Chao Mao; Jin-Jing Hong; Ming-Zheng Lin; Feng Han; Dong Li (Journal of Fluorescence, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Overexpression of T-type calcium channel Cav3.1 in oral squamous cell carcinoma: association with proliferation and anti-apoptotic activity - Rui-Fang Li; Qi-Wen Man; Jin-Yuan Liu; Yue-Yu Zheng; Xin Gao; Hai-Ming Liu (Journal of Molecular Histology, 2021)

Benzoyl ester formation in Aspergillus ustus by hijacking the polyketide acyl intermediates with alcohols - Liujuan Zheng; Shu-Ming Li (Archives of Microbiology, 2021)
Accumulation of two benzoyl esters in Aspergillus ustus after feeding with alcohols was reported 30 years ago. To the best of our knowledge, the biosynthesis for these esters has not been elucidated prior to this study. Here, we demonstrate that these compounds are artifical products of the phenethyl polyketide ustethylin A biosynthestic pathway. In addition, four aditional benzoyl esters with different methylation levels were also isolated and identified as shunt products. Feeding experiments provided evidence that the enzyme-bound polyketide acyl intermediates are hijacked by externally fed MeOH or EtOH, leading to the formation of the benzoyl esters. Graphic abstract

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Oceanomicrobium pacificus gen. nov., sp. nov., a member of the family Rhodobacteraceae isolated from seawater of tropical western Pacific - Dadong Dai; Yangjie Li; Wenxuan He; Fang Qin; Jinshui Zheng; Ming Sun; Dechao Zhang (Antonie van Leeuwenhoek, 2021)

Spatial distribution of atmospheric bioaerosols in Beijing, Hangzhou and Wuhan, China - Xuezheng Ma; Qi Zhang; Keyang Liu; Liping Zhang; Manman Zhang; Xin Zhao; Chunya Zhou; Jinke Li; Ming Cheng; Lili Li; Kongxin Hu; Jinsong Li; et al. (Aerobiologia, 2021)

GmNAC06, a NAC domain transcription factor enhances salt stress tolerance in soybean - Ming Li; Rui Chen; Qiyan Jiang; Xianjun Sun; Hui Zhang; Zheng Hu (Plant Molecular Biology, 2021)
Key message We found GmNAC06 plays an important role in salt stress responses through the phenotypic, physiological and molecular analyses of OE, VC, and Mutant composite soybean. Abstract Salinization affects 20% of all cultivated land worldwide because of the high salinity of irrigation water and the excessive use of water, and this amount is increasing daily. NAC (NAM, ATAF, and CUC) have been found to be involved in salt stress. In this study, a soybean NAC gene, GmNAC06 (Glyma06g21020.1), was cloned and functionally characterized. The results of expression analysis suggested that salt stress could influence the expression level of GmNAC06 . The subcellular localization analysis results suggested that GmNAC06 may function as a transcription factor. Under salt stress, the overexpression technology combined with CRISPR-Cas9 system found that GmNAC06 could cause the accumulation of proline and glycine betaine to alleviate or avoid the negative effects of ROS; similarly, it could control the Na + /K + ratios in hairy roots to maintain ionic homeostasis. The fresh weight of the transgenic hairy roots and the histochemical ROS staining of wild leaves suggested that transgenic hairy roots influence the function of wild leaves under salt stress conditions. Moreover, the expression levels of GmUBC2 and GmHKT1 were higher in the GmNAC06 hairy roots than in the control. Thus, the overexpression of GmNAC06 in hairy roots notably causes an entire composite plant to exhibit salt tolerance. The phenotype of composite soybean plants and transgenic Arabidopsis plants suggest that GmNAC06 plays a role in response to salt stress and could be useful in generating salt tolerant transgenic crops.

Down-regulation of MANNANASE7 gene in Brassica napus L. enhances silique dehiscence-resistance - Yu-Long Li; Yan-Kun Yu; Ke-Ming Zhu; Li-Na Ding; Zheng Wang; Yan-Hua Yang; Jun Cao; Li-Zhang Xu; Yao-Ming Li; Xiao-Li Tan (Plant Cell Reports, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Identification of immune-related gene signature predicting survival in the tumor microenvironment of lung adenocarcinoma - Mengnan Zhao; Ming Li; Zhencong Chen; Yunyi Bian; Yuansheng Zheng; Zhengyang Hu; Jiaqi Liang; Yiwei Huang; Jiacheng Yin; Cheng Zhan; Mingxiang Feng; Qun Wang (Immunogenetics, 2020)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Characteristics of discontinuities in Heifangtai landslide area in Gansu, China - Bin Li; Qiang Xu; Qiang Cheng; Tian-Xiang Liu; Ming-Gao Tang; Guang Zheng; Hai-Yan Wang (Applied Geophysics, 2020)

Effects of the Lower Airway Secretions on Airway Opening Pressures and Suction Pressures in Critically Ill COVID-19 Patients: A Computational Simulation - Zhenglong Chen; Ming Zhong; Li Jiang; Nanshan Chen; Shengjin Tu; Yuan Wei; Ling Sang; Xia Zheng; Chunyuan Zhang; Jiale Tao; Linhong Deng; Yuanlin Song (Annals of Biomedical Engineering, 2020)

Interleukin-1β in hypothalamic paraventricular nucleus mediates excitatory renal reflex - Fen Zheng; Chao Ye; Guo-Wei Wan; Bing Zhou; Ying Tong; Jian-Zhen Lei; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2020)

Genome-wide transcriptome and proteome profiles indicate an active role of alternative splicing during de-etiolation of maize seedlings - Zhen Yan; Zhuo Shen; Zhe Li; Qing Chao; Lei Kong; Zhi-Fang Gao; Qing-Wei Li; Hai-Yan Zheng; Cai-Feng Zhao; Cong-Ming Lu; Ying-Wei Wang; Bai-Chen Wang (Planta, 2020)

Upregulation of long non-coding RNA MEG3 in type 2 diabetes mellitus complicated with vascular disease: a case–control study - Wei-wei Chang; Liu Zhang; Xin-ming Yao; Yan Chen; Li-jun Zhu; Zheng-mei Fang; Ying Zhao; Ying-shui Yao; Yue-long Jin (Molecular and Cellular Biochemistry, 2020)

Postchemotherapy hippocampal functional connectivity patterns in patients with breast cancer: a longitudinal resting state functional MR imaging study - Yun Feng; Dilihumaer Tuluhong; Zhao Shi; Li Juan Zheng; Tao Chen; Guang Ming Lu; Shaohua Wang; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Assessment of the air pollution emission reduction effect of the coal substitution policy in China: an improved grey modelling approach - Ming-Huan Shou; Zheng-Xin Wang; Dan-Dan Li; Yi Wang (Environmental Science and Pollution Research, 2020)

Anthraquinone derivatives from a coral associated fungus Stemphylium lycopersici - Jiao Li; Yu-Bing Zheng; Tibor Kurtán; Ming-Xiang Liu; Hua Tang; Chun-Lin Zhuang; Wen Zhang (Natural Product Research, 2020)

Isolation of a Male-Specific Molecular Marker and Development of a Genetic Sex Identification Technique in Spotted Knifejaw (Oplegnathus punctatus) - Ming Li; Hao Xu; Wenteng Xu; Qian Zhou; Xiwen Xu; Ying Zhu; Weiwei Zheng; Wensheng Li; Zunfang Pang; Songlin Chen (Marine Biotechnology, 2020)

Influences of ABC transporter and CYP3A4/5 genetic polymorphisms on the pharmacokinetics of lenvatinib in Chinese healthy subjects - Jiaming Li; Xiaoqian Wang; Chen Ning; Zhaoyu Wang; Yao Wang; Ming Zheng; Siliang Zhang; Yang Lu; Yongjie Zhang; Ning Li; Xijing Chen; Di Zhao (European Journal of Clinical Pharmacology, 2020)

Single B cells reveal the antibody responses of rhesus macaques immunized with an inactivated enterovirus D68 vaccine - Huiwen Zheng; Zening Yang; Bingxiang Li; Heng Li; Lei Guo; Jie Song; Dongpei Hou; Nan Li; Jinxi Yang; Qiongwen Wu; Ming Sun; Longding Liu (Archives of Virology, 2020)

Experimental investigation for dynamic instability of coal-rock masses in horizontal section mining of steeply inclined coal seams - Zheng-yi Wang; Lin-ming Dou; Jiang He; An-ye Cao; Xiong-wei Li; Peng-bo Li; Chang-sheng Wu (Arabian Journal of Geosciences, 2020)

Structure and Functional Diversity of Surface Bacterioplankton Communities in an Overwintering Habitat for Large Yellow Croaker, Pseudosciaena crocea, of the Southern East China Sea - Wen Yang; Shi-Zhan Zheng; Shou-Heng Zhou; Li Zhao; Jin-Yong Zhu; Betina Lukwambe; Regan Nicholaus; Cheng-Hua Li; Zhong-Ming Zheng (Frontiers in Marine Science, 2020)

Genome-wide identification of the NPR1-like gene family in Brassica napus and functional characterization of BnaNPR1 in resistance to Sclerotinia sclerotiorum - Zheng Wang; Lu-Yue Ma; Xiao Li; Feng-Yun Zhao; Rehman Sarwar; Jun Cao; Yu-Long Li; Li-Na Ding; Ke-Ming Zhu; Yan-Hua Yang; Xiao-Li Tan (Plant Cell Reports, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Characterization of a Rapeseed Anthocyanin-More Mutant with Enhanced Resistance to Sclerotinia sclerotiorum - Rui Liu; Li-Na Ding; Ming Li; Wei Cao; Yu-Kang Wang; Wei-Jie Wang; Yan-Kun Yu; Zheng Wang; Ke-Ming Zhu; Xiao-Li Tan (Journal of Plant Growth Regulation, 2020)

Correction to: Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)

Optimization of an mRNA vaccine assisted with cyclodextrin-polyethyleneimine conjugates - Lu Tan; Tao Zheng; Man Li; Xiaofang Zhong; Yao Tang; Ming Qin; Xun Sun (Drug Delivery and Translational Research, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Angiotensin Type 1 Receptors and Superoxide Anion Production in Hypothalamic Paraventricular Nucleus Contribute to Capsaicin-Induced Excitatory Renal Reflex and Sympathetic Activation - Yun Qiu; Fen Zheng; Chao Ye; Ai-Dong Chen; Jue-Jin Wang; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (Neuroscience Bulletin, 2020)

Fractionation and chemical structure of dissolved organic matter in the rhizosphere associated with cadmium accumulation in tobacco lines (Nicotiana tabacum L.) - Ming Zhao; Tingxuan Li; Haiying Yu; Xizhou Zhang; Zicheng Zheng; Yongdong Wang; Tao Liu; Dharmendra K. Gupta; Huagang Huang (Environmental Science and Pollution Research, 2020)

Tide-Surge Interaction in the Pearl River Estuary: A Case Study of Typhoon Hato - Peng Zheng; Ming Li; Caixia Wang; Judith Wolf; Xueen Chen; Michela De Dominicis; Peng Yao; Zhan Hu (Frontiers in Marine Science, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

Genetic removal of the CH1 exon leads to the production of hypofunctional heavy chain-only IgG2a in rats - Zhenrong Li; Ming Zhang; Shunan Zheng; Yu Song; Xueqian Cheng; Di Yu; Lijuan Du; Liming Ren; Haitang Han; Yaofeng Zhao (Transgenic Research, 2020)

Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)
Simulated microgravity can significantly affect various cell types and multiple systems of the human body, such as cardiovascular system, skeletal muscle system, and immune system, and is known to cause anemia and loss of electrolyte and fluids. Epidermal stem cells (EpSCs) were cultured in a rotary cell culture system (RCCS) bioreactor to simulate microgravity. The metabolites of EpSCs were identified by liquid chromatography-mass spectrometry (LC-MS). Compared with normal gravity (NG) group, a total of 57 different metabolites of EpSCs were identified ( P < 0.05, VIP > 1), including lipids and lipid-like molecules (51 molecules), amino acids (5 molecules), nucleosides, nucleotides, and analogues (1 molecule). According to the partial least squares discriminant analysis (PLS-DA) score plot, a VIP > 1 and P < 0.05 were obtained for the 57 different metabolites, of which 23 molecules were significantly downregulated and 34 were significantly upregulated in simulated microgravity (SMG) group. These results showed that SMG has a significant impact on different pathways, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that multiple pathways were involved, mainly the amino acid metabolism pathway, lipid metabolism pathway, membrane transport pathway, and cell growth and death pathways. Thus, the metabolic profile of EpSCs was changed under SMG. Exploring the metabolic profile of EpSCs would be helpful to further understand the growth characteristics of EpSCs under SMG, which will provide a new approach to explore the metabolomics mechanism of stress injury and repair trauma under SMG.

(±)-Quassidine K, a pair of cytotoxic bis- β -carboline alkaloid enantiomers from Picrasma quassioides - Xin-Ming Guo; Fei Li; Fang-Fang Zheng; Na-Na Gong; Yan Li; Wen-Zhou Feng; Lin Tian (Natural Product Research, 2020)

Founder effects, post-introduction evolution and phenotypic plasticity contribute to invasion success of a genetically impoverished invader - Zhi-Yong Liao; J. F. Scheepens; Qiao-Ming Li; Wei-Bin Wang; Yu-Long Feng; Yu-Long Zheng (Oecologia, 2020)

Mechanism of CNP-mediated DG-PKC and IP4 signaling pathway in diabetic rats with gastric motility disorder - Hui-Ming Lian; Jun-Yu Guo; Yan Sun; Mo-Han Zhang; Li-Hua Piao; Zheng Jin; Ying-Lan Cai (Molecular Biology Reports, 2020)

Study of multi-objective path planning method for vehicles - Yan Chun Zheng; Juan Wang; Dong Guo; Hai Zhang; Chao Chao Li; Dong Chun Li; Hui Ming Li; Kai Li (Environmental Science and Pollution Research, 2020)

Comprehensive strength deterioration model of compacted loess exposed to drying-wetting cycles - Chang-ming Hu; Yi-li Yuan; Yuan Mei; Xue-yan Wang; Zheng Liu (Bulletin of Engineering Geology and the Environment, 2020)

Lactobacillus jinshani sp. nov., isolated from solid-state vinegar culture of Zhenjiang aromatic vinegar - Yongjian Yu; Xin Li; Junhong Zhang; Li-Juan Chai; Zhen-Ming Lu; Zheng-Hong Xu (Antonie van Leeuwenhoek, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Study on Transient Overvoltage of Offshore Wind Farm Considering Different Electrical Characteristics of Vacuum Circuit Breaker - Zikai Zhou; Yaxun Guo; Xiaofeng Jiang; Gang Liu; Wenhu Tang; Honglei Deng; Xiaohua Li; Ming Zheng (Journal of Marine Science and Engineering, 2019)
For the study of transient overvoltage (TOV) in an offshore wind farm (OWF) collector system caused by switching off vacuum circuit breakers (VCBs), a simplified experimental platform of OWF medium-voltage (MV) cable collector system was established in this paper to conduct switching operation tests of VCB and obtain the characteristic parameters for VCB, especially dielectric strength parameters; also, the effectiveness of the VCB reignition model was verified. Then, PSCAD/EMTDC was used to construct the MV collector system of the OWF, and the effects of normal switching and fault switching on TOV amplitude, steepness, and the total number of reignition of the VCB were studied, respectively, with the experimental parameters and traditional parameters of dielectric strength of the VCB. The simulation results show that when the VCB is at the tower bottom, the overvoltage amplitude generated by the normal switching is the largest, which is 1.83 p.u., and the overvoltage steepness of the fault switching is the largest, up to 142 kV/μs. The overvoltage amplitude and steepness caused by switching off VCB at the tower bottom faultily with traditional parameters are about 2 and 1.5 times of the experimental parameters under the same operating condition.

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Complete genome sequences of five prunus necrotic ringspot virus isolates from Inner Mongolia of China and comparison to other PNRSV isolates around the world - Shuang Song; Ping-ping Sun; Ya-han Chen; Qiang Ma; Xiao-yun Wang; Ming-min Zhao; Zheng-nan Li (Journal of Plant Pathology, 2019)

Modification of the gravity increase method in slope stability analysis - Chang-ming Hu; Yi-li Yuan; Yuan Mei; Xue-yan Wang; Zheng Liu (Bulletin of Engineering Geology and the Environment, 2019)

Advances in plant GDSL lipases: from sequences to functional mechanisms - Li-Na Ding; Ming Li; Wei-Jie Wang; Jun Cao; Zheng Wang; Ke-Ming Zhu; Yan-Hua Yang; Yu-Long Li; Xiao-Li Tan (Acta Physiologiae Plantarum, 2019)

A breeding strategy targeting the secondary gene pool of bread wheat: introgression from a synthetic hexaploid wheat - Ming Hao; Lianquan Zhang; Laibin Zhao; Shoufen Dai; Aili Li; Wuyun Yang; Die Xie; Qingcheng Li; Shunzong Ning; Zehong Yan; Bihua Wu; Xiujin Lan; et al. (Theoretical and Applied Genetics, 2019)

Three BnaIAA7 homologs are involved in auxin/brassinosteroid-mediated plant morphogenesis in rapeseed (Brassica napus L.) - Ming Zheng; Maolong Hu; Hongli Yang; Min Tang; Liang Zhang; Hongfang Liu; Xiaokang Li; Jinglin Liu; Xingchao Sun; Shihang Fan; Jiefu Zhang; William Terzaghi; et al. (Plant Cell Reports, 2019)

Genetic mapping of a major QTL promoting homoeologous chromosome pairing in a wheat landrace - Chaolan Fan; Jiangtao Luo; Shujie Zhang; Meng Liu; Qingcheng Li; Yazhou Li; Lei Huang; Xuejiao Chen; Shunzong Ning; Zhongwei Yuan; Lianquan Zhang; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Dynamics of oxytetracycline and resistance genes in soil under long-term intensive compost fertilization in Northern China - Ming Wu; Hui Han; Xiangnan Zheng; Mohan Bai; Ting Xu; Guo-chun Ding; Ji Li (Environmental Science and Pollution Research, 2019)

Experimental Research on Creep Failure Characteristics of Gypsum Rock Based on Rock Longitudinal Wave Velocity - Zhihe Liu; Huaichang Zheng; Ming Li (Geotechnical and Geological Engineering, 2019)

Isolation and genetic analysis of a nidovirus from crucian carp (Carassius auratus) - Chen Xiao-yu; Zhou Yong; Chen Xin; Zheng Jian; Zeng Xian-dong; Ji Feng; Xu Li-ming (Archives of Virology, 2019)

Pseudofrancisella aestuarii gen. nov., sp. nov., a novel member of the family Francisellaceae isolated from estuarine seawater - Min-Ling Zheng; Jian-Yu Jiao; Lei Dong; Ming-Xian Han; Liang-Hui Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Antiviral activity of aconite alkaloids from Aconitum carmichaelii Debx - Weiming Xu; Min Zhang; Hongwu Liu; Kun Wei; Ming He; Xiangyang Li; Deyu Hu; Song Yang; Yuguo Zheng (Natural Product Research, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Origin of the Mushroom Stone Forest at the southeastern foot of the Little Sangpu Mountain in eastern Guangdong, China: A palaeo-sea-level indicator or not? - Jian-cheng Li; Wei Wang; Yan-ming Zheng (Journal of Mountain Science, 2019)

Reduced carbon use efficiency and increased microbial turnover with soil warming - Jianwei Li; Gangsheng Wang; Melanie A. Mayes; Steven D. Allison; Serita D. Frey; Zheng Shi; Xiao‐Ming Hu; Yiqi Luo; Jerry M. Melillo (Global Change Biology, 2019)
Global soil carbon (C) stocks are expected to decline with warming, and changes in microbial processes are key to this projection. However, warming responses of critical microbial parameters such as carbon use efficiency (CUE) and biomass turnover (rB) are not well understood. Here, we determine these parameters using a probabilistic inversion approach that integrates a microbial‐enzyme model with 22 years of carbon cycling measurements at Harvard Forest. We find that increasing temperature reduces CUE but increases rB, and that two decades of soil warming increases the temperature sensitivities of CUE and rB. These temperature sensitivities, which are derived from decades‐long field observations, contrast with values obtained from short‐term laboratory experiments. We also show that long‐term soil C flux and pool changes in response to warming are more dependent on the temperature sensitivity of CUE than that of rB. Using the inversion‐derived parameters, we project that chronic soil warming at Harvard Forest over six decades will result in soil C gain of

Improving seed germination and oil contents by regulating the GDSL transcriptional level in Brassica napus - Li-Na Ding; Xiao-Juan Guo; Ming Li; Zheng-Li Fu; Su-Zhen Yan; Ke-Ming Zhu; Zheng Wang; Xiao-Li Tan (Plant Cell Reports, 2019)

Design, synthesis, antiproliferative and antibacterial evaluation of quinazolinone derivatives - Hai-Xin Wang; Hai-Ying Liu; Wei Li; Shuai Zhang; Zheng Wu; Xin Li; Cai-Wen Li; Yu-Ming Liu; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Comparison of sea surface wind field measured by HY-2A scatterometer and WindSat in global oceans - Minwei Zheng; Xiao-Ming Li; Jin Sha (Journal of Oceanology and Limnology, 2019)

Transcriptome-Based Identification of a Strong Promoter for Hyper-production of Natamycin in Streptomyces - Kai Wang; Xiao-Fang Liu; Qing-Ting Bu; Yang Zheng; Xin-Ai Chen; Yong-Quan Li; Xu-Ming Mao (Current Microbiology, 2019)

Identification of the complete mitochondrial genome of Garra pingi pingi (Cypriniformes, Cyprinidae) - Yuan-Chao Zou; Mei Chen; Chuan-Jie Qin; Yong-Ming Wang; Rui Li; Ze-Min Qi; Zheng-Yong Wen (Conservation Genetics Resources, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

A new12-membered lactone from the stems of Ficus auriculata - Tai-Ming Shao; Cai-Juan Zheng; Xiao-Bao Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

Cadmium-accumulator straw application alleviates cadmium stress of lettuce (Lactuca sativa) by promoting photosynthetic activity and antioxidative enzyme activities - Yi Tang; Yongdong Xie; Guochao Sun; Huaqiang Tan; Lijin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Xiulan Lv; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2018)

3D FEM simulation of responses of LWD multi-mode resistivity imaging sonde - Zheng-Ming Kang; Shi-Zhen Ke; Xin Li; Jin-Tai Mi; Wei-Ning Ni; Ming-Yu Li (Applied Geophysics, 2018)

Synthesis, antitumor and antimicrobial evaluation of novel 1,3,4-thiadiazole derivatives bearing disulfide bond - Hai-Ying Liu; Hai-Xin Wang; Xin Li; Zheng Wu; Cai-Wen Li; Yu-Ming Liu; Wei Li; Bao-Quan Chen (Medicinal Chemistry Research, 2018)

Effect of Cys, GSH, and pH on Mercury Release from Tibetan Medicine Zuotai, β-HgS, and α-HgS in Artificial Gastrointestinal Juices - Zhiyuan Zheng; Ming Zhang; Yuancan Xiao; Lixin Wei; Cen Li (Biological Trace Element Research, 2018)

Altered Profiles of Gut Microbiota in Klebsiella pneumoniae-Induced Pyogenic Liver Abscess - Nan Chen; Zong-Xin Ling; Tong-Tong Jin; Ming Li; Sheng Zhao; Li-Shuang Zheng; Xin Xi; Lin-Lin Wang; Ying-Ying Chen; Yue-Liang Shen; Li-Ping Zhang; Shao-cong Sun (Current Microbiology, 2018)

Effect of nicotine from tobacco root exudates on chemotaxis, growth, biocontrol efficiency, and colonization by Pseudomonas aeruginosa NXHG29 - Li Ma; Shuai Chao Zheng; Ti Kun Zhang; Zi Yi Liu; Xue Jian Wang; Xing Kui Zhou; Cheng Gang Yang; Jin Ling Duo; Ming He Mo (Antonie van Leeuwenhoek, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Integrated analysis of transcriptomic and metabolomic data reveals critical metabolic pathways involved in rotenoid biosynthesis in the medicinal plant Mirabilis himalaica - Li Gu; Zhong-yi Zhang; Hong Quan; Ming-jie Li; Fang-yu Zhao; Yuan-jiang Xu; Jiang Liu; Man Sai; Wei-lie Zheng; Xiao-zhong Lan (Molecular Genetics and Genomics, 2018)

Outcomes of EC-MPS combined with low-dose tacrolimus in DCD kidney transplantation for high-risk DGF recipients - Li-zi Jiao; Chen-guang Ding; Pu-xun Tian; Xiao-ming Ding; Xiao-ming Pan; He-li Xiang; Xiao-hui Tian; Yang Li; Jin Zheng; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2018)

Association between short-term exposure to ambient air pollution and daily mortality: a time-series study in Eastern China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Different Hippocampus Functional Connectivity Patterns in Healthy Young Adults with Mutations of APP/Presenilin-1/2 and APOEε4 - Li Juan Zheng; Yun Yan Su; Yun Fei Wang; U. Joseph Schoepf; Akos Varga-Szemes; Jonathan Pannell; Xue Liang; Gang Zheng; Guang Ming Lu; Gui Fen Yang; Long Jiang Zhang (Molecular Neurobiology, 2018)

Seasonal variation rather than stand age determines bacterial diversity in the rhizosphere of wolfberry (Lycium barbarum L.) associated with soil degradation - Junhua Zhang; Ming Li; Keli Jia; Guoqi Zheng; Xi-En Long (Journal of Soils and Sediments, 2018)

Effects of air pollution on hospital visits for pneumonia in children: a two-year analysis from China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Responses of soil microbial community to nitrogen fertilizer and precipitation regimes in a semi-arid steppe - Yi-Fei Sun; Ju-Pei Shen; Cui-Jing Zhang; Li-Mei Zhang; Wen-Ming Bai; Ying Fang; Ji-Zheng He (Journal of Soils and Sediments, 2018)

Decomposition of harvest residue needles of different needle ages in a Chinese fir (Cunninghamia lanceolata) plantation - Qingpeng Yang; Renshan Li; Weidong Zhang; Wenhui Zheng; Qingkui Wang; Longchi Chen; Xin Guan; Ming Xu; Silong Wang (Plant and Soil, 2018)

Systematic transcriptome-wide analysis of mRNA–miRNA interactions reveals the involvement of miR-142-5p and its target (FOXO3) in skeletal muscle growth in chickens - Zhenhui Li; Bahareldin Ali Abdalla; Ming Zheng; Xiaomei He; Bolin Cai; Peigong Han; Hongjia Ouyang; Biao Chen; Qinghua Nie; Xiquan Zhang (Molecular Genetics and Genomics, 2018)

Rice straw decomposition affects diversity and dynamics of soil fungal community, but not bacteria - Peng Li; Yongchun Li; Xianqing Zheng; Lina Ding; Feng Ming; Aihu Pan; Weiguang Lv; Xueming Tang (Journal of Soils and Sediments, 2018)

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

A new biphenyl derivative from the mangrove endophytic fungus Phomopsis longicolla HL-2232 - Xiao-Bao Li; Guang-Ying Chen; Rui-Jie Liu; Cai-Juan Zheng; Xin-Ming Song; Chang-Ri Han (Natural Product Research, 2017)

Long-term grazing affects relationships between nitrogen form uptake and biomass of alpine meadow plants - Yu Guo; Li-Ping Liu; Li-Li Zheng; Fei-Hai Yu; Ming-Hua Song; Xian-Zhou Zhang (Plant Ecology, 2017)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis - Pei-wen Zheng; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2017)

Cloning and Stress-Induced Expression Analysis of Calmodulin in the Antarctic Alga Chlamydomonas sp. ICE-L - Ying-ying He; Yi-bin Wang; Zhou Zheng; Fang-ming Liu; Mei-ling An; Xiao-dong He; Chang-feng Qu; Lu-lu Li; Jin-lai Miao (Current Microbiology, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Characteristics and possible formation mechanisms of severe storms in the outer rainbands of Typhoon Mujiga (1522) - Bingyun Wang; Ming Wei; Wei Hua; Yongli Zhang; Xiaohang Wen; Jiafeng Zheng; Nan Li; Han Li; Yu Wu; Jie Zhu; Mingjun Zhang (Journal of Meteorological Research, 2017)

Autophagy response in the liver of pigeon exposed to avermectin - Xian-Song Wang; Ci Liu; Pervez Ahmed Khoso; Weijia Zheng; Ming Li; Shu Li (Environmental Science and Pollution Research, 2017)

Mesenchymal stem cells moderate immune response of type 1 diabetes - Junbi Xv; Qianwen Ming; Xiaotong Wang; Wenjing Zhang; Zheng Li; Shuai Wang; Yulin Li; Lisha Li (Cell and Tissue Research, 2017)

Functional effector memory T cells contribute to protection from superinfection with heterologous simian immunodeficiency virus or simian-human immunodeficiency virus isolates in Chinese rhesus macaques - Ming Sun; Huiwen Zheng; Yingpeng Xie; Bingxiang Li; Haiting Long; Ge Guo; Lei Guo; Jingjing Wang; Ruotong Ning; Yue Li; Longding Liu (Archives of Virology, 2017)

Neuroprotective Effects and Mechanisms of Action of Multifunctional Agents Targeting Free Radicals, Monoamine Oxidase B and Cholinesterase in Parkinson’s Disease Model - Zheng Liu; Wei Cai; Ming Lang; Ruizuo Yan; Zhenshen Li; Gaoxiao Zhang; Pei Yu; Yuqiang Wang; Yewei Sun; Zaijun Zhang (Journal of Molecular Neuroscience, 2017)

Phthalates in plastic bottled non-alcoholic beverages from China and estimated dietary exposure in adults - Ji-Feng Yang; Li-Ming Yang; Li-Ying Zheng; Guang-Guo Ying; Cheng-Bin Liu; Sheng-Lian Luo (Food Additives & Contaminants Part B-Surveillance, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

NFAT5 protects astrocytes against oxygen–glucose–serum deprivation/restoration damage via the SIRT1/Nrf2 pathway - Xun Xia; Bo Qu; Yun-Ming Li; Li-Bin Yang; Ke-Xia Fan; Hui Zheng; Hai-Dong Huang; Jian-Wen Gu; Yong-Qin Kuang; Yuan Ma (Journal of Molecular Neuroscience, 2017)

T cell infiltration is associated with kidney injury in patients with anti-glomerular basement membrane disease - Shui-Yi Hu; Xiao-Yu Jia; Jian-Nan Li; Xin Zheng; Jie Ao; Gang Liu; Zhao Cui; Ming-Hui Zhao (Science China Life Sciences, 2016)

Copper chelation by trientine dihydrochloride inhibits liver RFA-induced inflammatory responses in vivo - Ji-ming Yin; Li-bo Sun; Jia-sheng Zheng; Xin-xin Wang; De-xi Chen; Ning Li (Inflammation Research, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Spatial characteristics of extreme rainfall over China with hourly through 24-hour accumulation periods based on national-level hourly rain gauge data - Yongguang Zheng; Ming Xue; Bo Li; Jiong Chen; Zuyu Tao (Advances in Atmospheric Sciences, 2016)
Hourly rainfall measurements of 1919 national-level meteorological stations from 1981 through 2012 are used to document, for the first time, the climatology of extreme rainfall in hourly through 24-h accumulation periods in China. Rainfall amounts for 3-, 6-, 12- and 24-h periods at each station are constructed through running accumulation from hourly rainfall data that have been screened by proper quality control procedures. For each station and for each accumulation period, the historical maximum is found, and the corresponding 50-year return values are estimated using generalized extreme value theory. Based on the percentiles of the two types of extreme rainfall values among all the stations, standard thresholds separating Grade I, Grade II and Grade III extreme rainfall are established, which roughly correspond to the 70th and 90th percentiles for each of the accumulation periods. The spatial characteristics of the two types of extreme rainfall are then examined for different accumulation periods. The spatial distributions of extreme rainfall in hourly through 6-h periods are more similar than those of 12- and 24-h periods. Grade III rainfall is mostly found over South China, the western Sichuan Basin, along the southern and eastern coastlines, and in the large river basins and plains. There are similar numbers of stations with Grade III extreme hourly rainfall north and south of 30°N, but the percentage increases to about 70% south of 30°N as the accumulation period increases to 24 hours, reflecting richer moisture and more prolonged rain events in southern China. Potential applications of the extreme rainfall climatology and classification standards are suggested at the end.

Recent significant tornadoes in China - Ming Xue; Kun Zhao; Mingjung Wang; Zhaohui Li; Yongguang Zheng (Advances in Atmospheric Sciences, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Influence of the exclusion distance among trees on gap fraction and foliage clumping index of forest plantations - Jun Geng; Jing-Ming Chen; Li-Li Tu; Qing-Jiu Tian; Lei Wang; Ran-Ran Yang; Yan-Jun Yang; Yan Huang; Wei-Liang Fan; Chun-Guang Lv; Guang Zheng (Trees, 2016)

Identification of microRNAs, phasiRNAs and Their Targets in Pineapple - Yun Zheng; Ting Li; Zhenning Xu; Ching Man Wai; Kun Chen; Xiaotuo Zhang; Shengpeng Wang; Bo Ji; Ray Ming; Ramanjulu Sunkar (Tropical Plant Biology, 2016)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

Elevated Neurosteroids in the Lateral Thalamus Relieve Neuropathic Pain in Rats with Spared Nerve Injury - Meng Zhang; Jia Liu; Meng-Meng Zhou; Honghai Wu; Yanning Hou; Yun-Feng Li; Yuxin Yin; Lemin Zheng; Feng-Yu Liu; Ming Yi; You Wan (Neuroscience Bulletin, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Developing a baseline and tools for the future assessment of the ecological status of rivers within the Three Gorges Reservoir catchment, China - Shi-yun Chi; Ju-xiang Hu; Ming Li; Jin-xiu Zheng (Hydrobiologia, 2016)

Phoma glomerata D14: An Endophytic Fungus from Salvia miltiorrhiza That Produces Salvianolic Acid C - Xiuqing Li; Xin Zhai; Zhiheng Shu; Ruifang Dong; Qianliang Ming; Luping Qin; Chengjian Zheng (Current Microbiology, 2016)

Salusin β Within the Nucleus Tractus Solitarii Suppresses Blood Pressure Via Inhibiting the Activities of Presympathetic Neurons in the Rostral Ventrolateral Medulla in Spontaneously Hypertensive Rats - Hong-Bao Li; Yan Lu; Jin-Jun Liu; Yu-Wang Miao; Tian-Zhen Zheng; Qing Su; Jie Qi; Hong Tan; Zu-Yi Yuan; Guo-Qing Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Myricetin protects against diet-induced obesity and ameliorates oxidative stress in C57BL/6 mice - Hong-ming Su; Li-na Feng; Xiao-dong Zheng; Wei Chen (Journal of Zhejiang University-SCIENCE B, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Enhanced butanol production from cassava with Clostridium acetobutylicum by genome shuffling - Shu-Bo Li; Yi Qian; Zheng-Wu Liang; Yuan Guo; Mou-Ming Zhao; Zong-Wen Pang (World Journal of Microbiology and Biotechnology, 2016)

Procalcitonin Is a Stronger Predictor of Long-Term Functional Outcome and Mortality than High-Sensitivity C-Reactive Protein in Patients with Ischemic Stroke - Chao Wang; Li Gao; Zhi-Guo Zhang; Yu-Qian Li; Yan-Long Yang; Tao Chang; Long-Long Zheng; Xing-Ye Zhang; Ming-Hao Man; Li-Hong Li (Molecular Neurobiology, 2016)

Petrology, geochemistry, and geochronology of mafic rocks from the Taoxinghu Devonian ophiolite, LongmuCo–Shuanghu–Lancang suture zone, northern Tibet: evidence for an intra-oceanic arc–basin system - Yan-Wang Wu; Cai Li; Meng-Jing Xu; Chao-Ming Xie; Ming Wang; Sheng-Qing Xiong; Zheng-Guo Fan (International Geology Review, 2016)

Tomographic inversion of near-surface Q factor by combining surface and cross-hole seismic surveys - Guo-Fa Li; Hao Zheng; Wen-Liang Zhu; Ming-Chao Wang; Tong-Li Zhai (Applied Geophysics, 2016)

Regional magnetic anomaly fields: 3D Taylor polynomial and surface spline models - Yan Feng; Yong Jiang; Yi Jiang; Zheng Li; Jin Jiang; Zhong-Wei Liu; Mei-Chen Ye; Hong-Sheng Wang; Xiu-Ming Li (Applied Geophysics, 2016)

Isolation, diversity and acetylcholinesterase inhibitory activity of the culturable endophytic fungi harboured in Huperzia serrata from Jinggang Mountain, China - Ya Wang; Zheng Lai; Xi-Xi Li; Ri-Ming Yan; Zhi-Bin Zhang; Hui-Lin Yang; Du Zhu (World Journal of Microbiology and Biotechnology, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Remanufacturing cathode from end-of-life of lithium-ion secondary batteries by Nd:YAG laser radiation - Wei-wei Liu; Heng Zhang; Li-hong Liu; Xiao-chuan Qing; Zi-jue Tang; Ming-zheng Li; Jin-song Yin; Hong-chao Zhang (Clean Technologies and Environmental Policy, 2016)

Expression of Shewanella frigidimarina fatty acid metabolic genes in E. coli by CRISPR/cas9-coupled lambda Red recombineering - Jun Xia; Ling Wang; Jian-bo Zhu; Cheng-jun Sun; Ming-gang Zheng; Li Zheng; Ying-hua Lou; Lei Shi (Biotechnology Letters, 2016)

Association between the FTOrs8050136 polymorphism and cancer risk: a meta-analysis - Jian Zhao; Xiaoyi Huang; Mingyuan Yang; Ming Li; Jianming Zheng (Familial Cancer, 2016)

Characterization and expression analysis of the expansin gene NnEXPA1 in lotus Nelumbo nucifera - Neng Cheng; Xiao-Fei Zeng; Xing-Fei Zheng; Ying Diao; You-Wei Wang; Ke-Qiang Xie; Ming-Quan Zhou; Zhong-Li Hu (Biologia, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Radial anisotropy in the crust beneath the northeastern Tibetan Plateau from ambient noise tomography - Jing Tan; Hongyi Li; Xinfu Li; Ming Zhou; Longbin Ouyang; Sanjian Sun; Dan Zheng (Journal of Earth Science, 2015)

A two‐domain protein triggers heat shock pathway and necrosis pathway both in model plant and nematode - Lifang Ruan; Huihui Wang; Ge Cai; Donghai Peng; Hua Zhou; Jinshui Zheng; Lei Zhu; Xixi Wang; Haoquan Yu; Seng Li; Ce Geng; Ming Sun (Environmental Microbiology, 2015)
Summary The entomopathogen B acillus thuringiensis is equipped with multiple virulent factors. The genome sequence of B . thuringiensis YBT 1520 revealed the presence of a two‐domain protein named Nel which is composed of a necrosis‐inducing phytophthora protein 1‐like domain found in phytopathogens and a ricin B ‐like lectin domain. The merging of two distantly related domains is relatively rare. Nel induced necrosis and pathogen‐triggered immunity ( PTI ) on model plants. The Nel also exhibited inhibition activity to nematode. Microscopic observation showed that the toxicity of Nel to nematodes targets the intestine. Quantitative proteomics revealed that Nel stimulated the host defence. The Nel thus possesses dual roles, as both toxin and elicitor. Remarkably, the Nel protein triggered a similar response, induction of the heat shock pathway and the necrosis pathway, in both model plants and nematodes. The unusual ability of Nel to function across kingdom suggests a highly conserved mechanism in eukaryotes that predates the divergence of plants and animal. It is also speculated that the two‐domain protein is the result of horizontal gene transfer ( HGT) between phytopathogens and entomopathogens. Our results provide an example that HGT occurs between members of different species or even genera with lower frequency are particularly important for evolution of new bacterial pathogen lineages with new virulence. B acillus thuringiensis occupies the same ecological niches, plant and soil, as phytopathogens, providing the opportunity for gene exchange.

Plasticity in nitrogen form uptake and preference in response to long-term nitrogen fertilization - Ming-Hua Song; Li-Li Zheng; Katharine N. Suding; Tan-Feng Yin; Fei-Hai Yu (Plant and Soil, 2015)

Sediment delivery across multiple spatio-temporal scales in an agriculture watershed of the Chinese Loess Plateau - Ming-guo Zheng; Run-kui Li; Ji-jun He; Ming Cui (Journal of Mountain Science, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Identification of volatile and softening-related genes using digital gene expression profiles in melting peach - Xiong-wei Li; Jun Jiang; Li-ping Zhang; Yi Yu; Zheng-wen Ye; Xiu-min Wang; Jing-yi Zhou; Ming-liang Chai; Hui-qin Zhang; Pere Arús; Hui-juan Jia; Zhong-shan Gao (Tree Genetics & Genomes, 2015)

NMDAR-Mediated Hippocampal Neuronal Death is Exacerbated by Activities of ASIC1a - Su Gao; Yang Yu; Zhi-Yuan Ma; Hui Sun; Yong-Li Zhang; Xing-Tao Wang; Chaoyun Wang; Wei-Ming Fan; Qing-Yin Zheng; Chun-Lei Ma (Neurotoxicity Research, 2015)

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence - Gang-ming Zhan; Fu-ping Wang; Huai-yong Luo; Shu-chang Jiang; Wen-ming Zheng; Li-li Huang; Zhen-sheng Kang (Journal of Zhejiang University-SCIENCE B, 2015)

Proteome analysis of pear reveals key genes associated with fruit development and quality - Jia Ming Li; Xiao San Huang; Lie Ting Li; Dan Man Zheng; Cheng Xue; Shao Ling Zhang; Jun Wu (Planta, 2015)

TSC1 R509X Mutation in a Chinese Family with Tuberous Sclerosis Complex - Yu Zhang; Jing Gan; Zheng Pu; Ming ming Xu; Li feng Wang; Yu hua Li; Zhen guo Liu (NeuroMolecular Medicine, 2015)

Impacts of the Wenchuan earthquake on tree mortality and biomass carbon stock - Shuai Qiu; Ming Xu; Yunpu Zheng; Renqiang Li; Michelle Hang Gi Wong; Liyun Zhang; Lixiang Liu; Changhong Lai; Wen Zhang (Natural Hazards, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Different influences of field aging on nickel toxicity to Folsomia candida in two types of soil - Yu-Rong Liu; Jing Li; Ji-Zheng He; Yi-Bing Ma; Yuan-Ming Zheng (Environmental Science and Pollution Research, 2015)

Soil pH determines the alpha diversity but not beta diversity of soil fungal community along altitude in a typical Tibetan forest ecosystem - Jun-Tao Wang; Yuan-Ming Zheng; Hang-Wei Hu; Li-Mei Zhang; Jing Li; Ji-Zheng He (Journal of Soils and Sediments, 2015)

Molecular and serological evidence for Seoul virus in rats (Rattus norvegicus) in Zhangmu, Tibet, China - Tingsong Hu; Quanshui Fan; Xiaobing Hu; Bo Deng; Gang Chen; Liangqi Gu; Ming Li; Ying Zheng; Guihong Yuan; Wei Qiu; Xiaomei Jiang; Fuqiang Zhang (Archives of Virology, 2015)

Mutation breeding of high 4-androstene-3,17-dione-producing Mycobacterium neoaurum ZADF-4 by atmospheric and room temperature plasma treatment - Chao Liu; Xian Zhang; Zhi-ming Rao; Ming-long Shao; Le-le Zhang; Dan Wu; Zheng-hong Xu; Hui Li (Journal of Zhejiang University-SCIENCE B, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

The CD8α gene in duck (Anatidae): cloning, characterization, and expression during viral infection - Qi Xu; Yang Chen; Wen Ming Zhao; Zheng Yang Huang; Xiu Jun Duan; Yi Yu Tong; Yang Zhang; Xiu Li; Guo Bin Chang; Guo Hong Chen (Molecular Biology Reports, 2015)

Cloning and characterization of the genes encoding the small and large subunit of the ADP-glucose pyrophosphorylase in lotus (Nelumbo nucifera Gaertn) - Neng Cheng; Xiao-Fei Zeng; Xing-Fei Zheng; Ying Diao; You-Wei Wang; Ke-Qiang Xie; Ming-Quan Zhou; Zhong-Li Hu (Acta Physiologiae Plantarum, 2015)

KIM-1 and NGAL as biomarkers of nephrotoxicity induced by gentamicin in rats - Qi-hui Luo; Meng-lu Chen; Feng-jiao Sun; Zheng-li Chen; Ming-yang Li; Wen Zeng; Li Gong; An-chun Cheng; Xi Peng; Jing Fang; Li Tang; Yi Geng (Molecular and Cellular Biochemistry, 2014)

Detection and Analysis of 12 Heavy Metals in Blood and Hair Sample from a General Population of Pearl River Delta Area - Jiqiang Li; Dongzhi Cen; Donglan Huang; Xufeng Li; Jiajun Xu; Shilin Fu; Rui Cai; Xiaocong Wu; Ming Tang; Yao Sun; Jiren Zhang; Jingfen Zheng (Cell Biochemistry and Biophysics, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Expression of bkt and bch genes from Haematococcus pluvialis in transgenic Chlamydomonas - KaiJing Zheng; ChaoGang Wang; Ming Xiao; Jun Chen; JianCheng Li; ZhangLi Hu (Science China Life Sciences, 2014)

Combined effects of the BDNF rs6265 (Val66Met) polymorphism and environment risk factors on psoriasis vulgaris - Cheng Quan; Kun-Ju Zhu; Chi Zhang; Zhong Liu; Huan Liu; Cheng-Yao Zhu; Ke-Shen Li; Yi-Ming Fan; Jie Zheng (Molecular Biology Reports, 2014)

The expression profile and promoter analysis of β-N-acetylglucosaminidases in the silkworm Bombyx mori - Yuan-fen Zhai; Ming-xia Huang; Yu Wu; Guo-dong Zhao; Jie Du; Bing Li; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Assessment of chlorpyrifos exposure and absorbed daily doses among infants living in an agricultural area of the Province of Jiangsu, China - Ping Liu; Chun-hua Wu; Xiu-li Chang; Xiao-juan Qi; Ming-lan Zheng; Zhi-jun Zhou (International Archives of Occupational and Environmental Health, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Molecular cloning and expression analysis of ferritin, heavy polypeptide 1 gene from duck (Anas platyrhynchos) - Qi Xu; Yang Chen; Yang Zhang; Yi Yu Tong; Zheng Yang Huang; Wen Ming Zhao; Xiu Jun Duan; Xiu Li; Guo Bin Chang; Guo Hong Chen (Molecular Biology Reports, 2014)

Evaluation of geographic distribution of high-molecular-weight glutenin subunits (HMW-GS) in wild and cultivated Triticum species - Wei Li; Yu-Ming Wei; Li-Li Xu; An-Jun Liu; Yu-Zhen Sheng; Zhi-En Pu; Guo-Yue Cheng; You-Liang Zheng (Genetic Resources and Crop Evolution, 2014)

A pre-breeding screening program for transgenic boars based on fluorescence in situ hybridization assay - Gerelchimeg Bou; Mingju Sun; Ming Lv; Jiang Zhu; Hui Li; Juan Wang; Lu Li; Zhongfeng Liu; Zhong Zheng; Wenteng He; Qingran Kong; Zhonghua Liu (Transgenic Research, 2014)

Ferulic acid prevents liver injury and increases the anti-tumor effect of diosbulbin B in vivo - Jun-ming Wang; Yu-chen Sheng; Li-li Ji; Zheng-tao Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Expression analysis and RNA interference of BmCarE-10 gene from Bombyx mori - Guo-dong Zhao; Ming-xia Huang; Yi-ling Zhang; Xue-cen Wang; Jie Du; Bing Li; Yu-hua Chen; Ya-xiang Xu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Deregulation of microRNA expression in thyroid tumors - Zi-ming Yuan; Zhi-li Yang; Qi Zheng (Journal of Zhejiang University-SCIENCE B, 2014)

Genetic diversity analysis of yams (Dioscorea spp.) cultivated in China using ISSR and SRAP markers - Zhi Gang Wu; Xiao Xia Li; Xin Chun Lin; Wu Jiang; Zheng Ming Tao; Nitin Mantri; Chuan Yin Fan; Xiao Qing Bao (Genetic Resources and Crop Evolution, 2014)

Overexpression of NgAUREO1, the gene coding for aurechrome 1 from Nannochloropsis gaditana, into Saccharomyces cerevisiae leads to a 1.6-fold increase in lipid accumulation - Yi-jiang Huang; Ling Wang; Ming-gang Zheng; Li Zheng; Yan-li Tong; Yan Li (Biotechnology Letters, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Temporal change of runoff and sediment load and their differential response to human activities: A case study for a well-vegetated mountain watershed of southern China - Ming-guo Zheng; Li-ying Sun; Ming Yan (Journal of Mountain Science, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Linkage between community diversity of sulfate-reducing microorganisms and methylmercury concentration in paddy soil - Yu-Rong Liu; Yuan-Ming Zheng; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Cloning, expression and stress-respondent transcription of long-chain acyl-coenzyme A synthetase cDNA gene of Nannochloropsis gaditana and its involvement in the biosynthesis of eicosapentaenoic and decosahexaenoic acids - Ming-gang Zheng; Yi-jiang Huang; Li Zheng; Zhong-tao Sun; Ling Wang (Biotechnology Letters, 2014)

Isolation and characterization of fifteen microsatellite loci in the Tibetan fox (Vulpes ferrilata) - MIN LI; XIAO MING WANG; WEI BIN JIANG; PAN YU HUA; ZHENG HUAN WANG (Journal of Genetics, 2013)

The short chain cell-permeable ceramide (C6) restores cell apoptosis and perifosine sensitivity in cultured glioblastoma cells - Li-sen Qin; Zheng-quan Yu; Shi-ming Zhang; Guan Sun; Jian Zhu; Jin Xu; Jun Guo; Lin-shan Fu (Molecular Biology Reports, 2013)

Green-revertible Chlorina 1 (grc1) is required for the biosynthesis of chlorophyll and the early development of chloroplasts in rice - Jieqin Li; Yihua Wang; Juntao Chai; Lihua Wang; Chunming Wang; Wuhua Long; Di Wang; Yunlong Wang; Ming Zheng; Cheng Peng; Mei Niu; Jianmin Wan (Journal of Plant Biology, 2013)

Genome-Wide Analysis of MicroRNAs in Sacred Lotus, Nelumbo nucifera (Gaertn) - Yun Zheng; Guru Jagadeeswaran; Kanchana Gowdu; Nian Wang; Shaohua Li; Ray Ming; Ramanjulu Sunkar (Tropical Plant Biology, 2013)

Synthesis and potential antibacterial activity of new rhodanine-3-acetic acid derivatives - Jing Miao; Chang-Ji Zheng; Liang-Peng Sun; Ming-Xia Song; Li-Li Xu; Hu-Ri Piao (Medicinal Chemistry Research, 2013)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Identification of Major QTL for Waterlogging Tolerance Using Genome-Wide Association and Linkage Mapping of Maize Seedlings - Xiaobo Zhang; Bin Tang; Feng Yu; Liu Li; Ming Wang; Yadong Xue; Zuxin Zhang; Jianbing Yan; Bing Yue; Yonglian Zheng; Fazhan Qiu (Plant Molecular Biology Reporter, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Visual and Olfactory Responses of Seven Butterfly Species During Foraging - Yu-Chong Tang; Cheng-Li Zhou; Xiao-Ming Chen; Hua Zheng (Journal of Insect Behavior, 2013)

Synthesis and in vitro antitumor activity of 1-(3-dimethylamino)propyl indolin-2-one derivatives - Kai Lv; Li-Li Wang; Xin-Bo Zhou; Ming-Liang Liu; Hong-Ying Liu; Zhi-Bing Zheng; Song Li (Medicinal Chemistry Research, 2013)

Enhancing production of a 24-membered ring macrolide compound by a marine bacterium using response surface methodology - Hua Chen; Mian-bin Wu; Zheng-jie Chen; Ming-lu Wang; Jian-ping Lin; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of super absorbent polymers on soil microbial properties and Chinese cabbage (Brassica chinensis) growth - Xi Li; Ji-Zheng He; Yu-Rong Liu; Yuan-Ming Zheng (Journal of Soils and Sediments, 2013)

Succession of plant and soil microbial communities with restoration of abandoned land in the Loess Plateau, China - Jun-Jian Li; Yuan-Ming Zheng; Jun-Xia Yan; Hong-Jian Li; Ji-Zheng He (Journal of Soils and Sediments, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

The TRIMCyp genotype in four species of macaques in China - Chang-Qing Yu; Lei Na; Xiao-Ling Lv; Jian-Dong Liu; Xiao-Ming Liu; Fang Ji; Yong-Hui Zheng; Hong-Li Du; Xian-Gang Kong; Jian-Hua Zhou (Immunogenetics, 2013)

Isolation and characterization of a stress responsive small GTP-binding protein AhRabG3b in peanut (Arachis hypogaea L.) - Jiong-Ming Sui; Rui Li; Qian-Cheng Fan; Lin Song; Chun-Hua Zheng; Jing-Shan Wang; Li-Xian Qiao; Shan-Lin Yu (Euphytica, 2013)

Meta-analysis of QTL associated with tolerance to abiotic stresses in barley - Wei-Tao Li; Chunji Liu; Ya-Xi Liu; Zhi-En Pu; Shou-Fen Dai; Ji-Rui Wang; Xiu-Jin Lan; You-Liang Zheng; Yu-Ming Wei (Euphytica, 2013)

ATP-binding cassette transporter A1 R219K polymorphism and coronary artery disease in Chinese population: a meta-analysis of 5,388 participants - Yan-yan Li; Hui Zhang; Xiao-yi Qin; Xin-zheng Lu; Bing Yang; Ming-long Chen (Molecular Biology Reports, 2012)

Molecular diversity of restriction enzyme sites, Indels and upstream open reading frames (uORFs) of 5′ untransalted regions (UTRs) of Waxy genes in Triticum L. and Aegilops L. species - Wei Li; Zhen Gao; Wei Xiao; Yu-Ming Wei; Ya-Xi Liu; Guo-Yue Chen; Zhi-En Pu; Hua-Ping Chen; You-Liang Zheng (Genetic Resources and Crop Evolution, 2012)

Reduction of distortion and improvement of efficiency for gridding of scattered gravity and magnetic data - Chen Zhang; Chang-Li Yao; Yong-Mao Xie; Yuan-Man Zheng; Hu-Liang Guan; Dong-Ming Hong (Applied Geophysics, 2012)

Synthesis, crystal structure and biological activity of novel anthranilic diamide insecticide containing alkyl ether group - Yu Zhao; Li-ping Xu; Jun Tong; Yong-qiang Li; Li-xia Xiong; Fang Li; Li-na Peng; Zheng-ming Li (Molecular Diversity, 2012)

Digital pH Fluorescent Sensing Shown by Small Organic Molecules - Ming-Hua Zheng; Mi-Mi Zhang; Hui-Hai Li; Jing-Yi Jin (Journal of Fluorescence, 2012)

RETRACTED ARTICLE: A 2-D DIGE analysis of simulated acid rain-responsive proteins in Pinus massoniana needles - Ting-Wu Liu; Wen-Jun Hu; Xiao-Qin Wang; Li Niu; Bin Fu; Fei-Hua Wu; Zhen-Ming Pei; Hai-Lei Zheng (Trees, 2012)

Traditional Chinese medicines benefit to nonalcoholic fatty liver disease: a systematic review and meta-analysis - Ke-Qing Shi; Yu-Chen Fan; Wen-Yue Liu; Ling-Fei Li; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

VEGF upregulates VEGF receptor-2 on human outer root sheath cells and stimulates proliferation through ERK pathway - Wei Li; Zhong-Fa Lu; Xiao-Yong Man; Chun-Ming Li; Jiong Zhou; Jia-Qi Chen; Xiao-Hong Yang; Xian-Jie Wu; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2012)

Involvement of p38MAPK/NF-κB Signaling Pathways in Osteoblasts Differentiation in Response to Mechanical Stretch - Liang Wang; Jian-yu Li; Xi-zheng Zhang; Lu Liu; Zong-ming Wan; Rui-xin Li; Yong Guo (Annals of Biomedical Engineering, 2012)

Highly Sensitive Detection of Residual Chlorpromazine Hydrochloride with Solid Substrate Room Temperature Phosphorimetry - Jia-Ming Liu; Li-ping Lin; Xin-Xing Wang; Xuan Lin; Ping Zhou; Shao-Qin Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Improvement of d-lactate productivity in recombinant Escherichia coli by coupling production with growth - Li Zhou; Kang-Ming Tian; Dan-Dan Niu; Wei Shen; Gui-Yang Shi; Suren Singh; Zheng-Xiang Wang (Biotechnology Letters, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Apigenin enhances the cytotoxic effects of tumor necrosis factor-related apoptosis-inducing ligand in human rheumatoid arthritis fibroblast-like synoviocytes - Qing-wen Sun; Song-min Jiang; Ke Yang; Jian-ming Zheng; Li Zhang; Wei-dong Xu (Molecular Biology Reports, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Synthesis, structure, and biological activity of novel (oxdi/tri)azoles derivatives containing 1,2,3-thiadiazole or methyl moiety - Xing-Hai Liu; Li Pan; Jian-Quan Weng; Cheng-Xia Tan; Yong-Hong Li; Bao-Lei Wang; Zheng-Ming Li (Molecular Diversity, 2012)

Mapping stripe rust resistance gene YrSph derived from Tritium sphaerococcum Perc. with SSR, SRAP, and TRAP markers - Shi-Sheng Chen; Guo-Yue Chen; Hua Chen; Yu-Ming Wei; Wei Li; Ya-Xi Liu; Deng-Cai Liu; Xiu-Jin Lan; You-Liang Zheng (Euphytica, 2012)

The Group III Two-Component Histidine Kinase AlHK1 is Involved in Fungicides Resistance, Osmosensitivity, Spore Production and Impacts Negatively Pathogenicity in Alternaria longipes - Yi Yong Luo; Jin Kui Yang; Ming Liang Zhu; Chen Jian Liu; Hai Yan Li; Ze Bao Lu; Wen Zheng Pan; Zhong Hua Zhang; Wei Bi; Ke Qin Zhang (Current Microbiology, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Polymorphic variations in manganese superoxide dismutase (MnSOD), glutathione peroxidase-1 (GPX1), and catalase (CAT) contribute to elevated plasma triglyceride levels in Chinese patients with type 2 diabetes or diabetic cardiovascular disease - Hong Chen; Ming Yu; Ming Li; Ruie Zhao; Qihan Zhu; Wenrui Zhou; Ming Lu; Yufeng Lu; Taishan Zheng; Jiamei Jiang; Weijing Zhao; Kunsan Xiang; et al. (Molecular and Cellular Biochemistry, 2012)

Different sperm sources and parameters can influence intracytoplasmic sperm injection outcomes before embryo implantation - Yue-hong Lu; Hui-juan Gao; Bai-jia Li; Ying-ming Zheng; Ying-hui Ye; Yu-li Qian; Chen-ming Xu; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

Response of denitrification genes nirS, nirK, and nosZ to irrigation water quality in a Chinese agricultural soil - Zhi-Feng Zhou; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2011)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Chlamydial Antiapoptotic Activity Involves Activation of the Raf/MEK/ERK Survival Pathway - Kun Du; Qun Zheng; Ming Zhou; LiSha Zhu; Biao Ai; Li Zhou (Current Microbiology, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Aluminum regulates oxalate secretion and plasma membrane H+-ATPase activity independently in tomato roots - Jian Li Yang; Xiao Fang Zhu; You Xiang Peng; Cheng Zheng; Feng Ming; Shao Jian Zheng (Planta, 2011)

Tissue-specific and expression of porcine growth hormone gene in BAC transgenic mice - Jia Tong; Simon G. Lillico; Ming Jun Bi; Tong Qing; Xiao Fang Liu; YuanYuan Wang; Min Zheng; Meili Wang; Yun Ping Dai; C. Bruce A. Whitelaw; Ning Li (Transgenic Research, 2011)

Genetic diversity and domestication history of African rice (Oryza glaberrima) as inferred from multiple gene sequences - Zhi-Ming Li; Xiao-Ming Zheng; Song Ge (Theoretical and Applied Genetics, 2011)

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo - Qiang Xu; Zhao-xu Li; Hui-qin Peng; Zheng-wang Sun; Rui-lin Cheng; Zhao-ming Ye; Wei-xu Li (Journal of Zhejiang University-SCIENCE B, 2011)

Pigment epithelium-derived factor plays an inhibitory role in proliferation and migration of HaCaT cells - Chun-Ming Li; Wei Li; Xiao-Yong Man; Jiong Zhou; Jia-Qi Chen; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2011)

Evaluation of Genetic Manipulation Strategies on d-Lactate Production by Escherichia coli - Li Zhou; Zhi-Rui Zuo; Xian-Zhong Chen; Dan-Dan Niu; Kang-Ming Tian; Bernard A. Prior; Wei Shen; Gui-Yang Shi; Suren Singh; Zheng-Xiang Wang (Current Microbiology, 2011)

Whole genome amplification in preimplantation genetic diagnosis - Ying-ming Zheng; Ning Wang; Lei Li; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Development of a large-scale isolation chamber system for the safe and humane care of medium-sized laboratory animals harboring infectious diseases - Xin Pan; Jian-cheng Qi; Ming Long; Hao Liang; Xiao Chen; Han Li; Guang-bo Li; Hao Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Identification, localization, and characterization of putative USP genes in barley - Wei-Tao Li; Yu-Ming Wei; Ji-Rui Wang; Chun-Ji Liu; Xiu-Jin Lan; Qian-Tao Jiang; Zhi-En Pu; You-Liang Zheng (Theoretical and Applied Genetics, 2010)

Responses of Queenright and Queenless Workers of Apis Cerana to 9-keto-2(E)-decenoic Acid, a Pheromonal Constituent of the Mandibular Gland - Ken Tan; Zheng-Wei Wang; Hua Li; Ming-Xian Yang; Christian W. W. Pirk; H. Randall Hepburn; Sarah E. Radloff (Journal of Chemical Ecology, 2010)

Nitrous oxide and nitric oxide emissions from an irrigated cotton field in Northern China - Chunyan Liu; Xunhua Zheng; Zaixing Zhou; Shenghui Han; Yinghong Wang; Kai Wang; Wangguo Liang; Ming Li; Deli Chen; Zhiping Yang (Plant and Soil, 2010)

Synthesis, Characterization, DNA Binding Properties, Fluorescence Studies and Antioxidant Activity of Transition Metal Complexes with Hesperetin-2-hydroxy Benzoyl Hydrazone - Yong Li; Zheng-Yin Yang; Ming-Fang Wang (Journal of Fluorescence, 2010)

Effects of mercury on the activity and community composition of soil ammonia oxidizers - Yu-Rong Liu; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

Cr(III) oxidation coupled with Mn(II) bacterial oxidation in the environment - Ji-Zheng He; You-Ting Meng; Yuan-Ming Zheng; Li-Mei Zhang (Journal of Soils and Sediments, 2010)

Enhancement of Sodium Caprate on Intestine Absorption and Antidiabetic Action of Berberine - Xiao-Yan Lv; Jing Li; Ming Zhang; Chun-Mei Wang; Zheng Fan; Chun-yan Wang; Li Chen (AAPS PharmSciTech, 2010)

Quantitative profiles of the mRNAs of ER-α and its novel variant ER-α36 in breast cancers and matched normal tissues - Yi Zheng; Jing Zhang; Zhen-zhen Xu; Jian-ming Sheng; Xiao-chen Zhang; Hao-hao Wang; Xiao-dong Teng; Xiao-jiao Liu; Jiang Cao; Li-song Teng (Journal of Zhejiang University-SCIENCE B, 2010)

Association of LT-α Ala252Gly gene polymorphism and the genetic predisposition of coronary heart disease in Chinese - Hanxiang Gao; Zheng Zhang; Jin Zhang; Nan Zhao; Qiang Li; Ming Bai (Molecular Biology Reports, 2010)

Molecular cloning, functional analysis and localization of a novel gene encoding polygalacturonase-inhibiting protein in Chorispora bungeana - Cuixia Di; Ming Li; Feng Long; Muqun Bai; Yajie liu; Xiaolin Zheng; Shijian Xu; Yun Xiang; Zhenglong Sun; Lizhe An (Planta, 2009)

Adaptation of the externally feeding bug Elasmucha necopinata (Hemiptera: Acanthosomatidae) to its fig host - Guang-Chang Ma; Hao-Yuan Hu; Li-Ming Niu; Yue-Guan Fu; Zheng-Qiang Peng; Wen-Jun Bu; Da-Wei Huang (Symbiosis, 2009)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Isolation and characterization of microsatellite markers for Primulina tabacum, a critically endangered perennial herb - Zheng-Feng Wang; Hai Ren; Qian-Mei Zhang; Wan-Hui Ye; Kai-Ming Liang; Zhong-Chao Li (Conservation Genetics, 2009)

Molecular Cloning and Expression of cDNA Encoding the Cysteine Proteinase Inhibitor from Upland Cotton - Ming-feng Jiang; Sheng-wei Li; Min Chen; Ying-fan Cai; Yong-fang Xie; Biao Li; Quan Sun; Huai-zhong Jiang; Zheng Pan; Yun-ling Gao; You-Lu Yuan; Yu-zheng Shi (Journal of Plant Biology, 2009)

Gene mapping and expression analysis of a novel mutantreproduce organs absent (roa) in rice - Nan Wang; Xian-Chun Sang; Yun-Feng Li; Ying-Hua Ling; Fang-Ming Zhao; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

Hydraulic pressure inducing renal tubular epithelial-myofibroblast transdifferentiation in vitro - Fei-yan Li; Xi-sheng Xie; Jun-ming Fan; Zi Li; Jiang Wu; Rong Zheng (Journal of Zhejiang University-SCIENCE B, 2009)

ATG16L1 T300A polymorphism and Crohn’s disease susceptibility: evidence from 13,022 cases and 17,532 controls - Hai-Feng Zhang; Li-Xin Qiu; Yu Chen; Wa-Li Zhu; Chen Mao; Li-Guang Zhu; Ming-Hua Zheng; Yan Wang; Lei Lei; Jian Shi (Human Genetics, 2009)

Relationships among Avena species as revealed by consensus chloroplast simple sequence repeat (ccSSR) markers - Wei-Tao Li; Yuan-Ying Peng; Yu-Ming Wei; Bernard R. Baum; You-Liang Zheng (Genetic Resources and Crop Evolution, 2009)

FAS −1,377 G/A polymorphism is associated with cancer susceptibility: evidence from 10,564 cases and 12,075 controls - Li-Xin Qiu; Jian Shi; Hui Yuan; Xin Jiang; Kai Xue; Hai-Feng Pan; Jin Li; Ming-Hua Zheng (Human Genetics, 2009)

Genetic diversity of HMW glutenin subunits in diploid, tetraploid and hexaploid Triticum species - Li-Li Xu; Wei Li; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2009)

The manganese superoxide dismutase Val16Ala polymorphism is associated with decreased risk of diabetic nephropathy in Chinese patients with type 2 diabetes - Limei Liu; Taishan Zheng; Niansong Wang; Feng Wang; Ming Li; Jiamei Jiang; Ruie Zhao; Lifang Li; Weijing Zhao; Qihan Zhu; Weiping Jia (Molecular and Cellular Biochemistry, 2009)

Resistance gene analog polymorphisms (RGAPs) in wild emmer wheat (Triticum dicoccoides) and their ecological associations - Pan Dong; Yu-Ming Wei; Guo-Yue Chen; Wei Li; Eviatar Nevo; You-Liang Zheng (Genetic Resources and Crop Evolution, 2009)

The involvement of sortase A in high virulence of STSS-causing Streptococcus suis serotype 2 - Changjun Wang; Ming Li; Youjun Feng; Feng Zheng; Yaqing Dong; Xiuzhen Pan; Gong Cheng; Ruiping Dong; Dan Hu; Xiaodan Feng; Junchao Ge; Di Liu; et al. (Archives of Microbiology, 2009)

Abundance and community composition of methanotrophs in a Chinese paddy soil under long-term fertilization practices - Yong Zheng; Li-Mei Zhang; Yuan-Ming Zheng; Hongjie Di; Ji-Zheng He (Journal of Soils and Sediments, 2008)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Occurrence of entomopathogenic fungi in migratory alate aphids in Yunnan Province of China - Bin Chen; Zheng Yue Li; Ming Guang Feng (BioControl, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Quantitative analyses of the abundance and composition of ammonia‐oxidizing bacteria and ammonia‐oxidizing archaea of a Chinese upland red soil under long‐term fertilization practices - Ji‐zheng He; Ju‐pei Shen; Li‐mei Zhang; Yong‐guan Zhu; Yuan‐ming Zheng; Ming‐gang Xu; Hongjie Di (Environmental Microbiology, 2007)

Quantitative analyses of the abundance and composition of ammonia‐oxidizing bacteria and ammonia‐oxidizing archaea of a Chinese upland red soil under long‐term fertilization practices - Ji‐zheng He; Ju‐pei Shen; Li‐mei Zhang; Yong‐guan Zhu; Yuan‐ming Zheng; Ming‐gang Xu; Hongjie Di (Environmental Microbiology, 2007)
Summary The abundance and composition of soil ammonia‐oxidizing bacteria (AOB) and ammonia‐oxidizing archaea (AOA) were investigated by using quantitative real‐time polymerase chain reaction, cloning and sequencing approaches based on amoA genes. The soil, classified as agri‐udic ferrosols with pH (H 2 O) ranging from 3.7 to 6.0, was sampled in summer and winter from long‐term field experimental plots which had received 16 years continuous fertilization treatments, including fallow (CK0), control without fertilizers (CK) and those with combinations of fertilizer nitrogen (N), phosphorus (P) and potassium (K): N, NP, NK, PK, NPK and NPK plus organic manure (OM). Population sizes of AOB and AOA changed greatly in response to the different fertilization treatments. The NPK + OM treatment had the highest copy numbers of AOB and AOA amoA genes among the treatments that received mineral fertilizers, whereas the lowest copy numbers were recorded in the N treatment. Ammonia‐oxidizing archaea were more abundant than AOB in all the corresponding treatments, with AOA to AOB ratios ranging from 1.02 to 12.36. Significant positive correlations were observed among the population sizes of AOB and AOA, soil pH and potential nitrification rates, indicating that both AOB and AOA played an important role in ammonia oxidation in the soil. Phylogenetic analyses of the amoA gene fragments showed that all AOB sequences from different treatments were affiliated with Nitrosospira or Nitrosospira‐ like species and grouped into cluster 3, and little difference in AOB community composition was recorded among different treatments. All AOA sequences fell within cluster S (soil origin) and cluster M (marine and sediment origin). Cluster M dominated exclusively in the N, NP, NK and PK treatments, indicating a pronounced difference in the community composition of AOA in response to the long‐term fertilization treatments. These findings could be fundamental to improve our understanding of the importance of both AOB and AOA in the cycling of nitrogen and other nutrients in terrestrial ecosystems.

Preoperative localization and minimally invasive management of primary hyperparathyroidism concomitant with thyroid disease - Yi-xiong Zheng; Shao-ming Xu; Ping Wang; Li Chen (Journal of Zhejiang University-SCIENCE B, 2007)

The role of iNOS-derived NO in the antihypertrophic actions of B-type natriuretic peptide in neonatal rat cardiomyocytes - Tiannan Wang; Ming Yan; Jieyue Li; Xiaoxiang Zheng (Molecular and Cellular Biochemistry, 2007)

Cloning and identification of partial DNA fragment for the B mating-type factor in Lentinula edodes using degenerate PCR - An-Zheng Li; Xue-Feng Xu; Fan-Xue Lin; Shui-Ming Cheng; Fang-Can Lin (World Journal of Microbiology and Biotechnology, 2007)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Ala45Thr variation in neuroD1 gene is associated with early-onset type 2 diabetes with or without diabetic pedigree in Chinese - Limei Liu; Weiping Jia; Taishan Zheng; Ming Li; Huijuan Lu; Kunsan Xiang (Molecular and Cellular Biochemistry, 2006)

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Shi-Ping Chen; Zheng-Wen Wang; Quan-Sheng Chen; Wen-Ming Bai (Oecologia, 2006)

Seasonal Variation of Virioplankton in a Eutrophic Shallow Lake - Yan-Ming Liu; Qi-Ya Zhang; Xiu-Ping Yuan; Zheng-Qiu Li; Jian-Fang Gui (Hydrobiologia, 2006)

The Genetic Diversity and Similarities Among Kengyilia Species Based on Random Amplified Microsatellite Polymorphism (RAMP) - Li Zhang; You-Liang Zheng; Yu-Ming Wei; Shi-Gui Liu; Yong-Hong Zhou (Genetic Resources and Crop Evolution, 2005)

Genome-wide Introgression Lines and their Use in Genetic and Molecular Dissection of Complex Phenotypes in Rice (Oryza sativa L.) - Zhi-Kang Li; Bin-Ying Fu; Yong-Ming Gao; Jian-Long Xu; J. Ali; H. R. Lafitte; Yun-Zhu Jiang; J. Domingo Rey; C. H. M. Vijayakumar; R. Maghirang; Tian-Qing Zheng; Ling-Hua Zhu (Plant Molecular Biology, 2005)

Construction of a genetic linkage map and QTL analysis of fiber-related traits in upland cotton (Gossypium hirsutum L.) - Zheng-Sheng Zhang; Yue-Hua Xiao; Ming Luo; Xian-Bi Li; Xiao-Ying Luo; Lei Hou; De-Mou Li; Yan Pei (Euphytica, 2005)

U–Pb and Hf-isotope analysis of zircons in mafic xenoliths from Fuxian kimberlites: evolution of the lower crust beneath the North China craton - Jianping Zheng; W. L. Griffin; Suzanne Y. O’Reilly; Fengxiang Lu; Chunmei Yu; Ming Zhang; Huimin Li (Contributions to Mineralogy and Petrology, 2004)

Co-inheritance of specific genotypes of HSPG and ApoE gene increases risk of type 2 diabetic nephropathy - Limei Liu; Kunsan Xiang; Taishan Zheng; Rong Zhang; Ming Li; Jie Li (Molecular and Cellular Biochemistry, 2003)

The heparan sulfate proteoglycan gene polymorphism: Association with type 2 diabetic nephropathy in Chinese - Limei Liu; Kunsan Xiang; Taishan Zheng; Rong Zhang; Ming Li; Yanqing Wang; Huijuan Li; Jie Li (Molecular and Cellular Biochemistry, 2003)

Recovery of transgenic orchid plants with hygromycin selection by particle bombardment to protocorms - Zhihua Yu; Minyong Chen; Lin Nie; Huafei Lu; Xiaotian Ming; Honghong Zheng; Li-Jia Qu; Zhangliang Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Recovery of transgenic rice plants expressing the rice dwarf virus outer coat protein gene (S8) - H. H. Zheng; Y. Li; Z. H. Yu; W. Li; M. Y. Chen; X. T. Ming; R. Casper; Z. L. Chen (Theoretical and Applied Genetics, 1997)